Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (2026)
(1) Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g., gamete interactions), which are likely affected by temperature. (2) Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. (3) We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus. Under typical thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favor preferred, dominant males over sneaker males. (4) We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. (5) Our results highlight that considering the thermal sensitivity of female-male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction, and sexual selection.
Keywords: Climate change; Gamete; Mate choice; Mating; Mating system; Operational sex ratio; Sexual selection; Sperm; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Reproduction is often more thermally sensitive than survival. Thus, understanding the thermal sensitivity of reproductive interactions is crucial given global warming. However, it is unknown how temperature influences female control over fertilization after mating ( i.e., cryptic female choice). We tested how temperatures relevant to current conditions and climate change projections influence cryptic female choice in a marine fish, Symphodus ocellatus . Under typical conditions, females bias fertilization dynamics to favor dominant males. We find that warmer temperatures decrease female influence on sperm velocity and reduce the expected paternity of dominant males. Our results demonstrate that temperatures relevant to climate change can shift the balance between mate choice and male-male competition. Thus, climate change may influence sexual selection, leading to evolutionary changes in reproductive traits.
Keywords: Geology; Oceanography; dept.psy

Role of an Intermediary Organization and State Government Partnership to Advance Practice and Policy in Children’s Behavioral Health - Lang, Jason; Randall, Kellie; Kelly, A.; Bracey, Jeana; Bridges-Hightower, Jenny; Newkirk, Katie; Lu, Jack; Gregory, Francis; Duran, Tracy; Geib, Catherine; Bozak, Stephanie; Mackey, Jocelyn; et al. (Prevention Science, 2026)
Keywords: Behavioral health; Bridge (graph theory); Diversity (politics); General partnership; Government (linguistics); Intermediary organization; Partnership; Plan (archaeology); Policy; Public policy; Research; State (computer science); System development; Workforce; Workforce development; dept.psy

Actigraphy-based sleep outcomes in substance use disorders: A systematic review and meta-analysis - Naveda, Alisson; Oliva, Henrique; Pulido-Saavedra, Alejandra; Ghadimi, Delaram; Moore, James; Morgan, Peter; Potenza, Marc; Angarita, Gustavo (Sleep Medicine Reviews, 2026)
Keywords: MEDLINE; Polysomnography; Sleep (system call); Substance use; Systematic review; dept.psy

Thinking differently: neurodivergent traits and responses to thought experiments in philosophers and the general population - McKee, Paul; Boulhadi, Khaoula; Weymouth, Helena; Nadelhoffer, Thomas (Philosophical Psychology, 2026)
Philosophers have long speculated that individual differences in temperament influence philosophical thinking, yet empirical research has rarely explored the role of neurodivergent traits in this domain. In this large online study (N = 1,254), we investigated whether participants with training in philosophy differ from the general population when it comes to six psychological traits–autism, ADHD, aphantasia, anendophasia, anauralia, and representational manipulation–and also whether these traits correlate with responses to two widely studied philosophical thought experiments: the “trolley problem” and the “rollback deterministic universe.” Compared to the general population, participants with training in philosophy had higher scores on measures of ADHD, internal verbalization, and representational manipulation, but lower scores on measures of visual imagery. These cognitive traits were also correlated with participants’ moral and metaphysical judgments (independent of their level of philosophical training)–e.g. participants who scored higher in visualization were less likely to judge that hitting the switch in the trolley problem is permissible but not obligatory, and also less likely to attribute free will and moral responsibility to agents in the rollback universe. Finally, we employed machine learning to develop predictive models that classify a randomly selected participant as either a philosopher or a non-philosopher. Models trained solely on responses to measures for neurodivergent traits achieved better performance than models trained solely on responses to philosophical thought experiments. This suggests that stable, trait-level neurodivergent characteristics may be more diagnostic of philosophical interest, aptitude, or training than judgments philosophers make on domain-relevant problems. © 2026 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Neurodiversity; dept.psy; experimental philosophy; free will beliefs; general population; moral judgment; philosophers

Investigating the analytical robustness of the social and behavioural sciences - Aczel, Balazs; Szaszi, Barnabas; Clelland, Harry T.; Kovacs, Marton; Holzmeister, Felix; van Ravenzwaaij, Don; Schulz-Kümpel, Hannah; Hoffmann, Sabine; Nilsonne, Gustav; Kosa, Livia; Torma, Zoltan A.; Abdelfatah, Yousuf; et al. (Nature, 2026)
The same dataset can be analysed in different justifiable ways to answer the same research question, potentially challenging the robustness of empirical science1-3. In this crowd initiative, we investigated the degree to which research findings in the social and behavioural sciences are contingent on analysts' choices. We examined a stratified random sample of 100 studies published between 2009 and 2018, in which, for one claim per study, at least five reanalysts independently reanalysed the original data. The statistical appropriateness of the reanalyses was assessed in peer evaluations, and the robustness indicators were inspected along a range of research characteristics and study designs. We found that 34% of the independent reanalyses yielded the same result (within a tolerance region of ±0.05 Cohen's d) as the original report; with a four times broader tolerance region, this indicator increased to 57%. Of the reanalyses conducted, 74% reached the same conclusion as the original investigation, 24% yielded no effects or inconclusive results and 2% reported the opposite effect. This exploratory study indicates that the common single-path analyses in social and behavioural research should not be simply assumed to be robust to alternative analyses4. Therefore, we recommend the development and use of practices to explore and communicate this neglected source of uncertainty. © 2026. The Author(s), under exclusive licence to Springer Nature Limited.
Keywords: Behavioural sciences; Empirical research; Exploratory research; Robustness (evolution); Sample size determination; Statistical analysis; dept.psy

General trait and workplace fear of missing out (FoMO) and the neurodiverse mind: Exploring autism, ADHD, and internal representation profiles - McKee, Paul; Boulhadi, Khaoula; Nadelhoffer, Thomas (Personality and Individual Differences, 2026)
Keywords: Mental representation; Psychometrics; Representation (politics); Social perception; Trait; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (Functional Ecology, 2026)
Abstract Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g. gamete interactions), which are likely also affected by temperature. Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus . Under typical, cooler thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favour preferred, dominant males over sneaker males. We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. Our results highlight that considering the thermal sensitivity of female–male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction and sexual selection. Read the free Plain Language Summary for this article on the Journal blog.
Keywords: Gamete; Mating; Mating system; Reproduction; Reproductive success; Sexual selection; Sperm; Sperm competition; alternative reproductive tactics; climate change; dept.psy; mating systems; ovarian fluid; sexual selection; sperm competition; thermal ecology

Actigraphy-based sleep outcomes in substance use disorders: A protocol for a systematic review and meta-analysis - Naveda, Alisson; Oliva, Henrique; Ghadimi, Delaram; Angarita, Gustavo (PLoS ONE, 2026)
INTRODUCTION: Individuals with substance use disorders (SUDs) are at increased risk for sleep disturbances, creating a bidirectional relationship that may heighten relapse risk. While polysomnography is the gold standard for measuring sleep, many studies have used actigraphy, a noninvasive, wrist-worn device that estimates rest-activity patterns and sleep-wake characteristics. Despite its utility, the use of actigraphy in populations with SUDs remains limited, and findings vary across substances and methodologies. This protocol outlines a systematic review and meta-analysis aiming to synthesize evidence on actigraphy-derived sleep outcomes across various substances. METHOD AND ANALYSIS: We will include peer-reviewed observational or interventional studies involving individuals aged 18 or older with a diagnosis of substance use (e.g., alcohol, benzodiazepines, cannabis, cocaine, opioids, methamphetamine, or nicotine) who use actigraphy to assess sleep compared to matched controls. Studies will be excluded during screening if they do not use actigraphy, do not include populations with SUDs, or focus on participants younger than 18. There will be no restrictions on location, setting, or language. Databases to be searched include PubMed, Scopus, Web of Science, ProQuest, ClinicalTrials.gov, CINAHL, PsycINFO, and Embase. Titles and abstracts will be screened in the first phase, followed by full-text screening using eligibility criteria. At least two independent reviewers will assess risk of bias using the Risk Of Bias In Non-randomized Studies of Exposures (ROBINS-E) tool. A synthesis will summarize key findings, including study characteristics, population differences, and methodological variations. DISCUSSION: This review will offer a clear and comprehensive assessment of the current literature on actigraphy to examine sleep in SUD and to inform future research to study sleep and its implications in SUD populations. PROTOCOL REGISTRATION NUMBER: International Prospective Register for Systematic Reviews (PROSPERO) number CRD420251072028.
Keywords: MEDLINE; Prospective cohort study; Protocol (science); Substance use; Systematic review; dept.psy

Conflict and cooperation in male–male partnerships alter paternal care behavior in the ocellated wrasse - Hellmann, Jennifer; Stiver, Kelly; Marsh‐Rollo, Susan; Alonzo, Suzanne (Behavioral Ecology, 2025)
Keywords: Biology; Fish; Fishery; Genetics; Paternal care; Symphodus ocellatus; Wrasse; Zoology; dept.psy; parental care; plasticity; reproduction; sexual selection; temperature

Breaking the truth bias: the impact of comparable truth baselines and reality interview on veracity judgments by laypeople and police officers - Bogaard, Glynis; Nieuwkamp, Veerle; Colwell, Kevin (Police Practice and Research, 2025)
This study examined whether embedding baselining within the Reality Interview (RI) protocol enhances intuitive veracity judgments. Baselining involves using a person's truthful verbal behavior as a reference point for evaluating the veracity of subsequent statements. We hypothesized that access to a comparable truth baseline (CTB) would improve veracity judgment accuracy. Eyewitnesses of a mock crime were interviewed with the RI and instructed to respond either honestly or deceptively. Laypeople (Experiment 1) and police officers (Experiment 2) evaluated these statements with or without a CTB. With a CTB, laypeople showed significantly higher accuracy in detecting deception and a reduced truth bias. However, police officers showed no improvement, maintaining chance-level performance regardless of statement veracity. These findings suggest that CTBs enhance lie detection in laypeople but not in trained professionals. Future research should explore tailored approaches to improving veracity judgments, perhaps incorporating specific guidelines on how to best use available cues.
Keywords: Baseline (sea); Comparable Truth Baseline; Deception; Interview; Lie detection; Point (geometry); Protocol (science); Reality Interview; Statement (logic); Trustworthiness; dept.psy; lie detection; verbal cues

Pharmacotherapies for stimulant use disorder and co-occurring attention deficit hyperactivity disorder: protocol for a systematic review and a meta-analysis - Oliva, Henrique; Pulido-Saavedra, Alejandra; Paredes-Naveda, Alisson; Forselius, Emerson; Potenza, Marc; Jegede, Oluwole; Angarita, Gustavo (Frontiers in Psychiatry, 2025)
Background Stimulant use disorder (StUD) and attention-deficit/hyperactivity disorder (ADHD) frequently co-occur. This comorbidity complicates treatment and worsens clinical outcomes. Despite the high prevalence, shared vulnerability and clinical relevance of this comorbidity, evidence on effective pharmacotherapies among individuals with this dual diagnosis remains limited. Materials and methods This systematic review protocol is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) statement and will include randomized controlled trials involving adults with comorbid StUD (cocaine, amphetamines, or methamphetamines) and ADHD. The following databases will be searched: PubMed, Embase, Scopus, and Web of Science. Covidence will be used to support independent screening and data extraction. Two reviewers will independently screen studies (title/abstract and full text). One author will extract data, which will be independently verified by a second reviewer. Quality assessment of included articles will be assessed using the Cochrane Risk of Bias instrument, and certainty of the evidence for each outcome will be assessed using Grading of Recommendations, Assessment, Development and Evaluations (GRADE) methodology. Primary outcomes include duration of continuous abstinence, odds of stimulant-negative urine samples, ADHD symptom changes, and medication adverse events. Where feasible, meta-analyses will be conducted using random-effects models. Significance and dissemination This review will synthesize existing evidence on the efficacy of pharmacotherapies (stimulants and non-stimulants) for individuals with co-occurring StUD and ADHD. The results of this study will likely inform clinical practice by evaluating outcomes such as reduction in stimulant use and abstinence, and improvement in ADHD symptoms. Findings will be disseminated through peer-reviewed publication and presentations to reach both clinical and academic audiences. Systematic review registration PROSPERO, CRD420250655356.
Keywords: Alternative medicine; Atomoxetine; Attention deficit hyperactivity disorder; Clinical psychology; Internal medicine; Medicine; Meta-analysis; Methylphenidate; Protocol (science); Psychiatry; Psychology; Stimulant; attention deficit hyperactivity disorder; co-occurring disorder; cocaine; dept.psy; methamphetamine; stimulant use disorder

Masked-Speech Recognition and Self-Reported Functional Listening in Autistic Young Adults - Wasiuk, Peter; Cook, Barbara; Irwin, Julia (Journal of Speech Language and Hearing Research, 2025)
Keywords: Active listening; Audiology; Autism; Cognitive psychology; Communication; Developmental psychology; Medicine; Perception; Psychology; Speech perception; dept.cmd; dept.psy

Writing Wisdom, Reviewing Identity: Positive Outcomes of Participating in a Memoir Course for Older Adults - Bivona, Marissa A.; Kahlbaugh, Patricia E.; Budnick, Christopher J. (The International Journal of Reminiscence and Life Review, 2020)
Constructing a personal narrative and consolidating identity is an ongoing process that becomes pressing in the face of mortality. The current pilot study examined the process of life review in a sample of older people, specifically examining the effects of participation in a memoir course on wisdom, identity, and well-being. We hypothesized that wisdom, identity fidelity and coherence, and subjective well-being would increase for those in the memoir group compared to a control. Eighteen elderly individuals from two senior retirement communities were randomly assigned to participate in weekly classes, for four weeks, either to work on a memoir or discuss films (control group). After engaging in the process of organizing their life story and writing about important memories, the nine individuals in the memoir group scored significantly higher on self-report measures of wise reminiscence, identity fidelity, and subjective well-being compared to those in the control group. Furthermore, exploratory analyses found that wise reminiscence statistically mediated relationships between the memoir condition and the outcome measures of identity fidelity, identity coherence, and subjective well-being. These findings point to the benefits of memoir writing for positive aging as well as potential mechanisms underlying its effectiveness.
Keywords: Identity; Life Review; Narrative; Subjective Well-Being; Wisdom; dept.psy

Turning molehills into mountains: Sleepiness increases workplace interpretive bias - Barber, Larissa K.; Budnick, Christopher J. (Journal of Organizational Behavior, 2015)
Three studies draw from evolutionary theory to assess whether sleepiness increases interpretive biases in workplace social judgments. Study 1 established a relationship between sleepiness and interpretive bias using ambiguous interpersonal scenarios from a measure commonly used in personnel selection (N = 148). Study 2 explored the boundary conditions of the sleepiness–interpretive bias link via an experimental online field survey of U.S. adults (N = 433). Sleepiness increased interpretive bias when social threats were clearly present (unfair workplace) but did not affect bias in the absence of threat (fair workplace). Study 3 replicated and extended findings from the previous two studies using objective measures of sleep loss and a quasi-experimental manipulation of minor sleep loss (N = 175). Negative affect, ego depletion, or personality variables did not influence the observed relationships. Overall, results suggest that a self-protection/evolutionary perspective best explains the effects of sleepiness on workplace interpretive biases. These studies advance the current research on sleep in organizations by adding a cognitive “threat interpretation” bias approach to past work examining the emotional reaction/behavioral side of sleep disruption. Interpretive biases due to sleepiness may have significant implications for employee health and counterproductive behavior. Copyright © 2015 John Wiley & Sons, Ltd.
Keywords: Conditional Reasoning Test of Aggression; dept.psy; fairness; interpretive bias; sleep; work perceptions

Attitudes About Aging and Beliefs About When you Have Been or Will be Your Best Self - Kahlbaugh, Patricia; Biblekaj, Viktoria; Shortell, Malori (The International Journal of Aging and Human Development, 2025)
Keywords: Anxiety; Clinical psychology; Developmental psychology; Gerontology; Healthy aging; Internalization; Medicine; Psychiatry; Psychology; Successful aging; dept.psy; peer-reviewed

Fear of Missing Out’s (FoMO) relationship with moral judgment and behavior - McKee, Paul C.; Senthilnathan, Ithika; Budnick, Christopher J.; Bind, Marie-Abèle; Antonios, Imad; Sinnott-Armstrong, Walter (PLOS ONE, 2024)
Across three online studies, we examined the relationship between the Fear of Missing Out (FoMO) and moral cognition and behavior. Study 1 (N = 283) examined whether FoMO influenced moral awareness, judgments, and recalled and predicted behavior of first-person moral violations in either higher or lower social settings. Study 2 (N = 821) examined these relationships in third-person judgments with varying agent identities in relation to the participant (agent = stranger, friend, or someone disliked). Study 3 (N = 604) examined the influence of recalling activities either engaged in or missed out on these relationships. Using the Rubin Causal Model, we created hypothetical randomized experiments from our real-world randomized experimental data with treatment conditions for lower or higher FoMO (median split), matched for relevant covariates, and compared differences in FoMO groups on moral awareness, judgments, and several other behavioral outcomes. Using a randomization-based approach, we examined these relationships with Fisher Tests and computed 95% Fisherian intervals for constant treatment effects consistent with the matched data and the hypothetical FoMO intervention. All three studies provide evidence that FoMO is robustly related to giving less severe judgments of moral violations. Moreover, those with higher FoMO were found to report a greater likelihood of committing moral violations in the past, knowing people who have committed moral violations in the past, being more likely to commit them in the future, and knowing people who are likely to commit moral violations in the future.
Keywords: Behavior; Interpersonal relationships; Machine learning; Memory recall; Moral philosophy; Personality; Religion; Social media; dept.csc; dept.psy; peer-reviewed

Using the Listening2Faces App with Three Young Adults with Autism: A Feasibility Study - Baron, Alisa; Harwood, Vanessa; Woodard, Cooper; Anderson, Kaitlyn; Fernandes, Barbara; Sullivan, Jessica; Irwin, Julia (Advances in Neurodevelopmental Disorders, 2024)
Abstract Objectives Listening2Faces (L2F) is a therapeutic, application-based training program designed to improve audiovisual speech perception for persons with communication disorders. The purpose of this research was to investigate the feasibility of using the L2F application with young adults with autism and complex communication needs. Methods Three young adults with autism and complex communication needs completed baseline assessments and participated in training sessions within the L2F application. Behavioral supports, including the use of cognitive picture rehearsal, were used to support engagement with the L2F application. Descriptive statistics were used to provide (1) an overview of the level of participation in L2F application with the use of behavioral supports and (2) general performance on L2F application for each participant. Results All three participants completed the initial auditory noise assessment (ANA) as well as 8 or more levels of the L2F application with varying accuracy levels. One participant completed the entire L2F program successfully. Several behavioral supports were used to facilitate participation; however, each individual demonstrated varied levels of engagement with the application. Conclusions The L2F application may be a viable intervention tool to support audiovisual speech perception in persons with complex communication needs within a school-based setting. A review of behavioral supports and possible beneficial modifications to the L2F application for persons with complex communication needs are discussed.
Keywords: dept.psy; peer-reviewed

Sleep Health among Children Adopted from Foster Care: The Moderating Effect of Parent–Child Sleep Interactions - Cifre, Anthony B.; Budnick, Christopher J.; Bick, Johanna; McGlinchey, Eleanor L.; Ripple, Carol H.; Wolfson, Amy R.; Alfano, Candice A. (Behavioral Sleep Medicine, 2024)
Keywords: dept.psy; peer-reviewed

Best Darn Statistics Workbook Ever - Hauselt, William J.; Mugno, Raymond (Kendall Hunt Publishing, 2021)
Keywords: dept.mat; dept.psy

The role of combat exposure on drinking behavior and subjective well-being: A Rubin Causal Model approach. - McKee, Paul; Budnick, Christopher J.; Walters, Kenneth S.; Bind, Marie-Abèle (Psychological Trauma: Theory, Research, Practice, and Policy, 2024)
Keywords: dept.psy; peer-reviewed

Developmental Themes in the Narrative of Adults with Early International Experiences - Abe, Jo Ann A. (Journal of Adult Development, 2023)
This study extends research on adult narrative identity in two major ways. First, it focuses on Adult Third Culture Kids (ATCKs), which refer to individuals who spent a part of their early developmental years abroad. In spite of the fact that they are an important demographic to study in this rapidly globalizing world, they have tended to be neglected in the field of psychology. Second, this study incorporates the cutting-edge tools of automated language analysis to extract developmental themes from autobiographical narratives using a bottom-up exploratory approach, as well as to identify psychological patterns and processes associated with the themes. The participants (N = 350; 18–80 + years old) were recruited from an alumni office of an international school and asked to write a narrative about the impact their international experiences had on their development. The meaning extraction method (MEM) yielded four developmental themes, which were remarkably consistent with the recurring themes that emerge from past research on adult narrative identity as well as ATCKs: past focus, communion, agency, and global focus. These four developmental themes, in turn, showed theoretically coherent patterns of relations with the demographic variables, linguistic markers of psychological patterns and processes, as well as self-reports of dimensions of well-being.
Keywords: Adult third culture kids (ATCKs); LIWC; MEH; Meaning extraction method; Narrative identity; dept.psy; peer-reviewed

Event-Related Potentials in Assessing Visual Speech Cues in the Broader Autism Phenotype: Evidence from a Phonemic Restoration Paradigm - Harwood, Vanessa; Baron, Alisa; Kleinman, Daniel; Campanelli, Luca; Irwin, Julia; Landi, Nicole (Brain Sciences, 2023)
Audiovisual speech perception includes the simultaneous processing of auditory and visual speech. Deficits in audiovisual speech perception are reported in autistic individuals; however, less is known regarding audiovisual speech perception within the broader autism phenotype (BAP), which includes individuals with elevated, yet subclinical, levels of autistic traits. We investigate the neural indices of audiovisual speech perception in adults exhibiting a range of autism-like traits using event-related potentials (ERPs) in a phonemic restoration paradigm. In this paradigm, we consider conditions where speech articulators (mouth and jaw) are present (AV condition) and obscured by a pixelated mask (PX condition). These two face conditions were included in both passive (simply viewing a speaking face) and active (participants were required to press a button for a specific consonant–vowel stimulus) experiments. The results revealed an N100 ERP component which was present for all listening contexts and conditions; however, it was attenuated in the active AV condition where participants were able to view the speaker’s face, including the mouth and jaw. The P300 ERP component was present within the active experiment only, and significantly greater within the AV condition compared to the PX condition. This suggests increased neural effort for detecting deviant stimuli when visible articulation was present and visual influence on perception. Finally, the P300 response was negatively correlated with autism-like traits, suggesting that higher autistic traits were associated with generally smaller P300 responses in the active AV and PX conditions. The conclusions support the finding that atypical audiovisual processing may be characteristic of the BAP in adults.
Keywords: audiovisual; dept.psy; event-related potentials; peer-reviewed; phonemic restoration; speech perception

Lifespan Development. - Anthis, Kristine (2007)
Keywords: dept.psy; faculty_collection; sabbatical_report

EdPsych Modules. - Durwin, Cheryl C. (2007)
Keywords: dept.psy; faculty_collection; sabbatical_report

Re-Examining the Long-Term Effects of Experiencing Parental Death in Childhood on Adult Psychopathology. - Jacobs, John R. (2006)
Keywords: dept.psy; faculty_collection

Learning and Behavior. - Mazur, James E. (2004)
Keywords: dept.psy; faculty_collection; sabbatical_report

Resource Manual for Psychology and Law. - Tolchin, Gerald (Fall;Psychology., 2000)
Keywords: dept.psy; faculty_collection; sabbatical_report

Longitudinal Effects of Early Reading Interventions on Normed, Standardized Reading Outcome Measures. - Carroll, Deborah A. (2019)
Keywords: dept.psy; faculty_collection; sabbatical_report

Learning and Behavior - Mazur, James E. (Pearson, 2013)
Keywords: Learning, Psychology of; Conditioned response; Behavior modification; Psychology, Comparative; dept.psy

Mrs. Job - Affinito, Mona Gustafson (iUniverse Inc, 2009)
"Beautiful, feisty Dara, rising from nomad to princess, experiences joy, spiritual and marital conflict, and unspeakable trials, without surrendering her love for Job and for her best friend Adah"--p. 4 of Cover.
Keywords: Christianity; Fiction; Religious fiction, American; Fiction; Suffering; Fiction; Wives; Job (Biblical figure); Religious aspects; dept.psy; faculty_collection

Forgiving One Page at a Time: The Diary of Your Journey to Restoration and Confidence - Affinito, Mona Gustafson (AuthorHouse, 2007)
Keywords: Forgiveness; dept.psy; faculty_collection

Learning and Behavior - Mazur, James E. (Pearson/Prentice Hall, 2006)
Keywords: Learning, Psychology of; Textbooks; Textbooks; Behavior modification; Textbooks; Conditioned response; Textbooks; Psychology, Comparative; dept.psy; faculty_collection

Sabbatical Leave Report - Sherman, William M. (2005)
Sabbatical leave report outlining time spent revising the textbook, "Behavior modification", conducting a research project entitled "Motherhood ideology, role balance, and health-promoting behaviors of non-tenured academic mothers with preschool children", and working on course proposals for the Department of Psychology.
Keywords: dept.psy; faculty_collection; sabbatical_report

The Roles of Vasopressin and Oxytocin in Memory Processing - McEwen, Barbara B. (Advances in pharmacology ; v. 50, 2004)
Keywords: Physiological aspects; Research; Memory; Research; Neuropeptides; Research; Oxytocin; Vasopressin; dept.psy; faculty_collection

Emergence of Uncertainty: A Microgenetic Study of the Preschool Period, Sabbatical Leave Report - Kahlbaugh, Patricia (2003)
Keywords: dept.psy; faculty_collection; sabbatical_report

College student Fear of Missing Out (FoMO) and maladaptive behavior: Traditional statistical modeling and predictive analysis using machine learning - McKee, Paul C.; Budnick, Christopher J.; Walters, Kenneth S.; Antonios, Imad (PLOS ONE, 2022)
This paper reports a two-part study examining the relationship between fear of missing out (FoMO) and maladaptive behaviors in college students. This project used a cross-sectional study to examine whether college student FoMO predicts maladaptive behaviors across a range of domains (e.g., alcohol and drug use, academic misconduct, illegal behavior). Participants (N = 472) completed hard copy questionnaire packets assessing trait FoMO levels and questions pertaining to unethical and illegal behavior while in college. Part 1 utilized traditional statistical analyses (i.e., hierarchical regression modeling) to identify any relationships between FoMO, demographic variables (socioeconomic status, living situation, and gender) and the behavioral outcomes of interest. Part 2 looked to quantify the predictive power of FoMO, and demographic variables used in Part 1 through the convergent approach of supervised machine learning. Results from Part 1 indicate that college student FoMO is indeed related to many diverse maladaptive behaviors spanning the legal and illegal spectrum. Part 2, using various techniques such as recursive feature elimination (RFE) and principal component analysis (PCA) and models such as logistic regression, random forest, and Support Vector Machine (SVM), showcased the predictive power of implementing machine learning. Class membership for these behaviors (offender vs. non-offender) was predicted at rates well above baseline (e.g., 50% at baseline vs 87% accuracy for academic misconduct with just three input variables). This study demonstrated FoMO’s relationships with these behaviors as well as how machine learning can provide additional predictive insights that would not be possible through inferential statistical modeling approaches typically employed in psychology, and more broadly, the social sciences. Research in the social sciences stands to gain from regularly utilizing the more traditional statistical approaches in tandem with machine learning.
Keywords: Alcohol consumption; Behavior; Cannabis; Drug interactions; Forecasting; Machine learning; Machine learning algorithms; Principal component analysis; dept.csc; dept.psy; peer-reviewed

Preparing Children for Reading Success: Hands-On Activities for Librarians, Educators, and Caregivers - Irwin, Julia; Moore, Dina (Rowman & Littlefield Publishers, 2014)
Designed to familiarize anyone who reads to young children with the essentials of promoting early and emerging literacy. Irwin and Moore share activities that can be used to foster this critical skill development, and have linked these activities to popular children's books.--
Keywords: Books and reading; Creative activities and seat work; Reading; Literacy; Children; dept.psy; faculty_collection

Empowering Young Readers: Dialogic Reading with Integrated Vocabulary Enrichment - Moore, Dina; Durwin, Cheryl C. (Rowman & Littlefield Publishers, 2022)
Keywords: dept.psy

Cognitive-Affective Styles of Biden and Trump Supporters: An Automated Text Analysis Study - Abe, Jo Ann A. (Social Psychological and Personality Science, 2022)
Are conservatives more simple-minded and happier than liberals? To revisit this question, 1,518 demographically diverse participants (52% females) were recruited from an online participant-sourcing platform and asked to write a narrative about the upcoming 2020 U.S. Presidential Election as well as complete self and candidates’ ratings of personality. The narratives were analyzed using three well-validated text analysis programs. As expected, extremely enthusiastic Trump supporters used less cognitively complex and more confident language than both their less enthusiastic counterparts and Biden supporters. Trump supporters also used more positive affective language than Biden supporters. More simplistic and categorical modes of thinking as well as positive emotional tone were also associated with positive perceptions of Trump’s, but not Biden’s personality. Dialectical complexity and positive emotional tone accounted for significant unique variance in predicting appraisals of Trump’s trustworthiness/integrity even after controlling for demographic variables, self-ratings of conscientiousness and openness, and political affiliation.
Keywords: AutoIC; FFM; LIWC; cognitive-affective styles; dept.psy; peer-reviewed; political preferences

Multiple Independent Identification Decisions: A Method of Calibrating Eyewitness Identifications - Pryke, S.; Lindsay, R.C.L.; Dysart, J.E.; Dupuis, P. (Journal of Applied Psychology, 2004)
Two experiments (N = 147 and N = 90) explored the use of multiple independent lineups to identify a target seen live. In Experiment 1, simultaneous face, body, and sequential voice lineups were used. In Experiment 2, sequential face, body, voice, and clothing lineups were used. Both studies demonstrated that multiple identifications (by the same witness) from independent lineups of different features are highly diagnostic of suspect guilt (G. L. Wells & R. C. L. Lindsay, 1980). The number of suspect and foil selections from multiple independent lineups provides a powerful method of calibrating the accuracy of eyewitness identification. Implications for use of current methods are discussed.
Keywords: Decision Making; Humans; Recognition (Psychology); Visual Perception; article; decision making; dept.psy; human; recognition; vision

Possible selves in the lives of adult women: A short-term longitudinal study - Anthis, K. (Possible Selves: Theory, Res. and Appl., 2006)
The current study examined the number and content of possible selves in the lives of adult women over the course of a five-month interval. Based on previous empirical studies of possible selves, a variety of hypotheses were proposed that addressed cohort differences in possible selves, continuity and change in possible selves, and predicting changes in possible selves over time with ego-identity. The results indicated mixed support for the hypotheses, but basically replicated previous research findings on possible selves. The findings are discussed in terms of how they extend both descriptive and predictive knowledge of possible selves. © 2006 by Nova Science Publishers, Inc. All rights reserved.
Keywords: dept.psy

The test of malingered incompetence (TOMI): A forced-choice instrument for assessing cognitive malingering in competence to stand trial evaluations - Colwell, K.; Colwell, L.H.; Perry, A.T.; Wasieleski, D.; Billings, T. (American Journal of Forensic Psychology, 2008)
The TOMI consists of two 25-item, two-alternative, forced-choice scales - General Knowledge (TOMI-G) and Legal Knowledge (TOMI- L) - designed to detect malingered cognitive impairment in CST evaluations. The TOMI was derived and validated with a university sample (N = 242), with a cut score of < 21 providing maximum classification accuracy of hon est and dishonest respondents. Subsequently, the TOMI was administered to forensic inpatient residents (N = 30) and was compared to existing, well- established tests of malingering (the Rey-FIT and the TOMM). Results indi cated strong correlations and predictive agreement for both scales, and dis tinction between honest and probable dishonest respondents for the TOMI-L. A third study provided additional validation for the TOMI in distinguishing honest from dishonest student respondents (N = 120) and examined the ef fects of motivation on response style. For dishonest responders, those in the high motivation group scored significantly lower than those in the low moti vation group, further betraying their dishonesty. The utility of the TOMI as a useful, novel tool for forensic practitioners is discussed. Copyright 2008 American Journal of Forensic Psychology.
Keywords: adult; article; clinical evaluation; cognitive defect; controlled study; dept.psy; diagnostic and statistical manual of mental disorders; female; forced choice method; human; major clinical study; male; malingering; mental disease; mental performance; mental test; psychologic assessment; ⛔ No DOI found

The Tragedy of Child Care in America - Zigler, Edward; Marsland, Katherine W.; Lord, Heather (Yale University Press, 2009)
Why the United States has failed to establish a comprehensive high-quality child care program is the question at the center of this book. Edward Zigler has been intimately involved in this issue since the 1970s, and here he presents a firsthand history of the policy making and politics surrounding this important debate. Good-quality child care supports cognitive, social, and emotional development, school readiness, and academic achievement. This book examines the history of child care policy since 1969, including the inside story of America's one great attempt to create a comprehensive system of child care, its failure, and the lack of subsequent progress. Identifying specific issues that persist today, Zigler and his coauthors conclude with an agenda designed to lead us successfully toward quality care for America's children. © 2009 by Yale University. All rights reserved.
Keywords: Child care; Government policy; Services for; United States; United States; Child welfare; United States; Children; dept.psy; faculty_collection

Change in suspect's memory as a result of deception - Colwell, K.; Hiscock-Anisman, C.; Corbett, L.; Memon, A.; Hauselt, W.J.; Bonilla, Y. (American Journal of Forensic Psychology, 2011)
One hundred and eight participants either stole or replaced a stolen exam key from a professor's office. Half of the participants were instructed to respond honestly and to help with an investigation; the other half were instructed to distort their statement so they were not implicated. Participants did not know whether they would be asked to lie or report honestly during their time in the professor's office. After completing the task, participants again met with a research assistant, who instructed them whether to lie or respond honestly at a one-week follow-up. After the interview, participants completed a Likert-type post-event questionnaire. Deceivers reported significantly more anxiety and motivation not to get caught while in the office, even though there were no differences in the instructions given to the two groups until after participants left the office. Therefore, the act of deception changed their memory for their time in the office. This is important theoretically because it suggests that forming a lie script could be akin to other memories for counterfactual thinking. Practically, it is important to note that a deceptive perpetrator or detainee may never be able to actually provide an accurate account. Copyright 2011 American Journal of Forensic Psychology.
Keywords: anxiety; article; deception; dept.psy; female; follow up; honesty; human; human experiment; male; memory; motivation; normal human; offender; questionnaire; task performance; theft; thinking; ⛔ No DOI found

Forgiveness in Counseling: Caution, Definition, and Application - Affinito, M.G. (Before Forgiving: Cautionary Views of Forgiveness in Psychother., 2012)
This chapter highlights that forgiveness is a decision that clients should be helped to make and that advocacy has little place in the counseling session. It specifically confirms the value of forgiveness in the counseling setting and offers some guidelines for its effective application. There are at least three approaches to justice, altering in the extent to which they are proactive or reactive, past or future oriented, limited or general: (1) retributive justice, (2) restorative justice, and (3) pervasive justice. The pragmatic model needs an in-depth investigation of alternatives; their practical and moral costs and their benefits. It is concluded that there can be no relief unless the offender confesses and asks forgiveness, and argues that repentance is poor therapy and of questionable morality, because it leaves clients in a state of helpless dependence on the person or persons who offended them in the first place. © 2002 by Oxford University Press, Inc. All rights reserved.
Keywords: Caution; Counseling; Forgiveness; Justice; Pervasive justice; Pragmatic model; Restorative justice; Retributive justice; dept.psy

Neurobiological and behavioral studies of skilled and impaired word reading - Frost, S.J.; Sandak, R.; Mencl, W.E.; Landi, N.; Moore, D.; Porta, G.D.; Rueckl, J.G.; Katz, L.; Pugh, K.R. (Single-Word Read.: Behavioral and Biological Perspectives, 2012)
Keywords: dept.psy

Affective awareness in parenting of fathers with co-occurring substance abuse and intimate partner violence - Gilchrist, G.; Smith Stover, C.; Spink, A. (Advances in Dual Diagnosis, 2012)
Few studies have examined the parenting of fathers with cooccurring substance abuse (SA) and intimate partner violence (IPV) problems. None have specifically interviewed men with these cooccurring issues using qualitative methods about their reflective functioning in relation to their children. This paper aims to provide evidence of the reflective capacity of fathers with cooccurring SA and IPV. To assess this, men were asked to describe examples of negative emotions they experienced as parents and how they perceived their children responded to those emotions. In total, 40 fathers with cooccurring SA and IPV were interviewed using the Revised Parent Development Interview. Interviews were coded for reflective functioning and for themes that emerged related to angry and guilty feelings these fathers experienced as parents. Overall, fathers in the sample had a very limited capacity to think about the thoughts and feelings of their children. The desire to spend more time with their child and an inability to provide financially were two common themes. Anger toward the child's mother for not providing adequate care and a focus on shielding the child from his anger were also reported frequently. Fathers did not report feelings of guilt related to their substance use or aggression in their relationships. This paper is one of the first to explore reflective functioning of fathers with cooccurring IPV and SA. These findings are discussed in relation to their implications for intervention with fathers with cooccurring SA and IPV issues. © 2012, Emerald Group Publishing Limited
Keywords: Domestic violence; Drug addiction; Fathers; Intimate partner violence; Men; Parenting; Substance abuse; United States of America; dept.psy

Using acid to improve credibility assessments with written and audio statements - Montalvo, L.; Hallinan, C.; Hiscock-Anisman, C.; Morrissey, D.; Bonilla, Y.; Colwell, K. (American Journal of Forensic Psychology, 2013)
Investigators are continually faced with the task of detecting deception. Assessment Criteria Indicative of Deception (ACID) is a system of interviewing and credibility assessment that maximizes verbal cues to detect deception, and teaches content analysis that highlights attempts to withhold, distort, or manipulate information. The ACID technique has been successful in discriminating honest from deceptive statements when credibility determinations are made either by statistical methods or trained raters. Unfortunately, the training has required several hours and application has required the time-consuming process of transcription. The current study demonstrates the utility of ACID following a brief training, and compares the credibility ratings made from analysis of transcripts to the credibility ratings made from the analysis of audio recordings. Twenty-nine university undergraduate and graduate students read or listened to a series of eight transcripts. Raters were provided with accounts before training and 4 accounts after training. Prior to training, raters performed at 55% accuracy. Following training, raters performed at 71% accuracy. Additionally, there was an untrained control group that performed at 53% accuracy. Of note, the post-training performance was identical for accounts presented in written and audio formats. In sum, the ACID technique was reliable, valid, easy to train, and showed that accurate decisions can be made from simple audio recordings. Copyright 2013 American Journal of Forensic Psychology,.
Keywords: accuracy; adult; article; assessment criteria indicative of deception; audiology; clinical assessment tool; clinical decision making; clinical education; content analysis; controlled study; deception; dept.psy; human; human experiment; meaningful use criteria; reliability; statistical analysis; validity; written language; ⛔ No DOI found

Screening for reading disability in university students with phonological processing and working memory tasks - Broggi, M., Jr.; Ready, R.E.; Moore, D.L. (Dyslexia, 2019)
Many students in higher education have undiagnosed reading disabilities (RDs), but there are few measures to screen for RD in this population. The aim of this study was to determine the ability of tasks that are sensitive to RDs—such as measures of phonemic awareness and working memory—to differentiate university students previously diagnosed with RDs from controls. Participants were university students with an RD (n = 26), a clinical control group diagnosed with attention-deficit/hyperactivity disorder (n = 24), and neurotypical controls (n = 44). Participants completed brief phonological processing and working memory tasks. The RD group scored significantly lower on all tasks than both control groups. The phonological processing tasks alone—without the working memory task—discriminated participants with RDs from controls with excellent sensitivity and specificity. A brief battery of phonemic tasks could be an effective screening instrument for persons with RDs on university campuses. © 2019 John Wiley & Sons, Ltd.
Keywords: Attention Deficit Disorder with Hyperactivity; Awareness; Dyslexia; Female; Humans; Learning Disorders; Male; Memory, Short-Term; Phonetics; Reading; Students; Task Performance and Analysis; Universities; Young Adult; attention deficit disorder; awareness; dept.psy; dyslexia; female; human; learning disorder; male; peer-reviewed; phonetics; phonological processing; psychology; reading; reading disability; screening test; short term memory; student; task performance; university; university students; working memory; young adult

Navigating Ethical Challenges for Pediatric Sickle Cell Pain Management in the Context of the Opioid Epidemic - Mulchan, Siddika S.; Wakefield, Emily O.; Martin, Sarah R.; Ayr-Volta, Lauren; Krenicki, Kayla; Zempsky, William T. (The Clinical Journal of Pain, 2022)
Objectives: The aim was to describe the impact of the opioid epidemic on pain management practices in pediatric sickle cell disease (SCD) and propose a conceptual framework for navigating ethical decision-making in pediatric sickle cell pain management. Methods: A review of the literature on ethical challenges in the management of sickle cell pain was conducted and considered in the context of the opioid epidemic and psychosocial factors affecting youth with SCD. The Integrated Ethical Framework for Pain Management (IEFPM) was applied to pediatric sickle cell pain management using a clinical case example. Results: Implicit bias, health-related stigma, and potential neurocognitive impairment all present unique challenges in ethical decision-making for youth with SCD. National guidelines for prescribing opioid medication may complicate providers’ clinical decision-making and affect their sickle cell pain management practices. The IEFPM was found to be applicable to ethical decision-making for pediatric sickle cell pain and captures both patient-related and provider-related aspects of clinical pain management. Discussion: The opioid epidemic has exacerbated existing ethical challenges for pain management among youth with SCD. The IEFPM provides a conceptual model that can be integrated into health care settings to facilitate ethical decision-making and promote greater health equity in the clinical management of pediatric sickle cell pain.
Keywords: Adolescent; Analgesics; Anemia; Child; Humans; Opioid; Opioid Epidemic; Pain; Pain Management; Sickle Cell; adolescent; analgesia; child; complication; dept.psy; human; narcotic analgesic agent; pain; peer-reviewed; sickle cell anemia

Ejaculate allocation and sperm characteristics differ among alternative male types in a species of fish with cooperation and competition among unrelated males. - Alonzo, Suzanne H.; Stiver, Kelly A.; Kindsvater, Holly K.; Marsh-Rollo, Susan E.; Nugent, Bridget; Kazancıoğlu, Erem (Cells, 2021)
Sexual selection arising from sperm competition has driven the evolution of immense variation in ejaculate allocation and sperm characteristics not only among species, but also among males within a species. One question that has received little attention is how cooperation among males affects these patterns. Here we ask how male alternative reproductive types differ in testes size, ejaculate production, and sperm morphology in the ocellated wrasse, a marine fish in which unrelated males cooperate and compete during reproduction. Nesting males build nests, court females and provide care. Sneaker males only “sneak” spawn, while satellite males sneak, but also help by chasing away sneakers. We found that satellite males have larger absolute testes than either sneakers or nesting males, despite their cooperative role. Nesting males invested relatively less in testes than either sneakers or satellites. Though sneakers produced smaller ejaculates than either satellite or nesting males, we found no difference among male types in either sperm cell concentration or sperm number, implying sneakers may produce less seminal fluid. Sperm tail length did not differ significantly among male types, but sneaker sperm cells had significantly larger heads than either satellite or nesting male sperm, consistent with past research showing sneakers produce slower sperm. Our results highlight that social interactions among males can influence sperm and ejaculate production. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Animals; Fishes; Male; Reproduction; Spermatozoa; Testis; adult; animal; article; controlled study; court; dept.psy; female; fish; human cell; male; metabolism; nesting; nonhuman; peer-reviewed; phenotypic plasticity; reproduction; seminal plasma; sexual selection; social interaction; sperm competition; sperm count; spermatozoon; spermatozoon tail; testis

Does the risk of sperm competition help explain cooperation between reproductive competitors? A study in the ocellated wrasse (Symphodus ocellatus). - Stiver, Kelly A; Alonzo, Suzanne H (The American naturalist, 2013)
Although cooperating individuals may gain benefits, they risk being cheated by their allies. Therefore, to understand the persistence of cooperation by mutual benefits, it is important to document both the potential benefits of cooperation and the risks of cheating. We experimentally examined evidence of cooperation in the ocellated wrasse (Symphodus ocellatus), a fish species with males that exercise three reproductive strategies: satellite and sneaker males attempt to parasitically spawn in the nests of nesting males. Nesting males have been hypothesized to tolerate satellites as a result of satellite aid in defense against sneaker males and help in courting females. Here, we provide evidence that cooperation between reproductive competitors may arise in response to sperm competition from other males. After we experimentally removed satellites, nesting males had more sneakers at their nest and experienced a higher rate of sneaking when they spawned (increased sperm competition risk). When we experimentally distracted nesting males to prevent their acting aggressively toward satellites, satellites spawned with females and ate eggs in the nest. Our results suggest that nesting males and satellites gain fitness benefits of reduced direct reproductive and sperm competition through cooperation. However, nesting males risk losing paternity, while satellites experience increased aggression and must invest in aggression themselves (i.e., they act aggressively toward sneakers).
Keywords: *Competitive Behavior/ph [Physiology]; *Cooperative Behavior; *Perciformes/ph [Physiology]; *Sexual Behavior, Animal/ph [Physiology]; *Spermatozoa/ph [Physiology]; Aggression; Alternative male tactics; Analysis of Variance; Animals; Competition; Competitive Behavior; Cooperation; Cooperative Behavior; Female; Fertility; Fertility/ph [Physiology]; Male; Models, Biological; Nesting Behavior; Nesting Behavior/ph [Physiology]; Perciformes; Sexual Behavior, Animal; Sneak-fertilization; Sperm competition; Spermatozoa; aggression; analysis of variance; animal; article; biological model; competitive behavior; cooperation; cooperative breeding; dept.psy; female; fertility; male; nesting; peer-reviewed; perciform; persistence; physiology; reproductive strategy; sexual behavior; sneak copulation; sperm competition; spermatozoon

The Promise of Automated Home-Cage Monitoring in Improving Translational Utility of Psychiatric Research in Rodents. - Mingrone, Alfred; Kaffman, Ayal; Kaffman, Arie (Frontiers in neuroscience, 2020)
Large number of promising preclinical psychiatric studies in rodents later fail in clinical trials, raising concerns about the efficacy of this approach to generate novel pharmacological interventions. In this mini-review we argue that over-reliance on behavioral tests that are brief and highly sensitive to external factors play a critical role in this failure and propose that automated home-cage monitoring offers several advantages that will increase the translational utility of preclinical psychiatric research in rodents. We describe three of the most commonly used approaches for automated home cage monitoring in rodents [e.g., operant wall systems (OWS), computerized visual systems (CVS), and automatic motion sensors (AMS)] and review several commercially available systems that integrate the different approaches. Specific examples that demonstrate the advantages of automated home-cage monitoring over traditional tests of anxiety, depression, cognition, and addiction-like behaviors are highlighted. We conclude with recommendations on how to further expand this promising line of preclinical research. Copyright © 2020 Mingrone, Kaffman and Kaffman.
Keywords: Actual-HCA; Chora feeder; Intellicage system; PhenoTyper; Review; addiction; anxiety disorder; automated home cage monitoring; automation; behavioral science; cognition; depression; dept.psy; monitoring; nonhuman; peer-reviewed; preclinical study; psychiatry; rodent; rodents; translational research

Audiovisual speech perception in children with autism spectrum disorders: Evidence from visual phonemic restoration. - Irwin, Julia; Avery, Trey; Kleinman, Daniel; Landi, Nicole (Journal of autism and developmental disorders, 2021)
Children with autism spectrum disorders have been reported to be less influenced by a speaker’s face during speech perception than those with typically development. To more closely examine these reported differences, a novel visual phonemic restoration paradigm was used to assess neural signatures (event-related potentials [ERPs]) of audiovisual processing in typically developing children and in children with autism spectrum disorder. Video of a speaker saying the syllable /ba/ was paired with (1) a synthesized /ba/ or (2) a synthesized syllable derived from /ba/ in which auditory cues for the consonant were substantially weakened, thereby sounding more like /a/. The auditory stimuli are easily discriminable; however, in the context of a visual /ba/, the auditory /a/ is typically perceived as /ba/, producing a visual phonemic restoration. Only children with ASD showed a large /ba/-/a/ discrimination response in the presence of a speaker producing /ba/, suggesting reduced influence of visual speech. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.
Keywords: Auditory Perception; Autism Spectrum Disorder; Child; Cues; Evoked Potentials; Humans; Speech; Speech Perception; Visual Perception; association; autism; child; dept.psy; evoked response; hearing; human; peer-reviewed; speech; speech perception; vision

The offspring of alcohol-exposed sires exhibit heightened ethanol intake and behavioral alterations in the elevated plus maze. - Koabel, Jennifer; McNivens, Meghan; McKee, Paul; Pautassi, Ricardo; Bordner, Kelly; Nizhnikov, Michael (Alcohol (Fayetteville, N.Y.), 2021)
Research suggests that addictive traits are indeed heritable, but very few preclinical studies have explored transgenerational effects of paternal alcohol exposure. The present study addressed this gap in knowledge. We explored whether offspring of ethanol-exposed sires would be more likely to accept ethanol than descendants of water-exposed and control sires. We also investigated whether the second generation of ethanol-exposed descendants would accept ethanol more than controls and were more or less likely to experience anxiety-like behavior in behavioral assessments. We exposed male rats to repeated binge doses of alcohol (4 g/kg/day across 8 days), water, or left them untreated and mated them with untreated females. We then bred the offspring of these rats to test transgenerational effects of paternal alcohol exposure. We tested 14-day-old offspring from the first and second filial generation for their acceptance of ethanol and water, and measured anxiety-like behavior in 38-day-old, second-generation offspring using an elevated plus maze. The results indicate that offspring of ethanol-exposed sires increase ethanol acceptance in the first generation compared to untreated controls, whereas in the second-generation increased ethanol acceptance vs. these controls is seen in descendants of both ethanol- and vehicle-treated sires. At adolescence, the second generation of rats derived from alcohol-exposed sires exhibited significantly more time spent in the open arms and significantly more arm entries than any other group. The present study suggests that parental ethanol exposure is associated with lingering effects in the infant and adolescent offspring. The second filial generation was also found to be affected, albeit similarly by grandparental ethanol exposure or by the stress of the vehicle administration. Copyright © 2021 Elsevier Inc. All rights reserved.
Keywords: Addictive; Alcohol Drinking; Animals; Anxiety; Article; Behavior; Elevated Plus Maze Test; Ethanol; Male; Maze Learning; Rats; Sprague Dawley rat; addiction; adolescence; adolescent; adult; alcohol; alcohol consumption; animal; animal experiment; animal model; anxiety; behavior disorder; binge drinking; breeding; concentration (parameter); controlled study; dept.psy; drinking behavior; elevated plus maze test; experience; exposure; female; grandparent; inhibitory control; male; maze test; newborn; nonhuman; paternal exposure; peer-reviewed; progeny; rat; sire; vertical transmission; water

Measurement of Motivation States for Physical Activity and Sedentary Behavior: Development and Validation of the CRAVE Scale. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Fogelman, Nia; Gilson, Todd A; Stanforth, Philip R; Divin, Amanda L; Bartholomew, John B; Filgueiras, Alberto; McKee, Paul C; Ash, Garrett I; Ciccolo, Joseph T; Brotnow Decker, Line; et al. (Frontiers in psychology, 2021)
Physical activity, and likely the motivation for it, varies throughout the day. The aim of this investigation was to create a short assessment (CRAVE: Cravings for Rest and Volitional Energy Expenditure) to measure motivation states (wants, desires, urges) for physical activity and sedentary behaviors. Five studies were conducted to develop and evaluate the construct validity and reliability of the scale, with 1,035 participants completing the scale a total of 1,697 times. In Study 1, 402 university students completed a questionnaire inquiring about the want or desire to perform behaviors "at the present moment (right now). " Items related to physical activity (e.g., "move my body") and sedentary behaviors (e.g., "do nothing active"). An exploratory structural equation model (ESEM) revealed that 10 items should be retained, loading onto two factors (5 each for Move and Rest). In Study 2, an independent sample (n = 444) confirmed these results and found that Move and Rest desires were associated with stage-of-change for exercise behavior. In Study 3, 127 community-residing participants completed the CRAVE at 6-month intervals over two years- two times each session. Across-session interclass correlations (ICC) for Move (ICC = 0.72-0.95) and Rest (ICC = 0.69-0.88) were higher than when they were measured across 24-months (Move: ICC = 0.53; Rest: ICC = 0.49), indicating wants/desires have state-like qualities. In Study 4, a maximal treadmill test was completed by 21 university students. The CRAVE was completed immediately pre and post. Move desires decreased 26% and Rest increased 74%. Changes in Move and Rest desires were moderately associated with changes in perceived physical fatigue and energy. In Study 5, 41 university students sat quietly during a 50-min lecture. They completed the CRAVE at 3 time points. Move increased 19.6% and Rest decreased 16.7%. Small correlations were detected between move and both perceived energy and tiredness, but not calmness or tension. In conclusion, the CRAVE scale has good psychometric properties. These data also support tenets of the WANT model of motivation states for movement and rest (Stults-Kolehmainen et al., 2020a). Future studies need to explore how desires to move/rest relate to dynamic changes in physical activity and sedentarism. Copyright © 2021 Stults-Kolehmainen, Blacutt, Fogelman, Gilson, Stanforth, Divin, Bartholomew, Filgueiras, McKee, Ash, Ciccolo, Brotnow Decker, Williamson and Sinha.
Keywords: dept.psy; peer-reviewed

Defense against outside competition is linked to cooperation in male-male partnerships - Hellmann, Jennifer K.; Stiver, Kelly A.; Marsh-Rollo, Susan; Alonzo, Suzanne H. (Behavioral Ecology, 2020)
Male–male competition is a well-known driver of reproductive success and sexually selected traits in many species. However, in some species, males work together to court females or defend territories against male competitors. Dominant (nesting) males sire most offspring, but subordinate (satellite) males are better able to obtain fertilizations relative to unpartnered males. Because satellites only gain reproductive success by sneaking, there has been much interest in identifying the mechanisms enforcing satellite cooperation (defense) and reducing satellite sneaking. One such potential mechanism is outside competition: unpartnered satellites can destabilize established male partnerships and may force partnered satellites to restrain from cheating to prevent the dominant male from replacing them with an unpartnered satellite. Here, we manipulated perceived competition in the Mediterranean fish Symphodus ocellatus by presenting an “intruding” satellite male to established nesting and satellite male pairs. Focal satellite aggression to the intruder was higher when focal satellites were less cooperative, suggesting that satellites increase aggression to outside competitors when their social position is less stable. In contrast, nesting male aggression to the intruder satellite increased as spawning activity increased, suggesting that nesting males increase their defense toward outside competitors when their current relationship is productive. We found no evidence of altered spawning activity or nesting/satellite male interactions before and after the presentation. These results collectively suggest that response to outside competition is directly linked to behavioral dynamics between unrelated male partners and may be linked to conflict and cooperation in ways that are similar to group-living species.
Keywords: Satellites; Symphodus ocellatus; alternative reproductive tactics; biological market theory; cooperation; cooperative behavior; defense mechanism; dept.psy; interspecific competition; intraspecific interaction; outside options; peer-reviewed; satellite male; sneak

Big five, linguistic styles, and successful online learning - Abe, J. (Internet and Higher Education, 2020)
With the tremendous growth in online classes and programs at institutions of higher education, conflicting claims are increasingly being made on media and blog sites about the personality types that are compatible with this new learning format. The relations between the Five Factor Model of Personality (FFM) and linguistic styles with measures of academic performance in fully online asynchronous classes were examined. Consistent with findings based on research in face-to-face classes, Conscientiousness, Openness to Experience, and Analytic Thinking were associated with academic success. There was no support for the views propagated on the internet that extraversion, introversion, or anxiety hinder or foster online learning. The most robust predictor of academic performance throughout the semester, independent of the personality variables, was the number of words students contributed to the online discussions. These finding are interpreted within the Community of Inquiry framework (CoI; Garrison, 2003) and future lines of research are suggested. © 2020 Elsevier Inc.
Keywords: Academic performance; Community of Inquiry framework (CoI); Community of inquiry; E-learning; Education computing; Five Factor Model Of Personality (FFM); Five-factor model of personality; LIWC; Linguistic analysis; Linguistics; Online learning; dept.psy; peer-reviewed

N400 amplitude, latency, and variability reflect temporal integration of beat gesture and pitch accent during language processing. - Morett, Laura M; Landi, Nicole; Irwin, Julia; McPartland, James C (Brain Research, 2020)
This study examines how across-trial (average) and trial-by-trial (variability in) amplitude and latency of the N400 event-related potential (ERP) reflect temporal integration of pitch accent and beat gesture. Thirty native English speakers viewed videos of a talker producing sentences with beat gesture co-occurring with a pitch accented focus word (synchronous), beat gesture co-occurring with the onset of a subsequent non-focused word (asynchronous), or the absence of beat gesture (no beat). Across trials, increased amplitude and earlier latency were observed when beat gesture was temporally asynchronous with pitch accenting than when it was temporally synchronous with pitch accenting or absent. Moreover, temporal asynchrony of beat gesture relative to pitch accent increased trial-by-trial variability of N400 amplitude and latency and influenced the relationship between across-trial and trial-by-trial N400 latency. These results indicate that across-trial and trial-by-trial amplitude and latency of the N400 ERP reflect temporal integration of beat gesture and pitch accent during language comprehension, supporting extension of the integrated systems hypothesis of gesture-speech processing and neural noise theories to focus processing in typical adult populations. Copyright © 2020 Elsevier B.V. All rights reserved.
Keywords: Adolescent; Adult; Beat gesture; Brain; Electroencephalography; Evoked Potentials; Evoked response variability; Female; Humans; Language; Male; N400; Pitch Perception; Pitch accent; Speech; Speech Perception; Temporal integration; Young Adult; adolescent; adult; article; brain; comprehension; controlled study; dept.psy; electroencephalography; event related potential; evoked response; female; gesture; human; human experiment; language; language processing; male; noise; peer-reviewed; physiology; pitch; pitch perception; speech; speech perception; videorecording; young adult

Motivation States for Physical Activity and Sedentary Behavior: Desire, Urge, Wanting, and Craving. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Bartholomew, John B; Gilson, Todd A; Ash, Garrett I; McKee, Paul C; Sinha, Rajita (Frontiers in psychology, 2020)
To better explain daily fluctuations in physical activity and sedentary behavior, investigations of motivation are turning from social cognitive frameworks to those centered on affect, emotion and automaticity, such as the Affect and Health Behavior Framework (AHBF), Integrated Framework and Affective-Reflective Theory (ART). This shift has necessitated: (a) re-examination of older theories and their constructs, such as drives, needs and tensions and (b) an inspection of competing theories from other fields that also attempt to explain dynamic changes in health behaviors. The Dynamical Model of Desire, Elaborated Intrusion Theory and others commonly share with AHBF the idea that human behavior is driven strongly by desires and/or the similar concepts of wants, urges, and cravings. These affectively-charged motivation states (ACMS) change quickly and may better explain physical activity behavior from one moment to the next. Desires for movement predominantly derive from negative but also positive reinforcement. Data from clinical populations with movement dysfunction or psychiatric disorders provides further evidence of these drivers of movement. Those with Restless Legs Syndrome, akathisia, tic disorders and exercise dependence all report strong urges to move and relief when it is accomplished. Motor control research has identified centers of the brain responsible for wants and urges for muscular movement. Models elaborated herein differentiate between wants, desires, urges and cravings. The WANT model (Wants and Aversions for Neuromuscular Tasks) conceptualizes desires for movement and rest as varying by magnitude, approach or avoidance-orientation (wants versus aversions) and as occupying independent dimensions instead of opposite ends of the same axis. For instance, one hypothetically might be in a state of both high desire for movement and rest simultaneously. Variations in motivation states to move and rest may also be associated with various stress states, like freezing or fight and flight. The first validated instrument to measure feelings of desire/want for movement and rest, the CRAVE Scale (Cravings for Rest and Volitional Energy Expenditure) is already shedding light on the nature of these states. With these advances in theory, conceptual modeling and instrumentation, future investigations may explore the effects of desires and urges for movement and sedentary behavior in earnest. Copyright © 2020 Stults-Kolehmainen, Blacutt, Bartholomew, Gilson, Ash, McKee and Sinha.
Keywords: conceptual analysis; dept.psy; desire; exercise; motivation; motivation states; peer-reviewed; physical activity; sedentary activity; urge for movement

The predictive validity of the Five-Factor Model of personality with preschool age children: A nine year follow-up study☆ - Abe, Jo Ann A (Journal of Research in Personality, 2005)
This study examined whether maternal ratings of the Five-Factor Model (FFM) obtained when children were 3.5 years would show theoretically coherent patterns of relations with a variety of behavioral referents in the laboratory at 5 years as well as with maternal and self-ratings of psychological functioning in adolescence. As expected, Agreeableness and Conscientiousness were associated with measures of self-regulation at both ages as well as with an internal locus of control, but only Conscientiousness was associated with high academic performance. By contrast, Neuroticism was associated with measures of anxiety and Extraversion was associated with difficulty inhibiting behaviors at both ages. Openness to Experience was associated with sophisticated play behavior at 5 years and self-confidence in adolescence. Overall, this study yielded strong support for the predictive validity of the FFM with preschool age children and provided further evidence that there are striking continuities in personality from early childhood to adolescence. (c) 2004 Elsevier Inc. All rights reserved.
Keywords: dept.psy; peer-reviewed

Use of visual information in speech perception: evidence for a visual rate effect both with and without a McGurk effect. - Brancazio, Lawrence; Miller, Joanne L (Perception & psychophysics, 2005)
The McGurk effect, where an incongruent visual syllable influences identification of an auditory syllable, does not always occur, suggesting that perceivers sometimes fail to use relevant visual phonetic information. We tested whether another visual phonetic effect, which involves the influence of visual speaking rate on perceived voicing (Green & Miller, 1985), would occur in instances when the McGurk effect does not. In Experiment 1, we established this visual rate effect using auditory and visual stimuli matching in place of articulation, finding a shift in the voicing boundary along an auditory voice-onset-time continuum with fast versus slow visual speech tokens. In Experiment 2, we used auditory and visual stimuli differing in place of articulation and found a shift in the voicing boundary due to visual rate when the McGurk effect occurred and, more critically, when it did not. The latter finding indicates that phonetically relevant visual information is used in speech perception even when the McGurk effect does not occur, suggesting that the incidence of the McGurk effect underestimates the extent of audio-visual integration.
Keywords: *Speech Perception; *Visual Perception; Adolescent; Adult; Auditory Perception; Cues; Humans; Middle Aged; dept.psy

Effects of reinforcer probability, delay, and response requirements on the choices of rats and pigeons: Possible species differences - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2005)
In Experiment 1 with rats, a left lever press led to a 5-s delay and then a possible reinforcer. A right lever press led to an adjusting delay and then a certain reinforcer. This delay was adjusted over trials to estimate an indifference point, or a delay at which the two alternatives were chosen about equally often. Indifference points increased as the probability of reinforcement for the left lever decreased. In some conditions with a 20% chance of food, a light above the left lever was lit during the 5-s delay on all trials, but in other conditions, the light was only lit on those trials that ended with food. Unlike previous results with pigeons, the presence or absence of the delay light on no-food trials had no effect on the rats' indifference points. In other conditions, the rats showed less preference for the 20% alternative when the time between trials was longer. In Experiment 2 with rats, fixed-interval schedules were used instead of simple delays, and the presence or absence of the fixed-interval requirement on no-food trials had no effect on the indifference points. In Experiment 3 with rats and Experiment 4 with pigeons, the animals chose between a fixed-ratio 8 schedule that led to food on 33% of the trials and an adjusting-ratio schedule with food on 100% of the trials. Surprisingly, the rats showed less preference for the 33% alternative in conditions in which the ratio requirement was omitted on no-food trials. For the pigeons, the presence or absence of the ratio requirement on no-food trials had little effect. The results suggest that there may be differences between rats and pigeons in how they respond in choice situations involving delayed and probabilistic reinforcers.
Keywords: *Behavior, Animal/ph [Physiology]; *Choice Behavior; *Reaction Time; *Reinforcement, Psychology; Animals; Behavior, Animal; Choice; Choice Behavior; Columbidae; Delay; Fixed interval; Fixed ratio; Key peck; Lever press; Male; Pigeons; Probability; Rats; Rats, Sprague-Dawley; Reaction Time; Reinforcement (Psychology); Species Specificity; Sprague Dawley rat; animal; animal behavior; decision making; dept.psy; male; peer-reviewed; physiology; pigeons and doves; probability; rat; reaction time; reinforcement; review; species difference

Exploring a concurrent-chains paradox: decreasing preference as an initial link is shortened. - Mazur, James E (Journal of experimental psychology. Animal behavior processes, 2005)
Experiments with pigeons and rats on concurrent-chains schedules examined a paradoxical effect reported by R. A. Preston and E. Fantino (1991). One schedule in the concurrent chain had a variable-interval (VI) 60-s initial link, and its terminal link was a 10-s delay to food. The other schedule had an initial link that ranged from VI 60 s to VI 2 s, and its terminal link was a 20-s delay to food. The paradoxical effect--a decrease in preference for the 20-s delay as its initial link was shortened--was found in some conditions but not in others. An analysis of response-reinforcer delays suggested that the paradoxical effect occurred in conditions in which responding on the short VI schedule almost always led to the 20-s delay, eliminating the possibility of switching to the alternative with the shorter delay. Copyright 2005 APA.
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Association Learning; Choice Behavior; Color Perception; Columba; Columbidae; Discrimination Learning; Models, Psychological; Motivation; Psychomotor Performance; Reaction Time; Reinforcement Schedule; animal; article; color vision; decision making; dept.psy; discrimination learning; learning; motivation; pigeons and doves; psychological model; psychomotor performance; reaction time; reinforcement

From Freud to Erikson to Marcia: Concept maps in personality psychology courses - Anthis, K (Teaching of Psychology, 2005)
This study examined concept maps produced by personality psychology students as a function of different types of concept map instruction. The results indicated the number of quantitative items in the students' concept maps significantly increased from the pretest to the posttest, as would be expected over the course of an academic semester. More importantly, the type of instructions the students received at the pretest played a significant role in the number of cross links depicted in the maps at the posttest. I discuss the results in term of the utility of instruction type when using concept maps in social science courses.
Keywords: dept.psy; ⛔ No DOI found

Heuristics and general principles of learning. - Mazur, James E (Behavioural Processes, 2005)
This research on decision-making heuristics is similar to research on animal learning in at least two ways. First, optimality modeling has not proven to be very useful for either research area. Second, both of these research areas seek to find general principles (or heuristics) that are applicable to different species in different settings. However, the basic principles of classical and operant conditioning seem to be more uniform across species and situations, whereas decision-making heuristics can vary for different species and different situations, even for tasks with very similar characteristics.
Keywords: *Algorithms; *Decision Making; *Learning; *Models, Psychological; Animalia; Animals; Decision-making; Heuristics; Humans; Optimality modeling; behavioral research; conditioned reflex; conference paper; decision making; dept.psy; heuristics; human; instrumental conditioning; learning; mental task; nonhuman

Varying initial-link and terminal-link durations in concurrent-chains schedules: a comparison of three models. - Mazur, James E (Behavioural Processes, 2004)
In Experiment 1, pigeons responded on concurrent-chains schedules with equal variable-interval schedules as initial links and fixed delays to food as terminal links. One terminal-link delay was always three times as long as the other. As terminal-link delays increased, response percentages on the key with the shorter terminal link increased according to a curvilinear function. This result supported the predictions of the hyperbolic value-added model and the contextual-choice theory but not delay-reduction theory. In Experiment 2, the terminal links were always delays of 2 s and 12 s, followed by food, and the durations of the initial links varied across conditions. As initial-link durations increased, pigeons' response percentages on the key with the shorter terminal link decreased, but toward an asymptote greater than 50%, indicating a continued preference for the shorter terminal link with very long initial links. This result was more consistent with the predictions of the hyperbolic-value added model than with those of the contextual-choice model or of delay-reduction theory. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: *Behavior, Animal; *Reinforcement, Psychology; Animals; Behavior, Animal; Columba; Columbidae; Concurrent-chains schedule; Initial links; Key peck; Pigeons; Reinforcement (Psychology); Terminal links; Time Factors; animal experiment; behavioral response; bird; conference paper; controlled study; decision making; dept.psy; experiment; food; intermethod comparison; model; modeling; nonhuman; pigeon; prediction; reinforcement; response time; temporal analysis; theory

Self-esteem, perception of relationships, and emotional distress: A cross-cultural study - Abe, Jo Ann A (Personal Relationships, 2004)
This study examined the relative importance of self-esteem, family cohesion, and support from friends in predicting depressed mood and anxiety in Japanese and American college students. Contrary to expectations, self-esteem was the strongest predictor of emotional distress in both groups of students. Nevertheless, consistent with predictions derived from Markus and Kitayama's theory of self-construals, family cohesion accounted for a significantly larger percentage of the variance in predicting emotional distress in Japan than in the United States. In both countries, the relations between support from friends and the measures of emotional distress were entirely mediated by self-esteem. However, among Japanese students, family cohesion accounted for additional significant variance in predicting the measures of emotional distress, even after controlling for self-esteem.
Keywords: dept.psy

Lexical influences in audiovisual speech perception - Brancazio, Lawrence (Journal of Experimental Psychology: Human Perception and Performance, 2004)
Phoneme identification with audiovisually discrepant stimuli is influenced by information in the visual signal (the McGurk effect). Additionally, lexical status affects identification of auditorily presented phonemes. The present study tested for lexical influences on the McGurk effect. Participants identified phonemes in audiovisually discrepant stimuli in which lexical status of the auditory component and of a visually influenced percept was independently varied. Visually influenced (McGurk) responses were more frequent when they formed a word and when the auditory signal was a nonword (Experiment 1). Lexical effects were larger for slow than for fast responses (Experiment 2), as with auditory speech, and were replicated with stimuli matched on physical properties (Experiment 3). These results are consistent with models in which lexical processing of speech is modality independent.
Keywords: *Lipreading; *Speech Perception; *Visual Perception; *Vocabulary; Adolescent; Adult; Female; Humans; Lipreading; Male; Phonetics; Reaction Time; Speech Perception; Visual Perception; Vocabulary; adolescent; adult; article; clinical trial; controlled clinical trial; controlled study; dept.psy; female; human; linguistics; lip reading; male; phonetics; randomized controlled trial; reaction time; speech perception; vision

Shame, guilt, and personality judgment - Abe, Jo Ann A (Journal of Research in Personality, 2004)
The purpose of this study was to shed further light on the intrapersonal and interpersonal correlates of shame- and guilt-proneness by examining their relations with self- and peer-ratings of the five-factor model (FFM) of personality. Shame- and guilt-proneness were assessed using a scenario-based and a checklist measure. Consistent with findings from previous research, the self-rating data yielded support for the view that shame-proneness may be associated with more maladaptive patterns than guilt-proneness. However, peer-ratings of personality failed to corroborate these findings. Both scenario-based and checklist measures of shame-proneness were associated with a tendency to underestimate one's Agreeableness relative to peer-ratings. Several possible interpretations of these findings are discussed in light of the extant research on personality judgment. (C) 2003 Elsevier Science (USA). All rights reserved.
Keywords: dept.psy; peer-reviewed

Gender and identity status differences in late adolescents’ possible selves - Anthis, Kristine; Dunkel, Curt S; Anderson, Brian (Journal of Adolescence, 2004)
The current study examined gender and identity status differences in late adolescents' possible selves. The intent of the study was to clarify conflicts between theory and research on gender differences in identity by investigating the content of participants' possible selves. Participants completed measures of identity and possible selves. The results indicated that there was a relationship between gender and the mean number of both feared and balanced interpersonally themed possible selves. The pattern of results is discussed in terms of prior findings regarding gender differences in both identity and possible selves. Suggestions for future research are also provided. (C) 2003 The Association for Professionals in Services for Adolescents. Published by Elsevier Ltd. All rights reserved.
Keywords: *Sex Factors; *Social Identification; Adolescent; Adult; Female; Humans; Male; Surveys and Questionnaires; United States; adolescent; adult; article; child behavior; controlled study; coping behavior; dept.psy; ego identity; ethnology; fear; female; gender identity; human; male; personality; race difference; sex difference; social status

Developmental changes in facial expressions of emotions in the strange situation during the second year of life - Izard, Carroll E; Abe, Jo Ann A (Emotion, 2004)
Infants' expressions of discrete emotions were coded during the more stressful episodes (4 through 8) of the Strange Situation at 13 and 18 months. The data showed a significant decrease in full-face expressions (more complex configurations of movements) and a significant increase in component expressions (simpler and more constrained patterns of movements). The authors interpreted this trend as a developmental change toward more regulated and less intense emotions. Consistent with this view, the aggregate index of infants' full-face negative emotion expressions, interpreted as reflecting relatively unregulated intense emotions, correlated significantly with maternal ratings of difficult temperament. The authors discuss alternative interpretations of the findings in terms of changes in reactivity/arousability and the emerging capacity for self-regulation.
Keywords: Adult; Affect; Arousal; Facial Expression; Female; Humans; Infant; Social Control, Informal; Temperament; adult; anger; arousal; article; body movement; body posture; child behavior; child development; child parent relation; dept.psy; emotion; face; facial expression; happiness; human; infant; longitudinal study; mother child relation; rating scale; temperament

Therapist variables that predict symptom change in psychotherapy with chronically depressed outpatients. - Vocisano, Carina; Klein, Daniel N; Arnow, Bruce A; Rivera, Caridad; Blalock, Janice A; Rothbaum, Barbara O; Vivian, Dina; Markowitz, John C; Kocsis, James H; Manber, Rachel; Castonguay, Louis G; Rush, A John; et al. (Psychotherapy, 2004)
The present study examines the contribution of psychotherapist variables to change in depressive symptoms in a large clinical trial comparing the efficacy of the cognitive-behavioral analysis system of psychotherapy, the antidepressant nefazodone, and the combination of both in the treatment of chronic depression. Greater change on the Hamilton Rating Scale for Depression (HRSD) was associated with greater emphasis on the therapeutic relationship, lower overall psychotherapy caseload, therapist psychodynamic orientation, and supervisory status. There was no relationship between HRSD change and therapist sex, age, or years of experience.
Keywords: Hamilton scale; adult; age; article; behavior therapy; clinical practice; clinical trial; cognitive therapy; controlled clinical trial; controlled study; depression; dept.psy; doctor patient relation; drug efficacy; female; gender; human; major clinical study; male; multicenter study; nefazodone; normal human; outpatient; patient care; patient guidance; physician attitude; prediction; psychodynamics; psychopharmacotherapy; psychotherapist; psychotherapy; randomized controlled trial; symptomatology; workload

Visual influences on the internal structure of phonetic categories - Brancazio, L; Miller, JL; Pare, MA (Perception & Psychophysics, 2003)
Previous work has demonstrated that the graded internal structure of phonetic categories is sensitive to a variety of contextual factors. One such factor is place of articulation: The best exemplars of voiceless stop consonants along auditory bilabial and velar voice onset time (VOT) continua occur over different ranges of VOT! (Volaitis & Miller, 1992). In the present study, we exploited the McGurk effect to examine whether-visual information for place of articulation also shifts the best-exemplar range for voiceless consonants, following Green and Kuhl's (1989) demonstration of effects of visual place of articulation on the location of voicing boundaries. In Experiment 1, we established that /p/ and /t/ have different best-exemplar ranges along auditory bilabial and alveolar VOT continua. We then found, in Experiment 2, a-similar shift in the best-exemplar range for /t/ relative to that for /p/ when there was a change in visual place of articulation, with auditory place of articulation held constant. These findings indicate-that the perceptual mechanisms that determine internal phonetic category structure-are sensitive to visual, as well as to Auditory, information.
Keywords: Adolescent; Adult; Female; Humans; Male; Middle Aged; Phonetics; Random Allocation; Speech Perception; Time Factors; Visual Perception; Voice; adolescent; adult; article; dept.psy; female; human; male; middle aged; phonetics; randomization; speech perception; time; vision; voice

Effects of free-food deliveries and delays on choice under concurrent-chains schedules. - Mazur, James E (Behavioural Processes, 2003)
Pigeons responded on a concurrent-chains schedule with two equal variable-interval (VI) schedules as initial links and delays to food of 3 and 12 s as the two terminal links. In even-numbered sessions, no other reinforcement schedule was present, and all pigeons showed a strong preference for the response key that had the shorter, 3-s terminal-link delay. In odd-numbered sessions, the initial links were interrupted at random times by one of three different types of events. When the interruptions were immediate food deliveries, the response percentages increased on the key that had the 3-s delay. When the interruptions were 30-s delays followed by food, the response percentages remained approximately unchanged. When the interruptions were 30-s delays with no food, the response percentages decreased. The results were used to compare the predictions of different mathematical models of concurrent-chains performance. The results favored models that assume that preference is determined by the relative amount of advantage that is gained when a terminal link is entered. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Choice; Columba; Concurrent chains; Free food; Key peck; Pigeons; Reinforcer delay; animal behavior; animal experiment; article; controlled study; decision making; dept.psy; food; food deprivation; mathematical model; nonhuman; pigeon; prediction; preference behavior; reinforcement; stimulus response

The role of sexist discrimination in adult women's identity development - Anthis, Kristine (Sex Roles, 2002)
The purpose of the current study was to examine the relationship between sexist discrimination and identity development in a sample of adult women. Participants completed a scale to indicate the extent to which sexist events had occurred in their lives and a measure of identity at 2 different data collection periods that spanned approximately 5 months. The results indicated that sexist events reported to occur within the last year at the first data collection period significantly predicted identity scores at the second data collection period. These findings are discussed in terms of how sexist discrimination may play a role in adult women's identity development and in terms of the additional psychometric data that supports the validity of the measure of sexist discrimination.
Keywords: dept.psy; identity; sexist discrimination; women

Winning friends and influencing peers: Strategies of peer influence in late childhood - Hawley, Patricia H; Little, Todd D; Pasupathi, Monisha (International Journal of Behavioral Development, 2002)
We divided children (N = 719, grades 3-6) into five control types based on the degree to which they reported employing prosocial (indirect, cooperative) and coercive (direct, hostile) strategies of control (prosocial controllers, coercive controllers, bistrategic controllers, noncontrollers, and typicals). We tested for differences across the five types on personal characteristics, friendship motivations, wellbeing, and social integration, expecting specific patterns according to whether control is wielded, and whether coercive or prosocial behaviour (or both) is employed. Prosocial controllers revealed positive characteristics (e. g., social skills, agreeableness), intrinsic friendship motivations, and positive wellbeing. In contrast, coercive controllers revealed negative characteristics (e. g., hostility), extrinsic friendship motivations, and ill-being. Bistrategic controllers, as expected, reported the highest control, and revealed characteristics associated with both prosocial and coercive orientations. Noncontrollers, in contrast, did not report having these characteristics and felt the least effective in the peer group. Our evolutionary perspective offers unique predictions of how prosocial and coercive children are similar in terms of their instrumental goals and the consequences of using both strategies or neither.
Keywords: childhood; controlled study; cooperation; dept.psy; female; hostility; human; male; motivation; perception; personality test; persuasive communication; prediction; review; school child; social adaptation; social control; social interaction; sociology; wellbeing

Evidence against a constant-difference effect in concurrent-chains schedules - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2002)
Savastano and Fantino (1996) reported that in concurrent-chains schedules, initial-link choice proportions remained constant as terminal-link durations increased as long as the subtractive difference between the two terminal-link schedules remained constant. Two experiments with pigeons were conducted to examine this constant-difference effect. Both experiments used equal variable-interval schedules as initial links. The terminal links were fixed delays to reinforcement in Experiment 1 and variable delays to reinforcement in Experiment 2. The durations of the terminal links were varied across conditions, but the difference between pairs of terminal links was always 10 s. In both experiments, preference for the shorter terminal link became less extreme as terminal-link, durations increased, so a constant-difference effect was not found, It is argued, however, that this choice situation does not provide clear evidence for or against delay-reduction theory versus other theories of choice.
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Choice Behavior; Color Perception; Columbidae; Concurrent-chains schedules; Delay-reduction theory; Fixed delays; Key peck; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Variable delays; animal; appetite; article; color vision; comparative study; decision making; dept.psy; motivation; peer-reviewed; pigeons and doves; recall; reinforcement

Social dominance and prosocial and coercive strategies of resource control in preschoolers - Hawley, P.H. (International Journal of Behavioral Development, 2002)
This study was designed to investigate the predictors of social dominance, the strategies children use to control resources (prosocial and coercive), and the associations between these strategies and measures of personality, social skills, and peer regard. A total of 30 preschoolers (ages 3-6) were rated by their teachers on social dominance. Based on these ratings, dominant children were paired with multiple subordinate children (i.e., block design; Kenny, 1990) and observed in a play situation designed to elicit resource control behaviour. As hypothesised, age and the surgency facet of extraversion predicted social dominance (but openness to experience did not). Furthermore, also as expected, both prosocial behaviour and coercive behaviour were related to resource control in the play situation. Last, both resource control strategies were associated with parent-rated social competence, but only coercive control was associated with positive peer regard (i.e., Likeability). Factors of personality (e.g. agreeableness, hostility) were not associated with either of the strategies. The utility of an evolutionary perspective to resource control and social competence is discussed.
Keywords: article; controlled study; dept.psy; female; group psychology; hostility; human; hypothesis; male; parent; personality; persuasive communication; play; prediction; preschool child; social adaptation; social behavior; social dominance; sociology; teacher

Concurrent-chain performance in transition: effects of terminal-link duration and individual reinforcers. - Mazur, James E (Animal learning & behavior, 2002)
Pigeons responded on concurrent-chain schedules with variable-interval initial links and equal delays as terminal links. The terminal-link delays were 1 sec in some conditions and 20 sec in other conditions. The percentages of reinforcers delivered for responses on the left key were 10%, 30%, 70%, or 90%, and this percentage was switched every five to nine sessions. The rate of change in the pigeons' response percentages after a switch was the same whether the terminal-link delays were 1 sec or 20 sec. Analysis of the effects of individual reinforcers showed that after a response on one key had been reinforced, response percentages on that key were higher for at least the next 100 responses. Small effects of individual reinforcers were evident after eight or nine additional reinforcers had been delivered. The effects of individual reinforcers were about equally large during times of transition and during periods in which overall response percentages were relatively stable.
Keywords: *Behavior, Animal; *Reinforcement, Psychology; Animalia; Animals; Columba; Columbidae; Random Allocation; Reaction Time; Reinforcement Schedule; animal experiment; article; conditioned reflex; conditioning; decision making; dept.psy; nonhuman; pigeon; reinforcement; task performance

Transitional choice behavior in concurrent-chain schedules - Mazur, James E; Blake, Nancy; Mcmanus, Courtney (Behavioural Processes, 2001)
The choice responses of four pigeons were examined in 20 periods of transition in a concurrent-chain procedure with variable-interval schedules as initial links and fixed delays to reinforcement as terminal links. In some conditions, the delays to reinforcement were different for the two terminal links, and changes in preference were recorded after the delays for the two response keys were switched. In other conditions, the reinforcer delays were equal for the two keys, but which key delivered 80% of the reinforcers was periodically switched. Choice proportions changed more quickly after a switch in reinforcement percentages chan after a switch in the delays, thereby contradicting the hypothesis that faster changes would occur when the switch in conditions was easier to discriminate. Analyses of response sequences showed that the effects: of individual reinforcers were larger and lasted longer in conditions with changing reinforcement percentages than in conditions with changing terminal-link delays. Rates of change in choice behavior do not appear to be limited by the unpredictability of variable reinforcement schedules, because the changes in behavior were slow and gradual even when there was a large and sudden change in reinforcer delays. (C) 2001 Elsevier Science B.V. All rights: reserved.
Keywords: Columba; Concurrent-chain schedules; Transitional choice behavior; animal experiment; article; behavior; controlled study; decision making; dept.psy; instrumental conditioning; nonhuman; pigeon; reinforcement; stimulus response

Hyperbolic value addition and general models of animal choice - Mazur, James E. (Psychological Review, 2001)
Three mathematical models of choice-the contextual-choice model (R. Grace, 1994), delay-reduction theory (N. Squires & E. Fantino, 1971). and a new model called the hyperbolic value-added model-were compared in their ability to predict the results from a wide variety of experiments with animal subjects. When supplied with 2 or 3 free parameters, all 3 models made fairly accurate predictions for a large set of experiments that used concurrent-chain procedures. One advantage of the hyperbolic value-added model is that it is derived from a simpler model that makes accurate predictions for many experiments using discrete-trial adjusting-delay procedures. Some results favor the hyperbolic value-added model and delay-reduction theory over the contextual-choice model, but more data are needed from choice situations For which the models make distinctly different predictions.
Keywords: *Behavior, Animal; *Choice Behavior; *Models, Psychological; Animals; Behavior, Animal; Choice Behavior; Columbidae; Conditioning (Psychology); Conditioning, Psychological; Models, Psychological; Reinforcement (Psychology); Reinforcement Schedule; Reinforcement, Psychology; animal; animal behavior; comparative study; conditioning; decision making; dept.psy; pigeons and doves; psychological model; reinforcement; review; ⚠️ Invalid DOI

Two- versus three-alternative concurrent-chain schedules: a test of three models. - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 2000)
Two experiments with pigeons used concurrent-chain procedures with variable-interval schedules as initial links and different delays to food as terminal links. Two schedules were present in all sessions. but a 3rd schedule was alternately present and absent in successive sessions. When the 3rd schedule delivered food with no terminal-link delay, the presence of this schedule led to an increase in preference for the schedule with the shorter terminal link of the 2 unchanged schedules. When the terminal-link delay for the 3rd schedule was 30 s, the presence of this schedule led to a decrease in preference for the schedule with the shorter terminal link of the 2 unchanged schedules. These results are inconsistent with the predictions of R. Grace's (1994) contextual-choice model, but they are consistent with 2 other mathematical models-delay-reduction theory and the hyperbolic value-added model.
Keywords: *Choice Behavior; *Columbidae; *Conditioning, Operant; Analysis of Variance; Animals; Choice Behavior; Columbidae; Conditioning, Operant; Models, Psychological; analysis of variance; animal; article; decision making; dept.psy; instrumental conditioning; pigeons and doves; psychological model

Tradeoffs among delay, rate, and amount of reinforcement - Mazur, James E (Behavioural Processes, 2000)
In Experiment I, an adjusting-delay procedure was used to measure pigeons' choices between a single delayed reinforcer and a range of different variable-time schedules. Indifference points showed an inverse relation between rate of reinforcement and delay that was well described by a hyperbolic equation. An adjusting-amount procedure was used in Experiment 2, in which pigeons chose between an adjusting amount of food delivered after a 0.5-s delay and 3 s of food delivered after a range of different delays, and the effects of delay were similar to those found in Experiment 1. The results from both experiments indicated that, for pigeons, the strength of a reinforcer decreased rapidly with increasing delay. Estimates of a decay rate parameter in the hyperbolic equation were similar to those found in other studies with pigeons, but the rates of temporal discounting were three or four times faster than those found in studies with rats, suggesting a possible species difference. (C) 2000 Published by Elsevier Science B.V. All rights reserved.
Keywords: Adjusting procedure; Amount of reinforcement; Delay; Discounting; Key peck; Pigeons; Rate of reinforcement; animal experiment; article; behavior; controlled study; dept.psy; dose time effect relation; nonhuman; pigeon; reinforcement; technique; variance

Early and chronic stress and their relation to breast cancer - Jacobs, John R; Bovasso, Gregory B (Psychological Medicine, 2000)
Background. The study examined the role of parental death and chronic depression with severe episodes in affecting risk of breast cancer. This avenue of research is in accord with oncology findings, which suggests that causative factors of breast cancer occur and develop over a period of 20 years or longer. Methods. Participants consisted of 1213 women in the Baltimore Epidemiologic Catchment Area study surveyed in 1980 and followed through 1994-1995. They were assessed for depressive and anxious disorders, paternal death in childhood and relatively recent adverse life events prior to cancer hospitalization. Results. In the course of the study, 29 women were hospitalized for breast cancer and 10 died of breast cancer. The psychosocial variables that predicted increased risk of breast cancer were maternal death in childhood (OR = 2.56, P ¡ 0.001) and chronic depression with severe episodes (OR = 14.0, P ¡ 0.001). Neither relatively recent life events nor other depressive and anxiety disorders were associated with increased risk. Maternal death and chronic depression with severe episodes were reported to have occurred at least 20 years prior to breast cancer hospitalization. Conclusions. Maternal death and chronic and severe depression occurred at least 20 years prior to breast cancer hospitalization and could have been involved in the causation or facilitation of cancer development. The authors suggest that meta-analysis of other prospective studies are needed to create larger groups of individuals with these stresses to confidently establish these variables as risk factors.
Keywords: *Breast Neoplasms/et [Etiology]; *Death; *Depressive Disorder/co [Complications]; *Stress, Psychological; Adult; Breast Neoplasms; Breast Neoplasms/px [Psychology]; Death; Depressive Disorder; Epidemiologic Studies; Female; Humans; Life Change Events; Middle Aged; Mother-Child Relations; Risk Factors; Stress, Psychological; adult; anxiety neurosis; article; breast cancer; cancer risk; depression; dept.psy; female; health survey; hospitalization; human; life event; major clinical study; medical psychology; mental stress; parental deprivation

Visual influences on perception of speech and nonspeech vocal-tract events. - Brancazio, Lawrence; Best, Catherine T; Fowler, Carol A (Language and speech, 2006)
We report four experiments designed to determine whether visual information affects judgments of acoustically-specified nonspeech events as well as speech events (the "McGurk effect"). Previous findings have shown only weak McGurk effects for nonspeech stimuli, whereas strong effects are found for consonants. We used click sounds that serve as consonants in some African languages, but that are perceived as nonspeech by American English listeners. We found a significant McGurk effect for clicks presented in isolation that was much smaller than that found for stop-consonant-vowel syllables. In subsequent experiments, we found strong McGurk effects, comparable to those found for English syllables, for click-vowel syllables, and weak effects, comparable to those found for isolated clicks, for excised release bursts of stop consonants presented in isolation. We interpret these findings as evidence that the potential contributions of speech-specific processes on the McGurk effect are limited, and discuss the results in relation to current explanations for the McGurk effect.
Keywords: *Illusions; *Speech Perception/ph [Physiology]; *Visual Perception/ph [Physiology]; Acoustic Stimulation; Attention; Audiovisual speech perception; Clicks; Humans; McGurk effect; Nonspeech; Perceptual Masking; Psychoacoustics; Speech Acoustics; dept.psy

Words that predict outstanding performance - Abe, Jo Ann A. (Journal of Research in Personality, 2009)
This study applied word count strategies developed by expressive writing researchers to examine whether the words students use to describe and reflect on their field practicum experiences would predict practicum supervisors' ratings of their performance. The weekly journals of 66 students who completed a practicum at a mental health or school setting were analyzed using a computerized text-analysis program. As expected, positive emotion words and "insight" words were positively correlated with almost all dimensions of evaluation, with the exception of organizational ability, and "we" words were associated with dimensions that focused on interpersonal relations. These findings further support the view that positive emotion words and "insight" words are powerful markers of cognitive broadening and behavioral flexibility and that "we" words index feelings of affiliation and belonging. As one might expect, there was an increase in "we" words and a decrease in "anxiety" words over the course of the internship. © 2009 Elsevier Inc. All rights reserved.
Keywords: Experiential learning; Positive emotions; Reflection; Text-analysis; dept.psy; peer-reviewed

Delay-amount tradeoffs in choices by pigeons and rats: hyperbolic versus exponential discounting. - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2009)
An adjusting-delay procedure was used to study the choices of pigeons and rats when both delay and amount of reinforcement were varied. In different conditions, the choice alternatives included one versus two reinforcers, one versus three reinforcers, and three versus two reinforcers. The delay to one alternative (the standard alternative) was kept constant in a condition, and the delay to the other (the adjusting alternative) was increased or decreased many times a session so as to estimate an indifference point--a delay at which the two alternatives were chosen about equally often. Indifference functions were constructed by plotting the adjusting delay as a function of the standard delay for each pair of reinforcer amounts. The experiments were designed to test the prediction of a hyperbolic decay equation that the slopes of the indifference functions should increase as the ratio of the two reinforcer amounts increased. Consistent with the hyperbolic equation, the slopes of the indifference functions depended on the ratios of the two reinforcer amounts for both pigeons and rats. These results were not compatible with an exponential decay equation, which predicts slopes of 1 regardless of the reinforcer amounts. Combined with other data, these findings provide further evidence that delay discounting is well described by a hyperbolic equation for both species, but not by an exponential equation. Quantitative differences in the y-intercepts of the indifference functions from the two species suggested that the rate at which reinforcer strength decreases with increasing delay may be four or five times slower for rats than for pigeons.
Keywords: *Choice Behavior; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning, Operant; Long Evans rat; Male; Models, Psychological; Rats; Rats, Long-Evans; Reinforcement Schedule; Reward; animal; article; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; pigeons and doves; psychological model; rat; reinforcement; reward

Re-examining the long-term effects of experiencing parental death in childhood on adult psychopathology. - Jacobs, John R; Bovasso, Gregory B (Journal of Nervous and Mental Disease, 2009)
This study examined whether the experience of the death of a parent in childhood increases risk for adult psychopathology. Participants consisted of 3481 men and women gathered through the Baltimore Epidemiologic Catchment Area study in 1981 and followed through 1994-1995. The Diagnostic Interview Survey was administered by trained interviewers and was used to assess DSM-III disorders including major depression, panic, and anxiety disorders. Maternal death was not a predictor of adult psychopathology. The death of the father during childhood more than doubled the risk for major depressive disorder in adulthood. This study did not find any significant interactions between gender of the deceased parent and gender of the participant nor did the current age of the participant or their age at the time of the death of a parent affect risk for adult psychopathology. The long-term effect on adult depression of the experience of the death of the father in childhood is attributed to likely financial stresses, which may have continued for years and possibly into early adulthood, complicating the family's adaptation to the initial loss.
Keywords: *Bereavement; *Death; *Mental Disorders/et [Etiology]; *Mental Disorders/px [Psychology]; *Parents; *Psychology, Child; Anxiety Disorders; Anxiety Disorders/di [Diagnosis]; Anxiety Disorders/et [Etiology]; Anxiety Disorders/px [Psychology]; Bereavement; Child Psychology; Death; Depression; Depressive Disorder, Major; Depressive Disorder, Major/di [Diagnosis]; Depressive Disorder, Major/ep [Epidemiology]; Depressive Disorder, Major/et [Etiology]; Depressive Disorder, Major/px [Psychology]; Diagnostic and Statistical Manual of Mental Disorders; Economics; Fathers; Female; Humans; Incidence; Male; Mental Disorders; Middle Aged; Mothers; Panic; Parental death; Parents; Prevalence; Risk Factors; Stress, Psychological; Stress, Psychological/et [Etiology]; Time Factors; adaptive behavior; adult; adulthood; anxiety disorder; article; bereavement; child psychology; childhood; death; depression; dept.psy; diagnostic and statistical manual of mental disorders; economics; family stress; father; female; gender; human; incidence; interview; major depression; male; maternal mortality; mental disease; mental stress; middle aged; mother; normal human; panic; parent; parental deprivation; personal experience; prevalence; psychological aspect; risk factor; time; time of death

Training in assessment criteria indicative of deception to improve credibility judgments - Colwell, Kevin; Hiscock-Anisman, Cheryl; Memon, Amina; Colwell, Lori H.; Taylor, Laura; Woods, Debra (Journal of Forensic Psychology Practice, 2009)
The recent attention given to false confessions and convictions underscores the need for a valid and applicable system of credibility assessment. The current study demonstrates the effectiveness of assessment criteria indicative of deception (ACID) training in increasing rater's ability to discriminate between honest and deceptive transcripts. ACID generates credibility assessment through analysis of behaviors related to memory and impression-management as they occur during the course of an investigative interview. Raters were taught that honest responses are longer, more vivid, and more spontaneous than deceptive responses. Conversely, deceptive responses are shorter, less vivid, more rigid, more carefully phrased, and less likely to change during the course of an investigative interview. Trained raters were able to correctly identify 77% of transcripts as honest or deceptive, whereas untrained raters correctly identified 57%. Future research should focus on using the ACID technique in more realistic situations and should involve training of professional investigators.
Keywords: Credibility; Detecting deception; Investigative interviewing; accuracy; analytic method; article; assessment criteria indicative of deception; behavioral research; controlled study; criminal justice; decision making; dept.psy; honesty; human; interview; self evaluation; training

Does choice of college textbook make a difference in students' comprehension? - Durwin, Cheryl Cisero; Sherman, William M (College Teaching, 2008)
The authors investigate whether the choice of college textbook affects students' comprehension of the material. Forty-eight students from educational psychology courses were randomly assigned to one of two conditions: (1) unfamiliar passages drawn from the textbook used in the course, or (2) comparable passages selected from a competitor textbook. Students read three passages and completed comprehension tests and an opinion survey. No significant differences were found. Implications for textbook selection practices are presented in the discussion section. © 2008, Copyright Taylor & Francis Group, LLC.
Keywords: comprehension; dept.psy; student preferences; textbook selection

Effects of reinforcer delay and variability in a successive-encounters procedure. - Mazur, James E (Learning & behavior, 2008)
Pigeons responded in a successive-encounters procedure that consisted of a search period, a choice period, and a handling period. The search period was either a fixed-interval or a mixed-interval schedule presented on the center key of a three-key chamber. Upon completion of the search period, the center key was turned off and the two side keys were lit. A pigeon could either accept a delay followed by food (by pecking the right key) or reject this option and return to the search period (by pecking the left key). During the choice period, a red right key represented the long alternative (a long handling delay followed by food), and a green right key represented the short alternative (a short handling delay followed by food). The experiment consisted of a series of comparisons for which optimal diet theory predicted no changes in preference for the long alternative (because the overall rates of reinforcement were unchanged), whereas the hyperbolic-decay model predicted changes in preference (because the delays to the next possible reinforcer were varied). In all comparisons, the results supported the predictions of the hyperbolic-decay model, which states that the value of a reinforcer is inversely related to the delay between a choice response and reinforcer delivery.
Keywords: *Choice Behavior; *Reinforcement, Psychology; Animals; Behavior, Animal; Choice Behavior; Columbidae; Male; Reinforcement (Psychology); Time Factors; animal; animal behavior; animal experiment; article; conditioning; controlled study; decision making; dept.psy; food; male; nonhuman; pigeon; pigeons and doves; psychological theory; reinforcement; time

Rats’ choices between one and two delayed reinforcers - Mazur, James E (Learning & Behavior, 2007)
Rats chose between alternatives that differed in the number of reinforcers and in the delay to each reinforcer. A left leverpress led to two reinforcers, each delivered after a fixed delay. A right leverpress led to one reinforcer after an adjusting delay. The adjusting delay was increased or decreased many times in a session, depending on the rat's choices, in order to estimate an indifference point-a delay at which the two alternatives were chosen about equally often. Both the number of reinforcers and their individual delays affected the indifference points. The overall pattern of results was well described by the hyperbolic-decay model, which states that each additional reinforcer delivered by an alternative increases preference for that alternative but that a reinforcer's effect is inversely related to its delay. Two other possible delay-discounting equations, an exponential equation and a reciprocal equation, did not produce satisfactory predictions for these data. Adding an additional free parameter to the hyperbolic equation as an exponent for delay did not appreciably improve the predictions, suggesting that raising delay to some power other than 1.0 was unnecessary. The results were qualitatively similar to those from a previous experiment with pigeons (Mazur, 1986), but quantitative differences suggested that the rates of delay discounting were several times slower for rats than for pigeons.
Keywords: *Choice Behavior; *Conditioning, Operant; *Motivation; *Reinforcement Schedule; *Time Perception; Animals; Male; Models, Theoretical; Rats; Rats, Sprague-Dawley; animal behavior; animal experiment; article; conditioning; dept.psy; hyperbolic decay model; mathematical model; nonhuman; pigeon; predictive validity; rat; reinforcement

Species differences between rats and pigeons in choices with probabilistic and delayed reinforcers - Mazur, James E. (Behavioural Processes, 2007)
An adjusting-delay procedure was used to study rats' choices with probabilistic and delayed reinforcers, and to compare them with previous results from pigeons. A left lever press led to a 5-s delay signaled by a light and a tone, followed by a food pellet on 50% of the trials. A right lever press led to an adjusting delay signaled by a light followed by a food pellet on 100% of the trials. In some conditions, the light and tone for the probabilistic reinforcer were present only on trials that delivered food. In other conditions, the light and tone were present on all trials that the left lever was chosen. Similar studies with pigeons [Mazur, J.E., 1989. Theories of probabilistic reinforcement. J. Exp. Anal. Behav. 51, 87-99; Mazur, J.E., 1991. Conditioned reinforcement and choice with delayed and uncertain primary reinforcers. J. Exp. Anal. Behav. 63, 139-150] found that choice of the probabilistic reinforcer increased dramatically when the delay-interval stimuli were omitted on no-food trials, but this study found no such effect with the rats. In other conditions, the probability of food was varied, and comparisons to previous studies with pigeons indicated that rats showed greater sensitivity to decreasing reinforcer probabilities. The results support the hypothesis that rats' choices in these situations depend on the total time between a choice response and a reinforcer, whereas pigeons' choices are strongly influenced by the presence of delay-interval stimuli. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: *Association Learning/ph [Physiology]; *Choice Behavior/ph [Physiology]; *Probability Learning; *Reinforcement, Psychology; *Time Perception/ph [Physiology]; Animals; Columba; Columbidae; Delay-interval stimuli; Delayed reinforcers; Probabilistic reinforcers; Rats; Rats, Sprague-Dawley; Rattus; Species Specificity; Time Factors; animal experiment; article; behavioral response; controlled study; decision making; dept.psy; food; food intake; gamebird; nonhuman; probability; rat; reinforcement; rodent; species difference; stimulus

Choice in a successive-encounters procedure and hyperbolic decay of reinforcement. - Mazur, James E (Journal of the experimental analysis of behavior, 2007)
Pigeons responded in a successive-encounters procedure that consisted of a search state, a choice state, and a handling state. The search state was either a fixed-interval or mixed-interval schedule presented on the center key of a three-key chamber. Upon completion of the search state, the choice state was presented, in which the center key was off and the two side keys were lit. A pigeon could either accept a delay followed by food (by pecking the right key) or reject this option and return to the search state (by pecking the left key). During the choice state, a red right key represented the long alternative (a long handling delay followed by food), and a green right key represented the short alternative (a short handling delay followed by food). In some conditions, both the short and long alternatives were fixed-time schedules, and in other conditions both were mixed-time schedules. Contrary to the predictions of both optimal foraging theory and delay-reduction theory, the percentage of trials on which pigeons accepted the long alternative depended on whether the search and handling schedules were fixed or mixed. They were more likely to accept the long alternative when the search states were fixed-interval rather than mixed-interval schedules, and more likely to reject the long alternative when the handling states were fixed-time rather than mixed-time schedules. This pattern of results was in qualitative agreement with the predictions of the hyperbolic-decay model, which states that the value of a reinforcer is inversely related to the delay between a choice response and reinforcer delivery.
Keywords: *Choice Behavior; *Reinforcement, Psychology; Animals; Choice; Choice Behavior; Columbidae; Delay-reduction theory; Hyperbolic-decay model; Key peck; Male; Optimal foraging theory; Pigeons; Reinforcement (Psychology); Successive-encounters procedure; animal; article; decision making; dept.psy; male; peer-reviewed; pigeons and doves; reinforcement

Mathematical models and the experimental analysis of behaviour - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2006)
The rise of mathematical models in the experimental analysis of behavior has increased over the years, and they offer several advantages. Mathematical models require theorists to be precise and unambiguous, often allowing comparisons of competing theories that sound similar when stated in words. Sometimes different mathematical models may make equally accurate predictions for a large body of data. In Such cases, it is important to find and investigate situations for which the competing models make different predictions because, unless two models are actually mathematically equivalent, they are based on different assumptions about the psychological processes that underlie ail observed behavior. Mathematical models developed in basic behavioral research have been used to predict and control behavior in applied settings, and they have guided research in other areas of psychology. A good mathematical model call provide a common framework for understanding what might otherwise appear to be diverse and unrelated behavioral phenomena. Because psychologists vary in their quantitative skills and in their tolerance for mathematical equations, it is important for those who develop mathematical models of behavior to find ways (such as verbal analogies, pictorial representations, or concrete examples) to communicate the key premises of their models to nonspecialists.
Keywords: *Models, Theoretical; *Social Behavior; Behavior; Equations; Humans; Mathematical models; Models, Theoretical; Reinforcement; Reinforcement (Psychology); Reinforcement, Psychology; Social Behavior; article; dept.psy; human; peer-reviewed; reinforcement; social behavior; theoretical model

Directed forgetting of a single item - Gottlob, Lawrence R; Golding, Jonathan M; Hauselt, William J (Journal of General Psychology, 2006)
In two experiments, we investigated directed forgetting of a single item. We presented participants with two phone numbers to remember and instructed half of the participants to forget the first phone number. The first number was either learned on a single trial (Experiment 1) or on three trials (Experiment 2). In Experiment 1, there was evidence of directed forgetting as a result of differential encoding; the forget instruction affected recall and recognition for both phone numbers. In Experiment 2, the evidence favored differential rehearsal because the forget instruction affected recall but not recognition. These results indicate that instructions to forget can affect memory of single items.
Keywords: Cues; Directed forgetting; Forgetting; Humans; Intentional forgetting; Memory; Mental Recall; Recall; Recognition (Psychology); Retention (Psychology); article; association; dept.psy; human; long term memory; recall; recognition

Readiness to change: A longitudinal study of changes in adult identity - Anthis, Kristine; Lavoie, Joseph C (Journal of Research in Personality, 2006)
It has been suggested in the identity literature that a readiness to change may play a role in identity development beyond adolescence, but an empirical investigation of this relationship had yet to be conducted until now. Therefore, the purpose of the current study was to establish a longitudinal relationship between readiness to change and adult identity development. Participants completed measures of readiness to change and identity at both the beginning and the end of the study. The results revealed a relationship between readiness to change and changes in identity exploration over the study interval, and between readiness to change and changes in identity commitment. The findings are discussed in terms of the currently available literature on identity development in adulthood. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Adults; Development; Identity; Stages of change; dept.psy; peer-reviewed

Does reflective journal writing improve course performance - Cisero, Cheryl A (College Teaching, 2006)
Abstract. This study investigated whether a reflective journal writing assignment would improve students' course performance. A total of 166 students from undergraduate sections of a course taught by the same instructor over three semesters completed the assignment as part of their requirements. Students (N = 317) from five previous semesters of the same course taught by the same instructor, who were not required to complete the assignment, served as a comparison group. Intervention and comparison groups were comparable on a variety of variables including all assignments, excepting the journal assignment. The findings are interpreted within the context of factors such as students' study habits and motivation. © 2006, Copyright Taylor & Francis Group, LLC.
Keywords: course performance; dept.psy; journal writing; motivation

Choice between single and multiple reinforcers in concurrent-chains schedules. - Mazur, James E (Journal of the experimental analysis of behavior, 2006)
Pigeons responded on concurrent-chains schedules with equal variable-interval schedules as initial links. One terminal link delivered a single reinforcer after a fixed delay, and the other terminal link delivered either three or five reinforcers, each preceded by a fixed delay. Some conditions included a postreinforcer delay after the single reinforcer to equate the total durations of the two terminal links, but other conditions did not include such a postreinforcer delay. With short initial links, preference for the single-reinforcer alternative decreased when a postreinforcer delay was present, but with long initial links, the postreinforcer delays had no significant effect on preference. In conditions with a postreinforcer delay, preference for the single-reinforcer alternative frequently switched from above 50% to below 50% as the initial links were lengthened. This pattern of results was consistent with delay-reduction theory (Squires & Fantino, 1971), but not with the contextual-choice model (Grace, 1994) or the hyperbolic value-added model (Mazur, 2001) as they have usually been applied. However, the hyperbolic value-added model could account for the results if its calculations were expanded to include reinforcers delivered in later terminal links. The implications of these findings for models of concurrent-chains performance are discussed.
Keywords: *Appetitive Behavior; *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Association Learning; Choice Behavior; Columbidae; Concurrent chains; Contextual-choice model; Delay-reduction theory; Discrimination Learning; Hyperbolic value-added model; Key peck; Motivation; Multiple reinforcers; Pigeons; Psychomotor Performance; Reinforcement Schedule; animal; appetite; article; decision making; dept.psy; discrimination learning; learning; motivation; peer-reviewed; pigeons and doves; psychomotor performance; reinforcement

Impact of enriched environment during adolescence on adult social behavior, hippocampal synaptic density and dopamine D2 receptor expression in rats - Gabriel, Paul; Mastracchio, Toni-Ann; Bordner, Kelly; Jeffrey, Rachel (Physiology & Behavior, 2020)
Environmental enrichment (EE) is one experimental manipulation that induces changes in the brain. However, it is important to distinguish between physical and social components of enrichment. To this end we established four groups of rats reared in different enriched environments during the adolescent period. Our results indicate heightened social memory and increased spine density in dentate gyrus specifically in socially enriched animals. Physical enrichment increased spine density in CA1. Dopamine D2 receptor expression in hippocampus was decreased across all enrichment conditions. Altogether, our results demonstrate differing effects of physical and social enrichment, supporting an important role for environment in synaptogenesis, behavior, and dopaminergic signaling. © 2020 The Authors
Keywords: Adolescence; Animals; Article; Dopamine; Environment; Environmental enrichment; Hippocampus; Memory; Rats; Receptors, Dopamine D2; Social Behavior; Social enrichment; Synapse density; animal; animal behavior; animal experiment; controlled study; dentate gyrus; dept.bio; dept.psy; dopamine 2 receptor; dopaminergic transmission; environment; environmental enrichment; female; hippocampal CA1 region; hippocampus; male; memory; nonhuman; peer-reviewed; priority journal; protein expression; rat; social behavior; spine; synapse; synaptogenesis

A preliminary investigation into collegiate student-athletes’ attitudes towards athletic trainers and sport psychology consultants - Ildefonso, Kenneth; Blanton, Jedediah; Durwin, Cheryl; Arvinen-Barrow, Monna; Kamphoff, Cindra (Journal of Sport, 2020)
To investigate if athletes’ attitudes toward athletic trainers and sport psychology consultants differ considering nature of athletic ability beliefs and previous experiences with these professionals; collegiate student-athletes (n = 114 male, n = 81 female, M age = 19.77, SD = 1.43) completed the Conceptions of the Nature of Athletic Ability Questionnaire-2 (Biddle, Wang, Chatzisarantis, & Spray, 2003), Attitudes Toward Athletic Trainers-Form (modified from the Attitudes toward Physiotherapist-Form; Arvinen-Barrow, Clement, & Bayes, 2012), and the Sport Psychology Attitudes Revised-Form (Martin, Kellman, Lavallee, & Page, 2002). Multiple analyses of variance revealed small statistically significant mean differences in attitudes considering ability beliefs, previous athletic training, and sport psychology experiences. Athletes with previous athletic training experience were less confident in their athletic trainer than those without such experience. In contrast, athletes with previous sport psychology experience were more confident in their consultant than those without such experiences. Results suggest athletes’ attitudes towards helping professionals may be partially influenced by subjective norms and expectations about the nature of such relationships.
Keywords: dept.psy; peer-reviewed

Integrating DSM-IV factors to predict violence in high-risk psychiatric patients - Lynch, Donna M.; Noel, Helen C. (Journal of Forensic Sciences, 2010)
This study incorporated Axis-II and Axis-IV factors in DSM-IV to test the relationship between predicted risk for violence assessed in the psychiatric emergency room and actual violence during hospitalization. Psychiatric nurses lack an objective instrument to use during the acute psychiatric assessment. The retrospective study comprised consecutive psychiatric admissions (n = 161) in one tertiary veterans' hospital. Statistical testing for the predictive power of risk factors, relationships between variables, and violent events included nonparametric tests, factor analysis, and logistic regression. Of the 32 patients who committed violence during hospitalization, 12 had committed violence in the psychiatric emergency room. Statistical significance was shown for violent incidents and dementia, court-ordered admission, mood disorder, and for three or more risk factors. The 13-item Risk of Violence Assessment (ROVA) scale suggests validity and sensitivity for rating DSM-IV factors and psychosocial stressors to predict risk for violence during hospitalization. Replication studies are recommended to strengthen validity of the ROVA scale.
Keywords: Adult; Aged; Aged, 80 and over; Aggression; Assault; Assessment; Commitment of Mentally Ill; Dementia; Diagnostic and Statistical Manual of Mental Disorders; Diagnostic and statistical manual of mental disorders (DSM-IV); Emergency Services, Psychiatric; Female; Forensic Psychiatry; Forensic science; Hospitals, Veterans; Humans; Instrument; Male; Mental Disorders; Middle Aged; New England; Psychiatric; Psychiatric Status Rating Scales; Reproducibility of Results; Retrospective Studies; Risk Assessment; Risk factors; Self-harm; Suicidal; United States; Violence; adult; aged; article; dementia; dept.psy; diagnostic and statistical manual of mental disorders; emergency health service; female; forensic psychiatry; human; male; mental disease; middle aged; psychological aspect; psychological rating scale; public hospital; reproducibility; retrospective study; risk assessment; violence

The role of conflict in continuity and change: life events associated with identity development in racially and ethnically diverse women - Anthis, Kristine (Identity, 2011)
In this archival study, life events were identified that served as precursors to identity transitions in 149 European American, African American, Mexican American, and Puerto Rican women. The data were collected during a period from the late 1970s to the early 1980s in the United States. Participants were interviewed and asked to describe events that had influenced their understanding of themselves. Events were coded into relational, career, education, personal, health-related, and miscellaneous categories. Results indicated that women were more likely to report life events regarding their relationships than events in other categories. A reexamination of the data revealed that that there were more similarities than differences among the racial and ethnic groups in terms of the life events described. Respondents were more likely to report continuity than change in their identities in response to life events serving as possible precursors to change. Results also revealed that when change did occur, it was associated with high levels of conflict particularly for the domains of relationships and educational achievement expectations. © 2011 Copyright Taylor and Francis Group, LLC.
Keywords: dept.psy

Mindfulness and modification therapy for behavioral dysregulation: results from a pilot study targeting alcohol use and aggression in women - Wupperman, Peggilee; Marlatt, G. Alan; Cunningham, Amy; Bowen, Sarah; Berking, Matthias; Mulvihill-Rivera, Nicole; Easton, Caroline (Journal of Clinical Psychology, 2012)
Objectives: Increasing evidence suggests that deficits in mindfulness (awareness, attentiveness, and acceptance of the present moment) play a role in a range of disorders involving behavioral dysregulation. This paper adds to that literature by describing a transdiagnostic psychotherapy (Mindfulness & Modification Therapy; MMT) developed to target behavioral dysregulation. Design: An open-treatment pilot-trial investigated the feasibility, acceptability, and pre-post effects of MMT targeting women (N = 14) court-referred for alcohol abuse/dependence and aggression. Results: Pre-post comparisons revealed significant decreases in alcohol use, drug use, and aggression. In addition, the retention rate was 93%. Conclusion: Preliminary evidence suggests that MMT is a feasible and acceptable treatment that decreases dysregulated behaviors such as substance use and aggression, while also potentially increasing retention. (c) 2011 Wiley Periodicals, Inc. J Clin Psychol 67:117, 2011.
Keywords: Adult; Aggression; Alcoholism; Anger; Attention; Awareness; Behavior dysregulation; Cognitive Therapy; Domestic Violence; Emotion regulation; Emotions; Female; Humans; Intervention; Middle Aged; Mindfulness; Pilot Projects; Substance; Transdiagnostic; Treatment Outcome; Young Adult; adult; aggression; alcoholism; article; attention; awareness; cognitive therapy; dept.psy; domestic violence; emotion; female; human; legal aspect; methodology; middle aged; physiology; pilot study; psychological aspect; treatment outcome

Neuroendocrine profiles associated with discrete behavioural variation in Symphodus ocellatus, a species with male alternative reproductive tactics. - Nugent, Bridget M.; Stiver, Kelly A.; Alonzo, Suzanne H.; Hofmann, Hans A. (Molecular Ecology, 2016)
The molecular mechanisms underlying phenotypic plasticity are not well understood. Identifying mechanisms underlying alternative reproductive tactics (ARTs) in species for which the behavioural and fitness consequences of this variation are well characterized provides an opportunity to integrate evolutionary and mechanistic understanding of the maintenance of variation within populations. In the ocellated wrasse Symphodus ocellatus, the behavioural phenotypes of three distinct male morphs (sneakers, satellites and nesting males), which arise from a single genome, have been thoroughly characterized. To determine the neuroendocrine and genomic mechanisms associated with discrete phenotypic variation and ARTs in S. ocellatus in their natural environment, we constructed a whole-brain de novo transcriptome and compared global patterns of gene expression between sexes and male morphs. Next, we quantified circulating cortisol and 11-ketotestosterone (11-kt), mediators of male reproductive behaviours, as well as stress and gonadal steroid hormone receptor expression in the preoptic area, ventral subpallial division of the telencephalon and dorsolateral telencephalon, critical brain regions for social and reproductive behaviours. We found higher levels of 11-kt in nesting males and higher levels of cortisol in sneaker males relative to other male morphs and females. We also identified distinct patterns of brain region-specific hormone receptor expression between males such that most hormone receptors are more highly expressed in satellites and nesting males relative to sneakers and females. Our results establish the neuroendocrine and molecular mechanisms that underlie ARTs in the wild and provide a foundation for experimentally testing hypotheses about the relationship between neuromolecular processes and reproductive success. Copyright © 2016 John Wiley & Sons Ltd.
Keywords: *Neurosecretory Systems/ph [Physiology]; *Perciformes/ph [Physiology]; *Reproduction; *Sexual Behavior, Animal; 11-ketotestosterone; Animals; Brain; Brain/me [Metabolism]; Female; Hydrocortisone; Hydrocortisone/bl [Blood]; Male; Nesting Behavior; Neurosecretory Systems; Perciformes; Perciformes/ge [Genetics]; Phenotype; Reproduction; Sexual Behavior, Animal; Testosterone; Testosterone/aa [Analogs & Derivatives]; Testosterone/bl [Blood]; Transcriptome; alternative reproductive tactics; analogs and derivatives; animal; blood; brain; dept.psy; female; gene expression; genetics; hormones; hydrocortisone; male; metabolism; nesting; neurosecretion; peer-reviewed; phenotype; physiology; reproduction; sexual behavior; testosterone; transcriptome

Ocean acidification affects fish spawning but not paternity at CO2 seeps - Milazzo, Marco; Cattano, Carlo; Alonzo, Suzanne H; Foggo, Andrew; Gristina, Michele; Rodolfo-Metalpa, Riccardo; Sinopoli, Mauro; Spatafora, Davide; Stiver, Kelly A; Hall-Spencer, Jason M (Proceedings of the Royal Society B: Biological Sciences, 2016)
Fish exhibit impaired sensory function and altered behaviour at levels of ocean acidification expected to occur owing to anthropogenic carbon dioxide emissions during this century. We provide the first evidence of the effects of ocean acidification on reproductive behaviour of fish in the wild. Satellite and sneaker male ocellated wrasse (Symphodus ocellatus) compete to fertilize eggs guarded by dominant nesting males. Key mating behaviours such as dominant male courtship and nest defence did not differ between sites with ambient versus elevated CO2 concentrations. Dominant males did, however, experience significantly lower rates of pair spawning at elevated CO2 levels. Despite the higher risk of sperm competition found at elevated CO2, we also found a trend of lower satellite and sneaker male paternity at elevated CO2 Given the importance of fish for food security and ecosystem stability, this study highlights the need for targeted research into the effects of rising CO2 levels on patterns of reproduction in wild fish. Copyright © 2016 The Author(s).
Keywords: *Carbon Dioxide/ch [Chemistry]; *Perciformes/ph [Physiology]; *Reproduction/ph [Physiology]; *Seawater/ch [Chemistry]; *Sexual Behavior, Animal; Alternative reproductive tactics; Animals; CO2 vent; Carbon Dioxide; Climate change; Hydrogen-Ion Concentration; Labrid; Labridae; Male; Oceans and Seas; Perciformes; Reproduction; Seawater; Sexual Behavior, Animal; Symphodus ocellatus; acidification; animal; anthropogenic effect; carbon dioxide; carbon emission; chemistry; climate change; concentration (composition); courtship; dept.psy; ecological stability; food security; male; pH; paternity; perciform; physiology; reproduction; reproductive behavior; sea; sea water; sexual behavior; spawning population; sperm competition; wild population

Human choices between variable and fixed rewards in hypothetical variable‐delay and double‐reward discounting procedures - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2016)
Prior research has shown that nonhumans show an extreme preference for variable-over fixed-delays to reinforcement. This well-established preference for variability occurs because a reinforcer's strength or “value” decreases according to a curvilinear function as its delay increases. The purpose of the present experiments was to investigate whether this preference for variability occurs with human participants making hypothetical choices. In three experiments, participants recruited from Amazon Mechanical Turk made choices between variable and fixed monetary rewards. In a variable-delay procedure, participants repeatedly chose between a reward delivered either immediately or after a delay (with equal probability) and a reward after a fixed delay (Experiments 1 and 2). In a double-reward procedure, participants made choices between an alternative consisting of two rewards, one delivered immediately and one after a delay, and a second alternative consisting of a single reward delivered after a delay (Experiments 1 and 3). Finally, all participants completed a standard delay-discounting task. Although we observed both curvilinear discounting and magnitude effects in the standard discounting task, we found no consistent evidence of a preference for variability-as predicted by two prominent models of curvilinear discounting (i.e., a simple hyperbola and a hyperboloid)-in our variable-delay and double-reward procedures. This failure to observe a preference for variability may be attributed to the hypothetical, rule-governed nature of choices in the present study. In such contexts, participants may adopt relatively simple strategies for making more complex choices.
Keywords: dept.psy; peer-reviewed

A longitudinal follow-up study of happiness and meaning-making - Abe, Jo Ann A. (The Journal of Positive Psychology, 2016)
The long-term outcomes associated with happiness and meaning-making were examined by following up on participants in previous studies on experiential learning an average of 2.5 years later. Measures of happiness and meaning-making were extracted by analyzing the participants' journals using a computerized text-analysis program. Happiness as assessed by a composite measure of positive emotionality showed weak associations with the measures of adaptive functioning, and was negatively correlated with optimism, as well as positively correlated with emotion suppression. By contrast, meaning-making as assessed by composite measures of cognitive processing and self-distancing was robustly positively correlated with almost all measures of adaptive functioning. Regression analyses revealed that the two measures of meaning and their interaction term accounted for 20-24% of the variance in predicting the outcome measures. This study revealed that there may be at times a trade-off between happiness and meaning-making as well as a reversal in their patterns of long-term outcomes.
Keywords: LIWC; dept.psy; follow up; happiness; longitudinal; meaning-making; regression analysis; self-distancing; text-analysis

Ovarian fluid allows directional cryptic female choice despite external fertilization. - Alonzo, Suzanne H; Stiver, Kelly A; Marsh-Rollo, Susan E (Nature Communications, 2016)
In species with internal fertilization, females can favour certain males over others, not only before mating but also within the female's reproductive tract after mating. Here, we ask whether such directional post-mating (that is, cryptic) female mate choice can also occur in species with external fertilization. Using an in vitro sperm competition experiment, we demonstrate that female ovarian fluid (ovarian fluid) changes the outcome of sperm competition by decreasing the importance of sperm number thereby increasing the relative importance of sperm velocity. We further show that ovarian fluid does not differentially affect sperm from alternative male phenotypes, but generally enhances sperm velocity, motility, straightness and chemoattraction. Under natural conditions, female ovarian fluid likely increases the paternity of the preferred parental male phenotype, as these males release fewer but faster sperm. These results imply females have greater control over fertilization and potential to exert selection on males in species with external fertilization than previously thought possible.
Keywords: *Body Fluids/me [Metabolism]; *Choice Behavior/ph [Physiology]; *Fertilization/ph [Physiology]; *Ovary/me [Metabolism]; *Spermatozoa/ph [Physiology]; Animals; Body Fluids; Choice Behavior; Female; Fertilization; Male; Ovary; Perciformes; Perciformes/ph [Physiology]; Reproduction; Reproduction/ph [Physiology]; Sexual Behavior, Animal; Sexual Behavior, Animal/ph [Physiology]; Sperm Count; Spermatozoa; animal; body fluid; decision making; dept.psy; experimental study; female; fertilization; fertilization (reproduction); in vitro study; liquid; male; mate choice; metabolism; ovary; paternity; phenotype; physiology; reproduction; sexual behavior; species; sperm; sperm competition; spermatozoon; spermatozoon count; spermatozoon motility; thinking

Age-related effects of chronic restraint stress on ethanol drinking, ethanol-induced sedation, and on basal and stress-induced anxiety response. - Fernandez, Macarena Soledad; Fabio, Maria Carolina; Miranda-Morales, Roberto Sebastian; Virgolini, Miriam B; De Giovanni, Laura N; Hansen, Cristian; Wille-Bille, Aranza; Nizhnikov, Michael E; Spear, Linda P; Pautassi, Ricardo Marcos (Alcohol, 2016)
Adolescents are sensitive to the anxiolytic effect of ethanol, and evidence suggests that they may be more sensitive to stress than adults. Relatively little is known, however, about age-related differences in stress modulation of ethanol drinking or stress modulation of ethanol-induced sedation and hypnosis. We observed that chronic restraint stress transiently exacerbated free-choice ethanol drinking in adolescent, but not in adult, rats. Restraint stress altered exploration patterns of a light-dark box apparatus in adolescents and adults. Stressed animals spent significantly more time in the white area of the maze and made significantly more transfers between compartments than their non-stressed peers. Behavioral response to acute stress, on the other hand, was modulated by prior restraint stress only in adults. Adolescents, unlike adults, exhibited ethanol-induced motor stimulation in an open field. Stress increased the duration of loss of the righting reflex after a high ethanol dose, yet this effect was similar at both ages. Ethanol-induced sleep time was much higher in adult than in adolescent rats, yet stress diminished ethanol-induced sleep time only in adults. The study indicates age-related differences that may increase the risk for initiation and escalation in alcohol drinking. Copyright © 2016 Elsevier Inc. All rights reserved.
Keywords: *Alcohol Drinking/px [Psychology]; *Anxiety/px [Psychology]; *Ethanol/ad [Administration & Dosage]; *Hypnotics and Sedatives/ad [Administration & Dosage]; *Stress, Psychological/px [Psychology]; Adolescent; Adult; Age Factors; Alcohol Drinking; Alcohol Drinking/ae [Adverse Effects]; Alcohol Drinking/bl [Blood]; Animals; Anxiety; Anxiety/bl [Blood]; Anxiety/et [Etiology]; Article; Chronic Disease; Ethanol; Ethanol/to [Toxicity]; Hypnotics and Sedatives; Hypnotics and Sedatives/to [Toxicity]; Male; Rat; Rats; Rats, Sprague-Dawley; Rats, Wistar; Restraint stress; Sprague Dawley rat; Stress, Psychological; Stress, Psychological/bl [Blood]; Stress, Psychological/co [Complications]; Wistar rat; acute stress; adverse effects; age; age distribution; alcohol; alcohol blood level; alcohol consumption; animal; animal behavior; anxiety; blood; body weight; chronic disease; complication; controlled study; corticosterone; corticosterone blood level; dept.psy; drinking behavior; etiology; hypnosis; hypnotic sedative agent; locomotion; male; mental stress; motor activity; mouse; nonhuman; open field test; peer-reviewed; psychology; rat; restrain stress; righting reflex; sedation; sex difference; sleep time; stimulus response; stress

The role of genes involved in stress, neural plasticity, and brain circuitry in depressive phenotypes: Convergent findings in a mouse model of neglect. - Montalvo-Ortiz, Janitza L; Bordner, Kelly A; Carlyle, Becky C; Gelernter, Joel; Simen, Arthur A; Kaufman, Joan (Behavioural brain research, 2016)
Early life neglect increases risk for the development of psychopathologies during childhood and adulthood, including depression and anxiety disorders. We recently reported epigenetic changes in DNA derived from saliva in three genes predicted depression in a cohort of maltreated children: DNA-binding protein inhibitor ID-3 (ID3), Glutamate NMDA Receptor (GRIN1), and Tubulin Polymerization Promoting Protein (TPPP). To validate the role of these genes in depression risk, secondary analyses were conducted of gene expression data obtained from medial prefrontal cortex (mPFC) tissue of mice subjected to a model of maternal neglect which included maternal separation and early weaning (MSEW). Anxiety and depression-like phenotype data derived using the elevated plus maze (EPM) and forced swimming test (FST), respectively, were also available for secondary analyses. Behavioral tests were conducted in MSEW and control adult male mice when they were between 65 and 80days old. ID3, GRIN1 and TPPP gene expression in the mPFC were found to significantly predict behavioral differences in the EPM and FST. These results further support the role of these genes in the etiology of depressive and anxiety phenotypes following early life stress. Copyright © 2016. Published by Elsevier B.V.
Keywords: *Depression/pa [Pathology]; *Gene Expression Regulation/ph [Physiology]; *Maternal Deprivation; *Neuronal Plasticity/ph [Physiology]; *Prefrontal Cortex/me [Metabolism]; *Stress, Psychological/pa [Pathology]; Animals; Article; C57BL mouse; DBA mouse; DNA-binding protein inhibitor ID-3 (ID3); Depression; Disease Models, Animal; GRIN1 gene; Gene Expression Regulation; Glutamate NMDA receptor (GRIN1); Gprin1 protein, mouse; ID3 gene; Idb3 protein, mouse; Inhibitor of Differentiation Proteins; Inhibitor of Differentiation Proteins/ge [Genetics]; Inhibitor of Differentiation Proteins/me [Metabolism]; Male; Maternal Deprivation; Maze Learning; Maze Learning/ph [Physiology]; Methylation; Mice; Mice, Inbred C57BL; Mice, Inbred DBA; Microarray Analysis; Neglect; Nerve Tissue Proteins; Nerve Tissue Proteins/ge [Genetics]; Nerve Tissue Proteins/me [Metabolism]; Neuronal Plasticity; Prefrontal Cortex; RNA, Messenger; RNA, Messenger/me [Metabolism]; Receptors, N-Methyl-D-Aspartate; Receptors, N-Methyl-D-Aspartate/ge [Genetics]; Receptors, N-Methyl-D-Aspartate/me [Metabolism]; Stress, Psychological; Swimming; Swimming/px [Psychology]; TPPP protein, mouse; Tubulin polymerization promoting protein (TPPP); animal; animal experiment; animal model; animal tissue; anxiety; connectome; controlled study; depression; dept.psy; disease activity; disease model; early life stress; gene; gene expression regulation; gene function; gene identification; gene location; genetics; inhibitor of differentiation protein; male; maternal deprivation; maze test; medial prefrontal cortex; mental stress; messenger RNA; metabolism; microarray analysis; molecular dynamics; molecular pathology; mouse; n methyl dextro aspartic acid receptor; nerve cell plasticity; nerve protein; nonhuman; pathology; peer-reviewed; phenotype; physiology; prediction; prefrontal cortex; priority journal; psychology; swimming; tubulin polymerization promoting protein gene

Transgenerational transmission of the effect of gestational ethanol exposure on ethanol Use‐Related behavior - Nizhnikov, Michael E; Popoola, Daniel O; Cameron, Nicole M (Alcoholism: Clinical and Experimental Research, 2016)
Background: Prenatal alcohol exposure (PAE) enhances the risk for alcoholism by increasing the propensity to consume alcohol and altering neurophysiological response to alcohol challenge. Trans-generationally transmittable genetic alterations have been implicated in these behavioral changes. To date, transgenerational transmission of PAE-induced behavioral responses to alcohol has never been experimentally investigated. Therefore, we explored the transgenerational transmission of PAE-induced behavioral effects across 3 generations. Methods: Pregnant Sprague Dawley dams received 1 g/kg ethanol (EtOH) or water daily on gestational days 17 through 20 via gavage, or remained untreated in their home cages. To produce second filial (F2) or F3 generations, similarly treated adult F1 or F2 offspring were mated and left undisturbed through gestation. On postnatal day (PND) 14, male and female F1, F2, and F3 offspring were tested for consumption of 5% (w/v) EtOH (in water), or water. Using the loss of righting reflex (LORR) paradigm on PND 42, F1 and F2 adolescent male offspring were tested for sensitivity to acute EtOH-induced sedation-hypnosis at 3.5 or 4.5 g/kg dose. F3 male adolescents were similarly tested at 3.5 g/kg dose. Blood EtOH concentration (BEC) was measured at waking. Results: EtOH exposure increased EtOH consumption compared to both water and untreated control groups in all generations. EtOH-treated group F1 and F2 adolescents displayed attenuated LORR duration compared to the water group. No attenuated LORR was observed in the F3 generation. BEC at waking corroborated with the significant LORR duration differences while also revealing differences between untreated control and water groups in F1 and F2 generations. Conclusions: Our results provide novel behavioral evidence attesting that late gestational moderate EtOH exposure increases EtOH intake across 3 generations and may alter sensitivity to EtOH-induced sedation-hypnosis across 2 generations. © 2016 Research Society on Alcoholism.
Keywords: Alcohol Drinking; Animals; Animals, Newborn; Article; Ethanol; Female; Infant; Intake; Loss of Righting Reflex; Male; Pregnancy; Prenatal Exposure Delayed Effects; Rat; Rats; Rats, Sprague-Dawley; Sprague Dawley rat; adult; alcohol; alcoholism; animal; animal experiment; behavior; behavior change; chemically induced; dept.psy; drinking behavior; epigenetics; female; genetics; hypnosis; male; newborn; nonhuman; pregnancy; prenatal exposure; priority journal; progeny; psychology; rat; righting reflex; sedation; transgenerational transmission; wakefulness; water

Very-Brief, Web-Based Interventions for Reducing Alcohol Use and Related Problems among College Students: A Review. - Leeman, Robert F; Perez, Elliottnell; Nogueira, Christine; DeMartini, Kelly S (Frontiers in psychiatry, 2015)
Very-brief, web-based alcohol interventions have great potential due to their convenience, ease of dissemination, and college students' stated preference for this intervention modality. To address the efficacy of these interventions, we conducted a review of the literature to identify randomized controlled trials (RCTs). Fifteen published reports were included. All RCTs meeting criteria for inclusion tested an intervention that featured personalized feedback on students' patterns of alcohol consumption. This review found some evidence to support the efficacy of very-brief, web-based interventions among college students for alcohol use reduction. Several trials, however, reported no evidence of efficacy and the methods of multiple trials raised concerns about potential bias that may have influenced study results. By contrast, this review did not yield evidence to support the efficacy of very-brief, web-based interventions for reduction of alcohol--related problems among college students. We found evidence to support the efficacy of two main types of intervention content: (a) focused solely on personalized normative feedback designed to correct misconceptions about peer alcohol consumption and (b) multi-component interventions. Future research is needed to test enhancements to very-brief, web-based interventions that feature personalized feedback on patterns of alcohol use and to determine for which types of college drinkers (e.g., heavier or lighter drinkers) these interventions are most efficacious. In addition, future studies are needed to test novel, very-brief, web-based interventions featuring approaches other than personalized feedback. In summary, this review yielded some evidence supporting very-brief, web-based interventions in reducing alcohol use but not related problems in college students. Very-brief, web-based interventions are worth pursuing given their convenience, privacy, and potential public health benefit.
Keywords: Computer; Effectiveness; Intervention; Motivational interviewing; Prevention; Review; Technology; Young adult; Youth; alcohol consumption; attitude to health; college student; dept.psy; evidence based practice; follow up; human; outcome assessment; peer group; peer-reviewed; personalized feedback; public health service; randomized controlled trial (topic); sample size; systematic error; very brief web based intervention

Should police use ACID? Training and credibility assessment using transcripts versus recordings - Colwell, Kevin; James-Kangal, Neslihan; Hiscock-Anisman, Cheryl; Phelan, Vivian (Journal of Forensic Psychology Practice, 2015)
There is a need for an applicable system of investigative interviewing and credibility assessment that extends science to practice. Experiment 1: Officers assessed the credibility of colleagues in a face-to-face interaction. Fourteen of sixteen officers were wrong in determining whether their colleague was responding honestly to them or lying to them. Experiment 2 compared untrained officers to officers trained in Assessment Criteria Indicative of Deception (ACID) in their ability to assess the credibility of statements regarding real and mock crimes by analyzing either verbatim transcripts or audio recordings. Officers who were trained in ACID performed significantly better after training than before, and significantly better than a group of officers who were never trained in ACID (89% correct versus 53% correct). No differences emerged due to analyzing transcripts versus recordings. The practical aspects of these results are discussed, including success rate, ease of application, and ease of training. The theoretical discussion includes differential recall enhancement and impression management. Finally, limitations and suggestions for future research are presented.
Keywords: Article; Assessment Criteria Indicative of Deception (ACID); adult; assessment criteria indicative of deception; audio recording; clinical assessment tool; controlled study; credibility assessment; criminal justice; deception; decision making; dept.psy; diagnostic accuracy; differential recall enhancement; human; human experiment; investigative interviewing; police; recall; scoring system; task performance; training; verbal behavior; videorecording; visual stimulation; word recognition; written language

Prenatal ethanol increases ethanol intake throughout adolescence, alters ethanol-mediated aversive learning, and affects μ but not δ or κ opioid receptor mRNA expression - Fabio, María Carolina; Macchione, Ana Fabiola; Nizhnikov, Michael E.; Pautassi, Ricardo Marcos (European Journal of Neuroscience, 2015)
Animal models of prenatal ethanol exposure (PEE) have indicated a facilitatory effect of PEE on adolescent ethanol intake, but few studies have assessed the effects of moderate PEE throughout adolescence. The mechanisms underlying this facilitatory effect remain largely unknown. In the present study, we analysed ethanol intake in male and female Wistar rats with or without PEE (2.0 g/kg, gestational days 17-20) from postnatal days 37 to 62. The results revealed greater ethanol consumption in PEE rats than in controls, which persisted throughout adolescence. By the end of testing, ethanol ingestion in PEE rats was nearly 6.0 g/kg. PEE was associated with insensitivity to ethanol-induced aversion. PEE and control rats were further analysed for levels of μ, δ and κ opioid receptor mRNA in the infralimbic cortex, nucleus accumbens shell, and ventral tegmental area. Similar levels of mRNA were observed across most areas and opioid receptors, but μ receptor mRNA in the ventral tegmental area was significantly increased by PEE. Unlike previous studies that assessed the effects of PEE on ethanol intake close to birth, or in only a few sessions during adolescence, the present study observed a facilitatory effect of PEE that lasted throughout adolescence. PEE was associated with insensitivity to the aversive effect of ethanol, and increased levels of μ opioid receptor transcripts. PEE is a prominent vulnerability factor that probably favors the engagement of adolescents in risky trajectories of ethanol use. © 2015 Federation of European Neuroscience Societies and John Wiley & Sons Ltd.
Keywords: *Alcohol Drinking/pp [Physiopathology]; *Avoidance Learning/de [Drug Effects]; *Central Nervous System Depressants/to [Toxicity]; *Ethanol/to [Toxicity]; *Prenatal Exposure Delayed Effects/ci [Chemically Induced]; *Receptors, Opioid, delta/me [Metabolism]; *Receptors, Opioid, kappa/me [Metabolism]; Adolescent; Age Factors; Alcohol Drinking; Animals; Article; Aversive conditioning; Avoidance Learning; Central Nervous System Depressants; Ethanol; Ethanol intake; Female; Male; Opioid receptors; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal Exposure Delayed Effects/pp [Physiopathology]; Prenatal ethanol; RNA isolation; RNA, Messenger; RNA, Messenger/me [Metabolism]; Rats; Rats, Wistar; Receptors, Opioid, delta; Receptors, Opioid, delta/ge [Genetics]; Receptors, Opioid, kappa; Receptors, Opioid, kappa/ge [Genetics]; Wistar rat; adolescence; adolescent; age; alcohol; alcohol consumption; alcohol intoxication; animal; animal experiment; animal model; aversion; aversive behavior; aversive conditioning; avoidance behavior; body weight; central depressant agent; chemically induced; controlled study; delta opiate receptor; dept.psy; drinking behavior; drug effects; ethanol intake; facilitation; female; fluid intake; genetics; glyceraldehyde 3 phosphate dehydrogenase; kappa opiate receptor; male; messenger RNA; metabolism; microdissection; motivation; mu opiate receptor; nonhuman; opioid receptors; pathophysiology; place preference; polymerase chain reaction; pregnancy; prenatal ethanol; prenatal ethanol exposure; prenatal exposure; priority journal; protein expression; quantitative analysis; rat; reinforcement; reverse transcription; sigma opiate receptor; sugar intake

Differential emotions theory as a theory of personality development - Abe, Jo Ann A. (Emotion Review, 2015)
In The Face of Emotions, which was Carroll Izard's first major attempt at elaborating his differential emotions theory (DET), he stated that the book presents a theoretical framework for the study of emotions and their role in personality and interpersonal processes. Yet, over the years, his contribution to personality theory has generally been overshadowed by the attention focused on his views on facial expressions and the structure of emotions. This article will begin with a brief overview of the DET perspective on personality development. Then, it will examine how the DET framework can be used to organize recent findings from three lines of research on adult personality. It will conclude with suggestions for future research as well as some personal recollections.
Keywords: dept.psy; differential emotions theory; emotions; personality development

Introduction: special section to honor carroll izard - Abe, Jo Ann A.; Schultz, David (Emotion Review, 2015)
Keywords: dept.psy

Endogenous opioids as substrates for ethanol intake in the neonatal rat: The impact of prenatal ethanol exposure on the opioid family in the early postnatal period. - Bordner, Kelly; Deak, Terrence (Physiology & Behavior, 2015)
BACKGROUND: Despite considerable knowledge that prenatal ethanol exposure can lead to devastating effects on the developing fetus, alcohol consumption by pregnant women remains strikingly prevalent. Both clinical and basic research has suggested that, in addition to possible physical, behavioral, and cognitive deficits, gestational exposure to alcohol may lead to an increased risk for the development of later alcohol-related use and abuse disorders. The current work sought to characterize alterations in endogenous opioid signaling peptides and gene expression produced by ethanol exposure during the last days of gestation., METHODS: Experimental subjects were 4-, 8-, and 12-day old infant rats obtained from pregnant females that were given daily intubations of 0, 1, or 2g/kg ethanol during the last few days of gestation (GDs 17-20). Using real-time RT-PCR, western blotting analysis, and enzyme immunoassays, we examined mRNA and protein for three opioid receptors and ligands in the nucleus accumbens, ventral tegmental area, and hypothalamus., RESULTS: Three main trends emerged - (1) mRNA for the majority of factors was found to upregulate across each of the three postnatal ages assessed, indicative of escalating ontogenetic expression of opioid-related genes; (2) prenatal ethanol significantly reduced many opioid peptides, suggesting a possible mechanism by which prenatal exposure can affect future responsiveness towards ethanol; and (3) the nucleus accumbens emerged as a key site for ethanol-dependent effects, suggesting a potential target for additional assessment and intervention towards understanding the ethanol's ability to program the developing brain., CONCLUSION: We provide a global assessment of relatively long-term changes in both opioid gene expression and protein following exposure to only moderate amounts of ethanol during a relatively short window in the prenatal period. These results suggest that, while continuing to undergo ontogenetic changes, the infant brain is sensitive to prenatal ethanol exposure and that such exposure may lead to relatively long-lasting changes in the endogenous opioid system within the reward circuitry. These data indicate a potential mechanism and target for additional assessments of ethanol's ability to program the brain, affecting later responsiveness towards the drug. Copyright © 2015 Elsevier Inc. All rights reserved.
Keywords: *Alcohol Drinking/pp [Physiopathology]; *Central Nervous System Depressants/pd [Pharmacology]; *Ethanol/pd [Pharmacology]; *Gene Expression Regulation, Developmental/de [Drug Effects]; *Prenatal Exposure Delayed Effects/pp [Physiopathology]; *Receptors, Opioid/me [Metabolism]; Age Factors; Alcohol Drinking; Analysis of Variance; Animals; Animals, Newborn; Article; Brain; Brain/gd [Growth & Development]; Brain/me [Metabolism]; Central Nervous System Depressants; Dynorphins; Dynorphins/ge [Genetics]; Dynorphins/me [Metabolism]; Enkephalins; Enkephalins/ge [Genetics]; Enkephalins/me [Metabolism]; Ethanol; Female; Gene Expression Regulation, Developmental; Gestational Age; MRNA; Male; Ontogeny; Opioids; Pregnancy; Prenatal Exposure Delayed Effects; Pro-Opiomelanocortin; Pro-Opiomelanocortin/ge [Genetics]; Pro-Opiomelanocortin/me [Metabolism]; Protein; Protein Precursors; Protein Precursors/ge [Genetics]; Protein Precursors/me [Metabolism]; RNA, Messenger; RNA, Messenger/me [Metabolism]; Rat; Rats; Rats, Sprague-Dawley; Receptors, Opioid; Receptors, Opioid/ge [Genetics]; Sprague Dawley rat; Western blotting; age; alcohol; alcohol consumption; analysis of variance; animal; animal experiment; animal tissue; beta endorphin; brain; brain development; central depressant agent; controlled study; delta opiate receptor; dept.psy; drinking behavior; drug effects; dynorphin; endorphin; enkephalin; enzyme immunoassay; female; gene expression; gene expression regulation; genetics; gestation period; gestational age; growth, development and aging; hypothalamus; infant; kappa opiate receptor; male; messenger RNA; metabolism; mu opiate receptor; newborn; nonhuman; nucleus accumbens; ontogeny; opiate receptor; pathophysiology; peer-reviewed; perinatal period; postnatal development; pre-prodynorphin; pregnancy; prenatal exposure; preprodynorphin; preproenkephalin; priority journal; proopiomelanocortin; protein; protein precursor

Change in the hedonic value of an aversive stimulus in the presence of a pre-exposed odor. - Kamenetzky, Giselle V; Suarez, Andrea B; Pautassi, Ricardo M; Mustaca, Alba E; Nizhnikov, Michael E (Physiology & behavior, 2015)
Rats exhibit a sensitive period from the time of birth until postnatal day 10 during which they develop preferences for odors even if those odors are paired with a moderately aversive stimulus. It is still unknown whether pre-exposure to an odor produces alterations on intake responses of basic tastants, and on other patterns that indicate a change in the hedonic value of reward, such as nipple grasping behavior. The current study assessed the effect of pre-exposure to an odor immediately after birth on intake responses of appetitive and aversive tastants. The objectives were to assess if 3-hour-old rats adjust their behaviors to obtain different values of appetitive and aversive rewards in the presence of a familiar odor. Specifically we wanted to determine whether the intake of saccharin or quinine, administered through the artificial nipple, increases in the presence of the familiar odor. Results showed that 3-hour-old rats differentially respond to two different concentrations of saccharin and two concentrations of quinine. In the presence of the pre-exposed odor newborn rats increased intake and grasp responses to the artificial nipple containing quinine. This effect disappeared with a higher concentration of quinine. These results suggest that the pre-exposed odor generated a change in the hedonic value of the aversive reward. Copyright © 2014 Elsevier Inc. All rights reserved.
Keywords: *Avoidance Learning/ph [Physiology]; *Conditioning, Psychological/ph [Physiology]; *Discrimination, Psychological/ph [Physiology]; *Emotions/ph [Physiology]; *Odorants; *Smell/ph [Physiology]; Age Factors; Analgesics, Non-Narcotic; Animals; Animals, Newborn; Appetitive Behavior; Appetitive Behavior/ph [Physiology]; Article; Aversive solutions; Avoidance Learning; Conditioning (Psychology); Discrimination (Psychology); Dose-Response Relationship, Drug; Emotions; Female; Male; Newborn rats; Odors; Olfactory learning; Ontogeny; Quinine; Quinine/ad [Administration & Dosage]; Rats; Rats, Sprague-Dawley; Reaction Time; Reaction Time/de [Drug Effects]; Reaction Time/ph [Physiology]; Saccharin; Saccharin/ad [Administration & Dosage]; Smell; Sprague Dawley rat; Sweetening Agents; age; analgesic agent; animal; animal behavior; animal experiment; appetite; aversion; avoidance behavior; birth; bitter taste; conditioning; controlled study; dept.psy; dose response; drug effects; emotion; exposure; female; food intake; grip strength; gustatory system; male; newborn; nipple; nonhuman; odor; peer-reviewed; perceptive discrimination; physiology; priority journal; quinine; rat; reaction time; reward; saccharin; stimulus; sweetening agent; taste

Can low-level ethanol exposure during pregnancy influence maternal care? An investigation using two strains of rat across two generations. - Popoola, Daniel O; Borrow, Amanda P; Sanders, Julia E; Nizhnikov, Michael E; Cameron, Nicole M (Physiology & behavior, 2015)
Gestational alcohol use is well documented as detrimental to both maternal and fetal health, producing an increase in offspring's tendency for alcoholism, as well as in behavioral and neuropsychological disorders. In both rodents and in humans, parental care can influence the development of offspring physiology and behavior. Animal studies that have investigated gestational alcohol use on parental care and/or their interaction mostly employ heavy alcohol use and single strains. This study aimed at investigating the effects of low gestational ethanol dose on parental behavior and its transgenerational transmission, with comparison between two rat strains. Pregnant Sprague Dawley (SD) and Long Evans (LE) progenitor dams (F0) received 1g/kg ethanol or water through gestational days 17-20 via gavage, or remained untreated in their home cages. At maturity, F1 female offspring were mated with males of the same strain and treatment and were left undisturbed through gestation. Maternal behavior was scored in both generations during the first six postnatal days. Arch-back nursing (ABN) was categorized as: 1, when the dam demonstrated minimal kyphosis; 2, when the dam demonstrated moderate kyphosis; and 3, when the dam displayed maximal kyphosis. Overall, SD showed greater amounts of ABN than LE dams and spent more time in contact with their pups. In the F0 generation, water and ethanol gavage increased ABN1 and contact with pups in SD, behaviors which decreased in treated LE. For ABN2, ethanol-treated SD dams showed more ABN2 than water-treated dams, with no effect of treatment on LE animals. In the F1 generation, prenatal exposure affected retrieval. Transgenerational transmission of LG was observed only in the untreated LE group. Strain-specific differences in maternal behavior were also observed. This study provides evidence that gestational gavage can influence maternal behavior in a strain-specific manner. Our results also suggest that the experimental procedure during gestation and genetic variations between strains may play an important role in the behavioral effects of prenatal manipulations. Copyright © 2015 Elsevier Inc. All rights reserved.
Keywords: *Central Nervous System Depressants/to [Toxicity]; *Ethanol/to [Toxicity]; *Maternal Behavior; *Prenatal Exposure Delayed Effects/ci [Chemically Induced]; Alcohol Drinking; Alcohol Drinking/pp [Physiopathology]; Analysis of Variance; Animals; Animals, Newborn; Article; Central Nervous System Depressants; Ethanol; Female; Grooming; Intragastric gavage; Long Evans rat; Male; Maternal Behavior; Maternal care; Posture; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal Exposure Delayed Effects/nu [Nursing]; Prenatal Exposure Delayed Effects/pp [Physiopathology]; Rat; Rats; Rats, Long-Evans; Rats, Sprague-Dawley; Species Specificity; Sprague Dawley rat; Time Factors; Transgenerational; alcohol; alcohol consumption; analysis of variance; animal; animal experiment; animal model; body posture; central depressant agent; chemically induced; controlled study; dept.psy; drinking behavior; female; genetic variability; grooming; kyphosis; licking; male; maternal behavior; maternal care; mating; newborn; nonhuman; nursing; parental behavior; pathophysiology; peer-reviewed; pregnancy; prenatal exposure; priority journal; progeny; rat; species difference; time

Neural gene expression profiles and androgen levels underlie alternative reproductive tactics in the ocellated wrasse, symphodus ocellatus - Stiver, Kelly A.; Harris, Rayna M.; Townsend, Jeffrey P.; Hofmann, Hans A.; Alonzo, Suzanne H. (Ethology, 2014)
Discrete variation in reproductive behavior and physiology is observed in diverse taxa. Although it is known that most within-sex alternative reproductive tactics arise as a consequence of phenotypic plasticity, relatively little is known about differential neural gene expression among plastic alternative reproductive phenotypes. In the ocellated wrasse Symphodus ocellatus, males exhibit one of three alternative tactics (nesting, satellite, and sneaker) within a reproductive season, but switch tactics between years. Satellites and sneakers spawn parasitically in dominant (nesting) males' nests, but only nesting males provide parental care. Nesting and satellite males show transient cooperative defense of nests against sneakers. Here, we analyze circulating sex steroid hormone levels and neural gene expression profiles in these three male phenotypes and in females. 11-ketotestosterone (but not testosterone) was highest in nesting males, while estradiol was highest in females. Brain transcriptomes of satellites and females were most similar to each other and intermediate to nesting and sneaker males. Sneakers showed more total expression differences, whereas nesting males showed higher magnitude expression differences. Our findings reveal the surprising extent to which neural gene expression patterns vary across reproductive tactics that vary in a number of social traits, including aggression, territoriality, and cooperation, providing important insights into the molecular mechanisms that may underlie variation in cooperative and reproductive behavior. © 2014 Blackwell Verlag GmbH.
Keywords: Androgens; Competition; Cooperation; Mating tactic; Microarray; Reproduction; Symphodus ocellatus; dept.psy

Hope, will, purpose, competence, and fidelity: ego strengths as predictors of career identity - Anthis, Kristine (Identity, 2014)
This correlational study examined the relationships among ego strengths and career identity. Self-report data were collected from a sample of university undergraduates (N = 239). Participants completed the Psychosocial Inventory of Ego Strengths and the Vocational Identity Status Assessment. The results revealed gender differences, primarily in career identity. The findings also showed that the unique variance explained in career identity by each ego strength was modest, indicating that the best predictor of career identity is the overall level of ego strengths. Suggestions for future research, such as longitudinal designs to establish ego strengths as developmental precursors of career identity, are provided. © 2014 Copyright Taylor & Francis Group, LLC.
Keywords: dept.psy

Adaptation and Sexual Offending - Camilleri, Joseph A.; Stiver, Kelly A. (Evolutionary Perspectives on Human Sexual Psychology and Behavior, 2014)
Agreement on the causes of sexual offending has eluded scholars because of an emphasis on studying proximate causes—as with crime in general, there are numerous variables that correlate with sexual offending. A more consilient view of sexual offending includes an evolutionary approach that attempts to answer ultimately why such behavior exists. To guide this research, Camilleri (The Oxford handbook of evolutionary perspectives on violence, homicide, and war, New York, 173–196) proposed a typology of sexual offenders that classifies offending based on two dimensions: (1) whether the behavior is an adaptation, by-product, or disorder and (2) if the mechanism is obligate or facultative. Categories resulting from this typology seem to capture the variability of sexual offending behavior. This chapter mostly reviews evidence of how sexual offending could function as an adaptation, draws links from nonhuman behavior literature, and briefly reviews alternative explanations, including by-products and disorders.
Keywords: Antisocial Behavior; Nonhuman Animal; Psychopathic Trait; Sexual Coercion; Sexual Offender; dept.psy

Brief prenatal ethanol exposure alters behavioral sensitivity to the kappa opioid receptor agonist (U62,066E) and antagonist (Nor‐BNI) and reduces kappa opioid receptor expression - Nizhnikov, Michael E; Pautassi, Ricardo Marcos; Carter, Jenna M; Landin, Justine D; Varlinskaya, Elena I; Bordner, Kelly A; Werner, David F; Spear, Norman E (Alcoholism: Clinical and Experimental Research, 2014)
Background: Approximately 10 to 15% of women consume alcohol (ethanol [EtOH]) during pregnancy in the United States. Even low amounts of EtOH consumption during pregnancy can elicit long-term consequences. Prenatal experience with as few as 3 drinks has been associated with increase problem drinking in adulthood. Such effects are corroborated in rodents; however, the underlying neural adaptations contributing to this effect are not clear. In the current set of experiments, we investigated whether changes in EtOH responding following prenatal EtOH exposure involved kappa opioid receptor activation and expression. Methods: Sprague-Dawley rats were prenatally exposed to low levels of alcohol (1.0 g/kg) during late gestation (gestational days 17 to 20 [GD17-20]) via intragastric intubation of pregnant dams. Following birth, EtOH intake, kappa- and mu-opioid-induced place conditioning, and kappa opioid receptor expression in mesolimbic brain regions were assessed in infant rats (postnatal days 14 to 15 [PD14-15]) that were offspring of dams given EtOH, vehicle, or untreated, during pregnancy. Results: Animals exposed to prenatal alcohol drank more alcohol later in life and exhibited significant changes in the kappa opioid system. While control subjects found kappa opioid activation aversive, animals exposed to EtOH prenatally exhibited either no aversion or appetitive responding. Further analysis revealed that synaptosomal kappa opioid receptor expression was significantly decreased in brain areas implicated in responding to EtOH. Conclusions: Overall, these data suggest that prenatal EtOH affects kappa opioid function and expression and that these changes may be involved in increased drinking later in life. © 2014 by the Research Society on Alcoholism.
Keywords: Alcohol Drinking; Animals; Brain Chemistry; Conditioning (Psychology); Ethanol; Female; Gene Expression; Infant; Kappa; Male; Naltrexone; Opioid; Pregnancy; Prenatal Exposure Delayed Effects; Pyrrolidines; Rats; Rats, Sprague-Dawley; Receptors, Opioid, kappa; Sprague Dawley rat; Western blotting; agonists; alcohol; alcohol abuse; alcohol consumption; analogs and derivatives; animal; animal experiment; animal tissue; antagonists and inhibitors; article; behavioral science; biosynthesis; brain level; chemically induced; conditioning; controlled study; dept.psy; drinking behavior; drug effects; drug therapy; female; fluid intake; gene expression; gestation period; kappa opiate receptor; kappa opiate receptor antagonist; limbic cortex; male; metabolism; naltrexone; nonhuman; nor bni; norbinaltorphimine; pregnancy; prenatal exposure; priority journal; protein expression; pyrrolidine derivative; rat; spiradoline; spiradoline mesilate; unclassified drug

Development of phonological constancy: 19-Month-Olds, but not 15-Month-Olds, identify words in a non-native regional accent - Mulak, Karen E.; Best, Catherine T.; Tyler, Michael D.; Kitamura, Christine; Irwin, Julia R. (Child Development, 2013)
By 12months, children grasp that a phonetic change to a word can change its identity (phonological distinctiveness). However, they must also grasp that some phonetic changes do not (phonological constancy). To test development of phonological constancy, sixteen 15-month-olds and sixteen 19-month-olds completed an eye-tracking task that tracked their gaze to named versus unnamed images for familiar words spoken in their native (Australian) and an unfamiliar non-native (Jamaican) regional accent of English. Both groups looked longer at named than unnamed images for Australian pronunciations, but only 19-month-olds did so for Jamaican pronunciations, indicating that phonological constancy emerges by 19months. Vocabulary size predicted 15-month-olds' identifications for the Jamaican pronunciations, suggesting vocabulary growth is a viable predictor for phonological constancy development.
Keywords: Acoustic Stimulation; Female; Fixation, Ocular; Humans; Infant; Language Development; Male; Perceptual Masking; Phonetics; Psychomotor Performance; Recognition (Psychology); Speech Perception; Vocabulary; article; auditory stimulation; dept.psy; eye fixation; female; human; infant; language development; linguistics; male; perception; phonetics; physiology; psychomotor performance; recognition; speech perception

Pigeons' choices with token stimuli in concurrent variable-interval schedules: concurrent vi schedules with tokens - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2013)
Twelve pigeons responded on concurrent variable-interval schedules that delivered token stimuli (stimulus lights for some pigeons, and white circles on the response keys for others). During exchange periods, each token could be exchanged for food on a fixed-ratio 1 schedule. Across conditions, the exchange requirements ( number of tokens that had to be earned before they could be exchanged for food) varied between one and four for the two response keys. The main findings were that the pigeons' response percentages varied as a function of the number of tokens earned at any given moment, and they were determined by both the delays to food and by the number of food deliveries in the exchange periods. In some conditions, tokens had to be earned but were not visible during the variable-interval schedules for one or both keys. When one key had visible tokens and the other did not, the pigeons showed a preference for the key without visible tokens. A model based on the matching law and a hyperbolic delay-discounting equation could account for the main patterns of choice responding, and for how response percentages changed as successive tokens were earned. The results are consistent with the view that the token stimuli served as discriminative stimuli that signaled the current delays to food.
Keywords: *Choice Behavior; *Token Economy; Animals; Columbidae; Concurrent variable-interval schedules; Conditioning, Operant; Generalized matching law; Hyperbolic discounting; Keypeck; Male; Models, Psychological; Pigeons; Reinforcement Schedule; Token stimuli; dept.psy; peer-reviewed

Assessment Criteria Indicative of Deception: An Example of the New Paradigm of Differential Recall Enhancement - Colwell, Kevin; Hiscock-Anisman, Cheryl; Fede, Jacquelyn (Applied Issues in Investigative Interviewing, Eyewitness Memory, and Credibility Assessment, 2013)
The present chapter details the historical and conceptual evolution of a new paradigm in statement analysis that has developed over the past 20 years. There has been an increasing awareness of the importance of interviewing designed to facilitate the detection of deception as a necessary component of statement analysis (Colwell, Hiscock, & Memon, 2002; Hartwig & Bond, 2011; Hernández-Fernaud & Alonso-Quecuty, 1997; Koehnken, Schimossek, Ascherman, & Hofer, 1995; Vrij, Fisher, Mann, & Leal, 2006). Subsequently, the work of multiple researchers has created a zeitgeist that has nurtured and informed the development of this new paradigm. This chapter begins by providing a quick overview of the various lines of research that comprise this paradigm. Attention is then given to credibility assessment and statement content criteria that discriminate honest from deceptive responding. Then, the focus is on strategies of impression management and the subjective experience of respondents during an investigative interview. This sets the stage for a discussion of investigative interviewing structure and techniques that facilitate the detection of deception through the process of differential recall enhancement (DRE: Colwell et al., 2012). Finally, this chapter considers in detail an approach to interviewing and assessment that is representative of the new paradigm.
Keywords: Content Criterion; Free Recall; Impression Management; Present Volume; Target Event; dept.psy

Sharing of potential nest sites by Etheostoma olmstedi males suggests mutual tolerance in an alloparental species. - Stiver, Kelly A; Wolff, Stephen H; Alonzo, Suzanne H (PloS one, 2013)
When reproductive competitors tolerate or cooperate with one another, they may gain particular benefits, such as collectively guarding resources or attracting mates. Shared resources may be those essential to reproduction, such as a breeding site or nest. Using the tessellated darter, a species where males but not females compete over potential nest sites, we examined site use and sharing under controlled conditions of differing competitor density. Sharing was observed even when competitor density was low and individuals could have each occupied a potential nest site without same-sex sharing. Males were more likely to share a nest site with one other when the difference in size between them was larger rather than smaller. There was no evidence that female sharing was dependent on their relative size. Fish were generally more likely to use and share larger sites, in accordance with the greater relative surface area they offered. We discuss how one or both sharing males may potentially benefit, and how male sharing of potential nest sites could relate to female mating preferences. Tessellated darter males are known to provide alloparental care for eggs but this occurs without any social contact between the alloparent and the genetic father of the young. Thus, the suggestion that they may also share sites and maintain social contact with reproductive competitors highlights the importance of increased focus on the potential complexity of reproductive systems.
Keywords: *Behavior, Animal; *Nesting Behavior; *Perches/ph [Physiology]; *Reproduction; Animals; Behavior, Animal; Etheostoma olmstedi; Female; Male; Nesting Behavior; Perches; Reproduction; Sexual Behavior, Animal; animal behavior; article; competitor species; controlled study; dept.psy; female; fish; male; male animal; mate choice; nesting; nonhuman; peer-reviewed; population density; population size; sex difference; social behavior; symbiosis

Maternal separation with early weaning: A rodent model providing novel insights into neglect associated developmental deficits - Carlyle, Becky C.; Duque, Alvaro; Kitchen, Robert R.; Bordner, Kelly A.; Coman, Daniel; Doolittle, Eliza; Papademetris, Xenophonios; Hyder, Fahmeed; Taylor, Jane R.; Simen, Arthur A. (Development and Psychopathology, 2012)
Child neglect is the most prevalent form of child maltreatment in the United States, and poses a serious public health concern. Children who survive such episodes go on to experience long-lasting psychological and behavioral problems, including higher rates of post-traumatic stress disorder symptoms, depression, alcohol and drug abuse, attention-deficit/hyperactivity disorder, and cognitive deficits. To date, most research into the causes of these life-long problems has focused on well-established targets such as stress responsive systems, including the hypothalamus-pituitary-adrenal axis. Using the maternal separation and early weaning model, we have attempted to provide comprehensive molecular profiling of a model of early-life neglect in an organism amenable to genomic manipulation: the mouse. In this article, we report new findings generated with this model using chromatin immunoprecipitation sequencing, diffuse tensor magnetic resonance imaging, and behavioral analyses. We also review the validity of the maternal separation and early weaning model, which reflects behavioral deficits observed in neglected humans including hyperactivity, anxiety, and attentional deficits. Finally, we summarize the molecular characterization of these animals, including RNA profiling and label-free proteomics, which highlight protein translation and myelination as novel pathways of interest.
Keywords: Animals; Anxiety; Attention; Behavior, Animal; Brain; C57BL mouse; Child; Child Abuse; Chromatin Immunoprecipitation; Developmental Disabilities; Diffusion Tensor Imaging; Disease Models, Animal; Epigenesis, Genetic; Humans; Maternal Deprivation; Mice; Mice, Inbred C57BL; Prefrontal Cortex; Proteomics; RNA; Weaning; animal; animal behavior; anxiety; article; attention; brain; child; child abuse; chromatin immunoprecipitation; dept.psy; developmental disorder; diffusion tensor imaging; disease model; genetic epigenesis; genetics; human; maternal deprivation; metabolism; mouse; pathophysiology; peer-reviewed; prefrontal cortex; proteomics; psychological aspect; weaning

Choice behavior of pigeons (Columba livia), college students, and preschool children (Homo sapiens) in the Monty Hall dilemma. - Mazur, James E; Kahlbaugh, Patricia E (Journal of Comparative Psychology, 2012)
In the Monty Hall dilemma, an individual chooses between three options, only one of which will deliver a prize. After the initial choice, one of the nonchosen options is revealed as a losing option, and the individual can choose to stay with the original choice or switch to the other remaining option. Previous studies have found that most adults stay with their initial choice, although the chances of winning are 2/3 for switching and 1/3 for staying. Pigeons, college students, and preschool children were given many trials on this task to examine how their choices might change with experience. The college students began to switch on a majority of trials much sooner than the pigeons, contrary to the findings by Herbranson and Schroeder (2010) that pigeons perform better than people on this task. In all three groups, some individuals approximated the optimal strategy of switching on every trial, but most did not. Many of the preschoolers immediately showed a pattern of always switching or always staying and continued this pattern throughout the experiment. In a condition where the probability of winning was 90% after a switch, all college students and all but one pigeon learned to switch on nearly every trial. The results suggest that one main impediment to learning the optimal strategy in the Monty Hall task, even after repeated trials, is the difficulty in discriminating the different reinforcement probabilities for switching versus staying.
Keywords: *Choice Behavior; *Columbidae; Adolescent; Animals; Child, Preschool; Choice Behavior; College students; Columbidae; Female; Games, Experimental; Humans; Male; Monty hall dilemma; Pigeons; Preschool children; Probability; Reinforcement Schedule; Reinforcement probability; Reward; Students; Students/px [Psychology]; Young Adult; adolescent; adult; animal; article; decision making; dept.psy; female; game; human; male; pigeons and doves; preschool child; probability; psychological aspect; reinforcement; reward; student

What lexical decision and naming tell us about reading - Katz, Leonard; Brancazio, Larry; Irwin, Julia; Katz, Stephen; Magnuson, James; Whalen, D. H. (Reading and Writing, 2012)
The lexical decision (LD) and naming (NAM) tasks are ubiquitous paradigms that employ printed word identification. They are major tools for investigating how factors like morphology, semantic information, lexical neighborhood and others affect identification. Although use of the tasks is widespread, there has been little research into how performance in LD or NAM relates to reading ability, a deficiency that limits the translation of research with these tasks to the understanding of individual differences in reading. The present research was designed to provide a link from LD and NAM to the specific variables that characterize reading ability (e.g., decoding, sight word recognition, fluency, vocabulary, and comprehension) as well as to important reading-related abilities (phonological awareness and rapid naming). We studied 99 adults with a wide range of reading abilities. LD and NAM strongly predicted individual differences in word identification, less strongly predicted vocabulary size and did not predict comprehension. Fluency was predicted but with differences that depended on the way fluency was defined. Finally, although the tasks did not predict individual differences in rapid naming or phonological awareness, the failures nevertheless assisted in understanding the cognitive mechanisms behind these reading-related abilities. The results demonstrate that LD and NAM are important tools for the study of individual differences in reading.
Keywords: Lexical decision; Naming; RT; Reading ability; dept.hls; dept.psy; peer-reviewed

Cognitive-affective styles associated with position on war - Abe, Jo Ann A. (Journal of Language and Social Psychology, 2012)
This study examined cognitive-affective styles associated with position on the Iraq war by analyzing responses posted on an online discussion forum using a computerized text-analysis program (Linguistic Inquiry and Word Count). Overall, the results were consistent with those obtained in narrative-coding studies. The pro-war group was associated with an external focus and a simplistic style of information processing. The anti-war group was associated with an internal focus and high levels of cognitive processing and negative emotion words. The “neither” group scored the highest on cognitive complexity and positive emotion words, and it was also the most balanced in terms of internal and external focus.
Keywords: Linguistic Inquiry and Word Count (LIWC); affective style; attitudes toward Iraq War; cognitive style; dept.psy; peer-reviewed

Eye movement dynamics and cognitive self-organization in typical and atypical development - Mirman, Daniel; Irwin, Julia R.; Stephen, Damian G. (Cognitive Neurodynamics, 2012)
This study analyzed distributions of Euclidean displacements in gaze (i.e. “gaze steps”) to evaluate the degree of componential cognitive constraints on audio-visual speech perception tasks. Children performing these tasks exhibited distributions of gaze steps that were closest to power-law or lognormal distributions, suggesting a multiplicatively interactive, flexible, self-organizing cognitive system rather than a component-dominant stipulated cognitive structure. Younger children and children diagnosed with an autism spectrum disorder (ASD) exhibited distributions that were closer to power-law than lognormal, indicating a reduced degree of self-organized structure. The relative goodness of lognormal fit was also a significant predictor of ASD, suggesting that this type of analysis may point towards a promising diagnostic tool. These results lend further support to an interaction-dominant framework that casts cognitive processing and development in terms of self-organization instead of fixed components and show that these analytical methods are sensitive to important developmental and neuropsychological differences.
Keywords: Autism; Development; Eye movements; Interaction-dominance; Self-organization; article; autism; cognition; dept.psy; eye movement; human; neuropsychology; speech perception

Teaching professionals to detect deception: the efficacy of a brief training workshop - Colwell, Lori H.; Colwell, Kevin; Hiscock-Anisman, Cheryl; Hartwig, Maria; Cole, Lindsey D.; Werdin, Kathryn; Youschak, Kimberly E. (Journal of Forensic Psychology Practice, 2012)
Despite the importance of credibility assessments in forensic settings, research shows that forensic professionals are mediocre at this task. This study tested the efficacy of a 2.5-hour training workshop on Assessment Criteria Indicative of Deception (ACID), a system of investigative interviewing and credibility assessment using verbal content analysis, in a sample of 99 forensic professionals at a maximum-security forensic hospital in the United States. Accuracy in detecting deception was assessed before and after training via written transcripts. Results showed that training improved participants' accuracy, with accuracy rates increasing from 61% to 70%. Implications of the findings and recommendations for future research are discussed.
Keywords: United States; accuracy; adult; article; assessment criterion indicative of deception; clinical assessment tool; deception; deception detection; dept.psy; female; hospital; human; male; nursing staff; psychiatrist; psychologist; registered nurse; social worker; training; verbal cues; vocational education; workshop

A latent class analysis of DSM-IV alcohol use disorder criteria and binge drinking in undergraduates - Beseler, Cheryl L.; Taylor, Laura A.; Kraemer, Deborah T.; Leeman, Robert F. (Alcoholism-Clinical and Experimental Research, 2012)
Background: Adolescent and adult samples have shown that the Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) abuse and dependence criteria lie on a continuum of alcohol problem severity, but information on criteria functioning in college students is lacking. Prior factor analyses in a college sample (Beseler et al., 2010) indicated that a 2-factor solution fit the data better than a single-factor solution after a binge drinking criterion was included. The second dimension may indicate a clustering of criteria related to excessive alcohol use in this college sample. Methods: The present study was an analysis of data from an anonymous, online survey of undergraduates (N = 361) that included items pertaining to the DSM-IV alcohol use disorder (AUD) diagnostic criteria and binge drinking. Latent class analysis (LCA) was used to determine whether the criteria best fit a categorical model, with and without a binge drinking criterion. Results: In an LCA including the AUD criteria only, a 3-class solution was the best fit. Binge drinking worsened the fit of the models. The largest class (class 1, n = 217) primarily endorsed tolerance (18.4%); none were alcohol dependent. The middle class (class 2, n = 114) endorsed primarily tolerance (81.6%) and drinking more than intended (74.6%); 34.2% met criteria for dependence. The smallest class (class 3, n = 30) endorsed all criteria with high probabilities (30 to 100%); all met criteria for dependence. Alcohol consumption patterns did not differ significantly between classes 2 and 3. Class 3 was characterized by higher levels on several variables thought to predict risk of alcohol-related problems (e. g., enhancement motives for drinking, impulsivity, and aggression). Conclusions: Two classes of heavy-drinking college students were identified, one of which appeared to be at higher risk than the other. The highest risk group may be less likely to “mature out” of high-risk drinking after college.
Keywords: Adolescent; Alcohol Typology; Alcohol Use Disorders; Alcohol-Related Disorders; College Students; Cross-Sectional Studies; Diagnostic and Statistical Manual of Mental Disorders; Ethanol; Female; Health Surveys; Humans; Impulsivity; Latent Class Analysis; Male; Risk Factors; Students; Universities; Young Adult; adult; aggression; alcohol consumption; alcohol use disorder criterion; alcoholism; article; binge drinking; clinical assessment tool; college student; controlled study; dept.psy; diagnostic and statistical manual of mental disorders; disease severity; drinking behavior; female; human; impulsiveness; major clinical study; male; motivation; priority journal; psychological model; undergraduate student

Scaffolding: Relationships among online quiz parameters and classroom exam scores - Anthis, Kristine; Adams, Lisa (Teaching of Psychology, 2012)
The current study examined relationships among online quiz parameters and students' classroom exam scores. The authors analyzed data from undergraduate courses across four semesters. The results revealed that regardless of the different parameters set for the online quizzes, the number of attempts that students made on quizzes was unrelated to their classroom exam scores, yet the amount of time they spent on quizzes was correlated negatively with their classroom exam scores. The results also revealed that students' scores on the online quizzes predicted their classroom exam scores, above and beyond the number of attempts, length of time allowed on quizzes, as well as their SAT Reading and SAT Math scores. The implications of these results are discussed subsequently. Future researchers may wish to provide empirical evidence on how not counting all of students' online quiz scores toward their final grade may influence students' quiz performance, given the anxiety that time limits can foster.
Keywords: attempts; dept.psy; exam scores; online quizzes; time limits

Effects of pre-trial response requirements on self-control choices by rats and pigeons. - Mazur, James E (Journal of the experimental analysis of behavior, 2012)
Parallel experiments with rats and pigeons examined whether the size of a pre-trial ratio requirement would affect choices in a self-control situation. In different conditions, either 1 response or 40 responses were required before each trial. In the first half of each experiment, an adjusting-ratio schedule was used, in which subjects could choose a fixed-ratio schedule leading to a small reinforcer, or an adjusting-ratio schedule leading to a larger reinforcer. The size of the adjusting ratio requirement was increased and decreased over trials based on the subject's responses, in order to estimate an indifference point-a ratio at which the two alternatives were chosen about equally often. The second half of each experiment used an adjusting-delay procedure-fixed and adjusting delays to the small and large reinforcers were used instead of ratio requirements. In some conditions, particularly with the reinforcer delays, the rats had consistently longer adjusting delays with the larger pre-trial ratios, reflecting a greater tendency to choose the larger, delayed reinforcer when more responding was required to reach the choice point. No consistent effects of the pre-trial ratio were found for the pigeons in any of the conditions. These results may indicate that rats are more sensitive to the long-term reinforcement rates of the two alternatives, or they may result from a shallower temporal discounting rate for rats than for pigeons, a difference that has been observed in previous studies.
Keywords: *Choice Behavior; *Conditioning, Operant; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning, Operant; Long Evans rat; Male; Rats; Rats, Long-Evans; Reinforcement Schedule; animal; article; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; pigeons and doves; rat; reinforcement

Positive emotions, emotional intelligence, and successful experiential learning - Abe, Jo Ann A. (Personality and Individual Differences, 2011)
This study explored the role that positive emotions and emotional intelligence play in experiential learning. Students' field practicum journals were analyzed using the Linguistic Inquiry and Word Count Program (LIWC) and a measure of emotional intelligence was obtained using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT). Positive emotion words were robustly associated with almost all dimensions of supervisors' ratings of students' performance, but showed weak associations with students' ratings of perceived benefits associated with their practicum experiences. Overall El scores were correlated with several of the supervisor rating items and the Facilitating Thought and Managing Emotions subscales of the El were robustly correlated with many of the student rating items. This study thus yielded a more differentiated view of the role of positive emotions and emotional intelligence in adaptive functioning and underscored the importance of using multiple informants to assess a complex construct such as successful experiential learning. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Emotional intelligence; Experiential learning; LIWC; MSCEIT; Positive emotions; dept.psy

Functional activation for imitation of seen and heard speech - Irwin, Julia R.; Frost, Stephen J.; Mencl, W. Einar; Chen, Helen; Fowler, Carol A. (Journal of Neurolinguistics, 2011)
This study examined fMRI activation when perceivers either passively observed or observed and imitated matched or mismatched audiovisual (”McGurk”) speech stimuli. Greater activation was observed in the inferior frontal gyrus (IFG) overall for imitation than for perception of audiovisual speech and for imitation of the McGurk-type mismatched stimuli than matched audiovisual stimuli. This unique activation in the IFG during imitation of incongruent audiovisual speech may reflect activation associated with direct matching of incongruent auditory and visual stimuli or conflict between category responses. This study provides novel data about the underlying neurobiology of imitation and integration of AV speech. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Audiovisual; FMRI; Imitation; McGurk effect; Speech perception; Speech production; adult; article; auditory stimulation; brain function; brain region; controlled study; dept.psy; female; functional magnetic resonance imaging; human; human experiment; inferior frontal gyrus; male; priority journal; speech discrimination; speech perception; superior temporal gyrus; task performance; visual stimulation

Effects of neurofibromatosis type 1 on children's development - Haynes, Norris M.; Kirwan, Jacqueline R.; McCrohan, Kelly (Social Work in Public Health, 2011)
In-depth study of the human genome holds the potential to provide needed focus on genetic disorders that affect hundreds of thousands of children and significantly affect their development. Neurofibromatosis Type-1 (NF-1) is one of the most common genetic disorders that affect neurological, cognitive, social, and physical development. NF-1 affects all racial groups and both genders equally. NF-1 occurs in about 1 in 2,500 to 3,300 individuals in the population. The incidence rate at birth is about 0.0004 births in the United States and is growing in prevalence. Children with NF-1 experience a range of psychomotor and cognitive impairments that affect the quality of their social lives and their learning and academic achievements. Interventions to address the psychosocial and educational needs of children with NF-1 include a range of social and academic support services, which are most effective when they are comprehensive, involve a multidisciplinary team of educational and health experts, and include a focus on supporting and empowering family members to be effective caregivers. Efforts to address the needs of children with NF-1 and to provide adequate support to their families have significant policy implications for local, state, and federal officials.
Keywords: *Child Development; *Genome, Human; *Neurofibromatosis 1/px [Psychology]; *School Health Services; Adolescent; Adult; Aged; Child; Child Development; Child Welfare; Child, Preschool; Emotions; Female; Genome, Human; Humans; Infant; Infant, Newborn; Male; Middle Aged; Neurofibromatosis; Neurofibromatosis 1; Neurofibromatosis 1/di [Diagnosis]; Neurofibromatosis 1/ep [Epidemiology]; Neurofibromatosis 1/ge [Genetics]; Patient Education as Topic; Power (Psychology); Power, Psychological; Prevalence; Risk Factors; School Health Services; Social Change; Social Work; United States; United States/ep [Epidemiology]; Young Adult; adolescent; adult; aged; article; behavior; birth rate; child; child development; child health; child welfare; cognition; dept.psy; disease incidence; disease prevalence; emotion; family empowerment; female; genetics; genome; heritability; human; human genome; infant; male; mental health; middle aged; neurofibromatosis; newborn; patient education; peer-reviewed; preschool child; prevalence; psychological aspect; psychology; risk factor; school health service; school psychologists; school-based interventions; social and emotional development; social change; social policy; social work

Augmenting acid with affective details to assess credibility - Ansarra, Ryan; Colwell, Kevin; Hiscock-Anisman, Cheryl; Hines, Amber; Fleck, Roland; Cole, Lindsey; Belarde, Delyana (European Journal of Psychology Applied to Legal Context, 2011)
There is a need within the criminal justice systems of many countries to create a valid and applicable system of investigative interviewing and credibility assessment. The present study assesses the general validity one such system, called Assessment Criteria Indicative of Deception (ACID). ACID comprises interviewing strategies that facilitate the detection of deception and content criteria that highlight differences in verbal behavior. Sixty university undergraduates performed a staged theft under time pressure and with incentives designed to increase external validity. The participants were interviewed and assessed using the ACID procedure. Half of them were instructed to answer honestly and the other half to deny his/her participation in the theft. Results showed that honest statements were longer, more vividly detailed, and more spontaneously structured than deceptive statements. Also, the addition of affective details as a dependent measure significantly improved the ACID system. Overall, 48 of 60 statements were accurately classified (26 of 30 honest statements and 22 of 30 deceptive statements). The ACID procedure was effective and benefited from the addition of affective details. The strengths and weaknesses of this study are discussed in light of basic research into deception and potential forensic application.
Keywords: Content analysis; Credibility assessment; Detecting deception; Investigative interviewing; Testimony; dept.psy; ⛔ No DOI found

Changes in alan greenspan's language use across the economic cycle: A text analysis of his testimonies and speeches - Abe, Jo Ann A. (Journal of Language and Social Psychology, 2011)
This study examined changes in Alan Greenspan's language use across the economic cycle by analyzing his testimonies and speeches using the Linguistic Inquiry and Word Count Program (LIWC), which is a widely used text analysis program. Consistent with expectations, Greenspan showed an increase in the composite measure of psychological distancing as well as a decline in the measure of cognitive complexity between the economic expansion and downturn periods. Interestingly, these patterns of changes became more pronounced during the purported economic recovery period. In contrast to the measures of psychological distancing and cognitive complexity, the measure of emotionality remained relatively stable across the economic cycle.
Keywords: Greenspan; LIWC; cognitive complexity; computerized text analysis; dept.psy; peer-reviewed; psychological distancing

Effect of night smoking, sleep disturbance, and their co-occurrence on smoking outcomes - Peters, Erica N.; Fucito, Lisa M.; Novosad, Claire; Toll, Benjamin A.; O'Malley, Stephanie S. (Psychology of Addictive Behaviors, 2011)
Recent evidence suggests that smoking during the night is an indicator of nicotine dependence and predicts smoking cessation failure. Night smokers are likely to experience disturbance to their sleep cycle when they wake to smoke, but we are not aware of the prevalence of night smokers' self-reported sleep disturbance. Because sleep disturbance also predicts smoking cessation failure, we examined how the pre-cessation risk factors of night smoking and sleep disturbance, and their co-occurrence, predict smoking cessation failure in a 6-week double-blind randomized controlled trial examining whether naltrexone augments the efficacy of the nicotine patch (O'Malley et al., 2006). Smokers (N = 385) completed the Pittsburgh Sleep Quality Index (Buysse, Reynolds, Monk, Berman, & Kupfer, 1989) and a single item of waking at night to smoke pre-cessation. Smoking status was determined at weeks 1, 6, 24, and 48 weeks after quitting. The two main findings were: (a) night smokers reported significantly greater sleep disturbance than nonnight smokers; and (b) smokers with co-occurring night smoking and sleep disturbance experienced significantly greater risk for smoking than smokers with neither risk factor. Results suggest that individuals who both wake during the night to smoke and report clinically-significant sleep disturbance represent a high-risk group of smokers. Future smoking cessation treatment might incorporate strategies related to managing these smokers' sleep habits and physiological dependence on nicotine in order to bolster their cessation outcomes.
Keywords: Adult; Double-Blind Method; Female; Humans; Male; Middle Aged; Night smoking; Outcome predictors; Pittsburgh Sleep Quality Index; Prevalence; Self Report; Sleep Disorders; Sleep disturbance; Smoking; Smoking Cessation; Smoking cessation; Tobacco Use Disorder; Treatment Outcome; adult; article; cigarette smoking; comorbidity; controlled study; dept.psy; double blind procedure; drug dose comparison; female; high risk patient; human; major clinical study; male; naltrexone; named inventories, questionnaires and rating scales; nicotine patch; night; placebo; prediction; randomized controlled trial; risk factor; sleep disorder; smoking cessation; smoking habit; tobacco dependence; treatment failure; wakefulness

Effects of time between trials on rats' and pigeons' choices with probabilistic delayed reinforcers. - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2011)
Parallel experiments with rats and pigeons examined reasons for previous findings that in choices with probabilistic delayed reinforcers, rats' choices were affected by the time between trials whereas pigeons' choices were not. In both experiments, the animals chose between a standard alternative and an adjusting alternative. A choice of the standard alternative led to a short delay (1 s or 3 s), and then food might or might not be delivered. If food was not delivered, there was an "interlink interval," and then the animal was forced to continue to select the standard alternative until food was delivered. A choice of the adjusting alternative always led to food after a delay that was systematically increased and decreased over trials to estimate an indifference point--a delay at which the two alternatives were chosen about equally often. Under these conditions, the indifference points for both rats and pigeons increased as the interlink interval increased from 0 s to 20 s, indicating decreased preference for the probabilistic reinforcer with longer time between trials. The indifference points from both rats and pigeons were well described by the hyperbolic-decay model. In the last phase of each experiment, the animals were not forced to continue selecting the standard alternative if food was not delivered. Under these conditions, rats' choices were affected by the time between trials whereas pigeons' choices were not, replicating results of previous studies. The differences between the behavior of rats and pigeons appears to be the result of procedural details, not a fundamental difference in how these two species make choices with probabilistic delayed reinforcers.
Keywords: *Choice Behavior; *Memory, Short-Term; *Probability Learning; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning, Operant; Long Evans rat; Male; Memory, Short-Term; Motivation; Probability Learning; Psychomotor Performance; Rats; Rats, Long-Evans; Reinforcement Schedule; Species Specificity; Time Perception; animal; article; decision making; dept.psy; instrumental conditioning; learning; male; motivation; peer-reviewed; pigeons and doves; psychomotor performance; rat; reinforcement; short term memory; species difference; time perception

Is it the clicker, or is it the question? Untangling the effects of student response system use - Anthis, Kristine (Teaching of Psychology, 2011)
Previous research on the effectiveness of clickers has found their use to be positively associated with exam scores but not without methodological issues that hinder the conclusions that can be drawn. To address these limitations, the current studies isolated the effects of clickers from the effects of questions presented with clickers. Study 1 showed that students who did not use clickers to respond to questions but raised their hands performed better on exams than students who saw the same questions and responded with clickers. Study 2 found no relationship between clicker use and exam scores, which suggests that prior research claims about the effectiveness of clickers may have been premature given that clicker use was confounded with question use in those studies. Suggestions for future research are also provided.
Keywords: SRS; clickers; dept.psy; metacognition

Assessing feigned cognitive impairment in defendants hospitalized for competency restoration: further validation of the TOMI - Colwell, Lori H.; Colwell, Kevin (Journal of Forensic Psychology Practice, 2011)
Valid screens for feigned cognitive impairment are a fundamental component of any forensic assessment. The TOMI is a verbally administered, two-alternative forced-choice screen for feigned cognitive impairment in competence to stand trial (CST) evaluations. The present study provided further validation for the use of this tool in a sample of 82 forensic inpatients, the second investigation of the TOMI in a real-world, psycholegal context. Using three independent external criteria-the Test of Memory Malingering (TOMM) Trial 2 score, TOMM Retention Trial score, and a clinical treatment team decision-and these combined criteria-the Legal Knowledge scale (TOMI-L) evidenced high levels of sensitivity and specificity and excellent negative predictive power (NPP). The General Knowledge scale (TOMI-G) demonstrated poor sensitivity but high specificity and NPP. The authors discuss the utility of both scales in guiding and streamlining more thorough assessments of response styles in CST evaluations.
Keywords: Competency; Forensic assessment; Legal Knowledge scale; Malingering; Test of Malingered Incompetence; Twoalternative forced-choice; adult; analytic method; article; clinical assessment tool; clinical decision making; clinical treatment team decision; cognitive defect; competence; dept.psy; forensic medicine; human; legal aspect; major clinical study; male; psychological aspect; sensitivity and specificity; validation process

Can children with autism spectrum disorders “Hear” a speaking face? - Irwin, Julia; Tornatore, Lauren A; Brancazio, Lawrence; Whalen, D H (Child Development, 2011)
This study used eye-tracking methodology to assess audiovisual speech perception in 26 children ranging in age from 5 to 15 years, half with autism spectrum disorders (ASD) and half with typical development. Given the characteristic reduction in gaze to the faces of others in children with ASD, it was hypothesized that they would show reduced influence of visual information on heard speech. Responses were compared on a set of auditory, visual, and audiovisual speech perception tasks. Even when fixated on the face of the speaker, children with ASD were less visually influenced than typical development controls. This indicates fundamental differences in the processing of audiovisual speech in children with ASD, which may contribute to their language and communication impairments.
Keywords: Adolescent; Child; Child Development Disorders, Pervasive; Child, Preschool; Communication; Female; Humans; Language Development Disorders; Lipreading; Male; Pattern Recognition, Visual; Perceptual Masking; Reference Values; Speech Perception; Verbal Behavior; adolescent; article; autism; child; dept.hls; dept.psy; female; human; interpersonal communication; language disability; lip reading; male; pattern recognition; perception; preschool child; psychological aspect; reference value; speech perception; verbal behavior

Effects of playing wii on well-being in the elderly: physical activity, loneliness, and mood - Kahlbaugh, Patricia E; Sperandio, Amanda J; Carlson, Ashley L; Hauselt, Jerry (Activities, Adaptation & Aging, 2011)
Effects of compensatory strategies offered by Wii technology on physical activity, loneliness, and mood are investigated. Thirty-five individuals (M = 82 years) were randomly assigned to either playing Wii or watching television with a partner for 10 weeks. Physical activity, loneliness, mood, life satisfaction, and health were assessed. The elderly playing Wii had lower loneliness and a pattern of greater positive mood compared to the television group. No differences in life satisfaction or physical activity were found, but loneliness predicted positive mood, and positive mood predicted physical activity. This investigation points to the benefits of using Wii for well-being, particularly social connection and enjoyment. © 2011 Copyright Taylor and Francis Group, LLC.
Keywords: dept.psy; integrative game playing; loneliness; mood; older adult recreation; well-being

Distinguishing truthful from invented accounts using reality monitoring criteria - Memon, Amina; Fraser, Joanne; Colwell, Kevin; Odinot, Geralda; Mastroberardino, Serena (Legal and Criminological Psychology, 2010)
Purpose. Previous research has suggested that true and invented memories can be distinguished between using the reality monitoring criteria. Two different coding schemes were used to examine the correct classification of reports as truthful or deceptive on the basis of individual reality-monitoring (RM) criteria. Method. Drawing upon the RM framework the present experiment examined transcripts of verbal accounts of eyewitnesses to a staged event or made up details about the incident. The statements were elicited during a face-to-face cognitive interview (CI) and were analysed by coders trained in the identification of criteria indicative of self-experienced and invented accounts (referred to here as Version 1) and a similar coding method (referred to here as Version 2). Results. A distinction was made between `external memories' (affective, perceptual, and contextual details) and `internal' memories (cognitive operations). For Version 1, the results indicated a higher number of contextual and external details in the descriptions of experienced events and as is commonly found in the deception literature, truthful accounts were longer. For Version 2, temporal and auditory details were more frequent in true accounts. Contrary to prediction, there were also more references to cognitive operations in true accounts. Conclusions. Any forensic application of RM should consider how external factors (characteristics of the event, motivation to deceive, and questioning style) influence the presence of RM criteria.
Keywords: adult; article; coding; cognition; controlled study; dept.psy; female; human; interview; major clinical study; male; memory; monitoring; priority journal; questionnaire; reality monitoring; self concept; verbal communication; witness

Distributed versus exclusive preference in discrete-trial choice. - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 2010)
Two experiments on discrete-trial choice examined the conditions under which pigeons would exhibit exclusive preference for the better of two alternatives as opposed to distributed preference (making some choices for each alternative). In Experiment 1, pigeons chose between red and green response keys that delivered food after delays of different durations, and in Experiment 2 they chose between red and green keys that delivered food with different probabilities. Some conditions of Experiment 1 had fixed delays to food and other conditions had variable delays. In both experiments, exclusive or nearly exclusive preference for the better alternative was found in some conditions, but distributed preference was found in other conditions, especially in Experiment 2 when key location varied randomly over trials. The results were used to evaluate several different theories about discrete-trial choice. The results suggest that exclusive preference for one alternative is a frequent outcome in discrete-trial choice. When distributed preference does occur, it is not the result of inherent tendencies to sample alternatives or to match response percentages to the values of the alternatives. Rather, distributed preference may occur when two factors (such as reinforcer delay and position bias) compete for the control of choice, or when the consequences for the two alternatives are similar and difficult to discriminate.
Keywords: *Choice Behavior/ph [Physiology]; *Conditioning, Operant/ph [Physiology]; *Reinforcement Schedule; *Reinforcement, Psychology; Animals; Choice Behavior; Columba; Columbidae; Conditioning, Operant; Discrete-trial choice; Exclusive preference; Male; Pigeons; Probability; Reaction Time; Reaction Time/ph [Physiology]; Reinforcement (Psychology); Reinforcement Schedule; Reinforcer delay; Time Factors; animal; article; decision making; dept.psy; instrumental conditioning; male; physiology; pigeons and doves; probability; reaction time; reinforcement; time

Impression management strategies of deceivers and honest reporters in an investigative interview - Hines, Amber; Colwell, Kevin; Hiscock-Anisman, Cheryl; Garrett, Erika; Ansarra, Ryan; Montalvo, Larissa (European Journal of Psychology Applied to Legal Context, 2010)
Understanding the subjective experience of respondents attempting to convince an investigator will enhance our theoretical knowledge of deception and improve assessment techniques. Discrepancies between respondents' understanding and actual credibility criteria are especially important. Sixty-six participants engaged in a small crime, and were interviewed following a week's preparation. All were provided incentive for convincing the interviewer of the veracity of their statement. Thirty-two were honestly reporting the theft, and thirty-four were responding to avoid being found guilty. After a Reality Interview (a derivative of the Cognitive Interview), participants were asked to describe what was important in convincing the interviewer through open-ended and Liken-type questions. These strategies of impression management are presented here. The basic task of convincing appeared similar for both groups, with participants focused on providing clear and careful stories without contradictions rather than attempting to provide vivid and spontaneously-constructed statements. Deceivers attached more importance to: I) preparing in advance, 2) monitoring and controlling information, and 3) maintaining eye contact. Honest respondents were more concerned with providing correct peripheral detail. Importantly, both groups were reporting much more similarity than difference, and the strategies described are not likely to succeed against verbal content analysis.
Keywords: Credibility; Deception; Interrogation; Testimony; Verbal communication; dept.psy; ⛔ No DOI found

Seeing to hear? Patterns of gaze to speaking faces in children with autism spectrum disorders. - Irwin, Julia R; Brancazio, Lawrence (Frontiers in Psychology, 2014)
Using eye-tracking methodology, gaze to a speaking face was compared in a group of children with autism spectrum disorders (ASD) and a group with typical development (TD). Patterns of gaze were observed under three conditions: audiovisual (AV) speech in auditory noise, visual only speech and an AV non-face, non-speech control. Children with ASD looked less to the face of the speaker and fixated less on the speakers' mouth than TD controls. No differences in gaze were reported for the non-face, non-speech control task. Since the mouth holds much of the articulatory information available on the face, these findings suggest that children with ASD may have reduced access to critical linguistic information. This reduced access to visible articulatory information could be a contributor to the communication and language problems exhibited by children with ASD.
Keywords: Audiovisual speech perception; Autism spectrum disorders; Communication development; Eyetracking; Lipreading; Speech in noise; dept.hls; dept.hms; dept.psy; peer-reviewed

Development of an audiovisual speech perception app for children with autism spectrum disorders - Irwin, Julia; Preston, Jonathan; Brancazio, Lawrence; D'Angelo, Michael; Turcios, Jacqueline (Clinical Linguistics & Phonetics, 2015)
Perception of spoken language requires attention to acoustic as well as visible phonetic information. This article reviews the known differences in audiovisual speech perception in children with autism spectrum disorders (ASD) and specifies the need for interventions that address this construct. Elements of an audiovisual training program are described. This researcher-developed program delivered via an iPad app presents natural speech in the context of increasing noise, but supported with a speaking face. Children are cued to attend to visible articulatory information to assist in perception of the spoken words. Data from four children with ASD ages 8-10 are presented showing that the children improved their performance on an untrained auditory speech-in-noise task.
Keywords: Attention; Audiovisual Aids; Audiovisual app; Autism spectrum disorder; Child; Child Development Disorders, Pervasive; Comprehension; Humans; Lipreading; Male; Mobile Applications; Pattern Recognition, Visual; Phonetics; Semantics; Speech Perception; Speech perception; attention; audiovisual aid; child; comprehension; dept.cmd; dept.hls; dept.psy; human; lip reading; male; mobile application; pattern recognition; phonetics; psychology; semantics; speech perception

Neurophysiology of speech differences in childhood apraxia of speech - Preston, Jonathan L; Molfese, Peter J; Gumkowski, Nina; Sorcinelli, Andrea; Harwood, Vanessa; Irwin, Julia; Landi, Nicole (Developmental Neuropsychology, 2014)
Event-related potentials (ERPs) were recorded during a picture naming task of simple and complex words in children with typical speech and with childhood apraxia of speech (CAS). Results reveal reduced amplitude prior to speaking complex (multisyllabic) words relative to simple (monosyllabic) words for the CAS group over the right hemisphere during a time window thought to reflect phonological encoding of word forms. Group differences were also observed prior to production of spoken tokens regardless of word complexity during a time window just prior to speech onset (thought to reflect motor planning/programming). Results suggest differences in pre-speech neurolinguistic processes.
Keywords: Adolescent; Apraxias; Child; Evoked Potentials; Female; Humans; Linguistics; Male; Neurophysiology; Speech; adolescent; apraxia; article; child; comparative study; dept.cmd; dept.psy; evoked response; female; human; linguistics; male; neurophysiology; pathophysiology; physiology; speech

Child and Adolescent Development: A Social Justice Approach - Anthis, Kristine (Cognella, 2021)
Child and Adolescent Development: A Social Justice Approach features portraits of development at each stage interwoven with the findings of developmental science research on how inequitable resources and opportunities, which are influenced by social, economic, and political factors, can impact development. The text also presents findings on how such data can be used to reduce inequities for children and their families, thereby optimizing development and allowing individuals to reach their full potential no matter who they are. The text begins with a chapter that briefly describes the stages, domains, and patterns of child and adolescent development, as well as traditional and contemporary theories. Subsequent chapters provide insight into the research methods of developmental science and explain how epigenetic influences affect development. The book then progresses chronologically, discussing the physical, cognitive, and emotional changes that occur within each stage, guiding readers through a tapestry of development from conception through adolescence. Throughout, Pan & Zoom sections supply both big-picture and microscopic understandings of development, Tech & Media asides highlight the influences that technology and media can have on child and adolescent development, and Mentor Minutes provide readers with practical wisdom through interviews with diverse professionals working in the field. Featuring a timely and much-needed perspective on development, Child and Adolescent Development is an ideal resource for courses in psychology, education, counseling, human services, and social work.
Keywords: Child development; Youth development; SCSU Faculty Scholar Award; award_winner; dept.psy

Experimentally induced variation in neuroendocrine processes affects male reproductive behaviour, sperm characteristics and social interactions - Nugent, Bridget M.; Stiver, Kelly A.; Hofmann, Hans A.; Alonzo, Suzanne H. (Molecular Ecology, 2019)
While extensive research has focused on how social interactions evolve, the fitness consequences of the neuroendocrine mechanisms underlying these interactions have rarely been documented, especially in the wild. Here, we measure how the neuroendocrine mechanisms underlying male behaviour affect mating success and sperm competition in the ocellated wrasse (Symphodus ocellatus). In this species, males exhibit three alternative reproductive types. “Nesting males” provide parental care, defend territories and form cooperative associations with unrelated “satellites,” who cheat by sneaking fertilizations but help by reducing sperm competition from “sneakers” who do not cooperate or provide care. To measure the fitness consequences of the mechanisms underlying these social interactions, we used “phenotypic engineering” that involved administering an androgen receptor antagonist (flutamide) to wild, free-living fish. Nesting males treated with flutamide shifted their aggression from sneakers to satellite males and experienced decreased submissiveness by sneaker males (which correlated with decreased nesting male mating success). The preoptic area (POA), a region controlling male reproductive behaviours, exhibited dramatic down-regulation of androgen receptor (AR) and vasotocin 1a receptor (V1aR) mRNA following experimental manipulation of androgen signalling. We did not find a direct effect of the manipulation on male mating success, paternity or larval production. However, variation in neuroendocrine mechanisms generated by the experimental manipulation was significantly correlated with changes in behaviour and mating success: V1aR expression was negatively correlated with satellite-directed aggression, and expression of its ligand arginine vasotocin (AVT) was positively correlated with courtship and mating success, thus revealing the potential for sexual selection on these mechanisms. © 2018 John Wiley & Sons Ltd
Keywords: 11-ketotestosterone; Androgen Receptor Antagonists; Animals; Brain; Female; Flutamide; Male; Neurosecretory Systems; Perciformes; RNA, Messenger; Receptors, Androgen; Reproduction; Sexual Behavior, Animal; Social Behavior; Spermatozoa; Testosterone; alternative reproductive tactics; androgen receptor; androgen receptor antagonist; androgens; animal; brain; dept.psy; drug effect; female; flutamide; genetics; male; messenger RNA; metabolism; neuroendocrine; neuroendocrine system; peer-reviewed; physiology; reproduction; sexual behavior; sexual selection; social behavior; social behaviour; spermatozoon; teleosts; testosterone

Neuropeptide manipulation has behavioural and cascading fitness consequences in wild-living fish - Stiver, Kelly A.; Marsh-Rollo, Susan E.; Alonzo, Suzanne H. (Animal Behaviour, 2019)
Due to the difficulty of simultaneously assessing variation in individual physiology, behaviour and fitness, we often know little about the mechanistic basis of life-history trade-offs and fitness variation. It is similarly challenging to examine how physiological variation in one individual has cascading fitness consequences for others in the social environment. Using a wild-living fish (ocellated wrasse, Symphodus ocellatus), we manipulated a neuropeptide pathway associated with courtship, aggression and parental care in vertebrates (arginine vasotocin, AVT) and directly examined the behavioural and fitness consequences. Nesting males injected with the AVT antagonist increased their paternal care, resulting in increased hatching of offspring and increased reproductive success of all individuals that mated at his nest. By directly examining physiology, behaviour and reproductive success, we revealed how a small change in individual physiology has clear and direct fitness consequences for multiple individuals. © 2019 The Association for the Study of Animal Behaviour
Keywords: Symphodus ocellatus; Vertebrata; arginine vasotocin; behavioral response; dept.psy; fitness; fitness consequences; life history; nonapeptide; parental care; parental investment; paternal care; peer-reviewed; peptide; phenotype; phenotypic engineering; physiological manipulation; physiology; proximate mechanisms; reproductive cost; reproductive investment; reproductive success; trade-off; trade-offs; wild population

The efficacy of free-recall, cognitive load, and closed-ended questions when children are asked to falsely testify about a crime - Wyman, Joshua; Foster, Ida; Crossman, Angela; Colwell, Kevin; Talwar, Victoria (Applied Cognitive Psychology, 2019)
The current study evaluated the benefits of free-recall, cognitive load, and closed-ended questions on children's (ages 6 to 11; N = 147) true and false eyewitness disclosures. Children witnessed an experimenter find a stranger's wallet and were then asked to make a false denial, false accusation, true denial, or true accusation regarding an alleged theft. Overall, the free-recall question resulted in longer, more forthcoming and more detailed disclosures from older children and those who made a truthful accusation; however, children under the age of 9 and lie-tellers mostly relied on the closed-ended questions to discuss the theft. Although the cognitive load questions resulted in newly recalled information, there were no significant narrative differences between true and false statements on these questions. These findings suggest that forensic professionals should consider a child's developmental level, statement veracity, and disclosure-type (denial vs. accusation) when examining the efficacy of these commonly used questioning strategies.
Keywords: article; child; children; cognitive load; dept.psy; drug efficacy; eyewitness reports; false reports; female; free-recall; human; human experiment; major clinical study; male; narrative; peer-reviewed; recall; theft; witness

The language of wisdom understood through an analysis of wise quotes - DeFrank, Melanie; Bivona, Marissa; Chiaraluce, Brianna; Kahlbaugh, Patricia (Journal of Language and Social Psychology, 2019)
Wise quotes carry advice about how to navigate life's difficult decisions or feelings, allowing cultures to pass wisdom through generations. Qualities of wisdom have been identified by careful examination of wise individuals. Similarly, wise sayings and quotations can be analyzed and interpreted as emblematic of cultural beliefs about wisdom. The present research examines thematic and linguistic qualities of 157 wise quotes nominated as wise by 194 undergraduates. Thematic analysis of wise quotes centered on five dimensions of wisdom: Humor, Emotion, Review, Openness and Experience. Humor and Emotion were found to be the least represented while Review and Experience were the most represented. Linguistic analysis compared strong (n = 101) versus weak (n = 56) wise quotes and found that strong wise quotes were more linguistically complex and less likely to use the first-person pronouns. Analyzing the language of wisdom through quotes can provide additional insight into cultural representations of wisdom.
Keywords: adult; article; communicating wisdom; controlled study; dept.psy; female; human; human experiment; humor; language; major clinical study; male; peer-reviewed; quotes; text analysis; thematic analysis; wisdom

Tests of an indifference rule in variable-delay and double-reward choice procedures with humans - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2019)
Four hundred and fifty participants were recruited from Amazon Mechanical Turk across 3 experiments to test the predictions of a hyperbolic discounting equation in accounting for human choices involving variable delays or multiple rewards (Mazur, 1984, 1986). In Experiment 1, participants made hypothetical choices between 2 monetary alternatives, 1 consisting of a fixed delay and another consisting of 2 delays of equal probability (i.e., a variable-delay procedure). In Experiment 2, participants made hypothetical monetary choices between a single, immediate reward and 2 rewards, 1 immediate and 1 delayed (i.e., a double-reward procedure). Experiment 3 also used a double-reward procedure, but with 2 delayed rewards. Participants in all 3 experiments also completed a standard delay-discounting task. Finally, 3 reward amounts were tested in each type of task ($100, $1000, and $5000). In the double-reward conditions (Experiments 2 and 3), the results were in good qualitative and quantitative agreement with Mazur's model (1984, 1986). In contrast, when participants made choices involving variable delays (Experiment 1), there was relatively poor qualitative and quantitative agreement with this model. These results, along with our previous findings, suggest the structure of questions in hypothetical tasks with humans can be a strong determinant of the choice pattern.
Keywords: Adult; Choice Behavior; Delay Discounting; Female; Humans; Male; Models, Psychological; Probability; Reward; adult; choice; decision making; delay discounting; dept.psy; female; human; humans; hyperbolic discounting; male; mathematical model; peer-reviewed; probability; psychological model; reward

Using the reality interview improves the accuracy of the Criteria‐Based content analysis and reality monitoring - Bogaard, Glynis; Colwell, Kevin; Crans, Samantha (Applied Cognitive Psychology, 2019)
Active interviewing approaches can exploit the verbal differences between truthtellers and liars, thus improving detecting deception. One such method is the Reality Interview (RI) aimed to facilitate recall from truthtellers, while increasing the difficulty for liars. This study investigated whether the RI could improve the diagnostic accuracy of the Reality Monitoring and the Criteria-Based Content Analysis. Liars and truthtellers were either asked to freely recall an event or interviewed with the RI. As hypothesized, the RI improved the discriminability of Reality Monitoring and Criteria-Based Content Analysis over Free Recall. Honest responses were longer, and the RI increased the word count difference between honest and false statements. However, after correcting for word count, results were no longer significant, showing its importance for deception detection. Nonetheless, the RI increased verbal differences between truthtellers and liars, demonstrating that using the RI with verbal credibility assessment tools is a powerful combination for investigative interviewing. © 2019 The Authors Applied Cognitive Psychology Published by John Wiley & Sons Ltd.
Keywords: Criteria-Based Content Analysis; Reality Interview; Reality Monitoring; article; content analysis; credibility assessment; deception; deception detection; dept.psy; diagnostic accuracy; diagnostic test accuracy study; human; human experiment; interview; monitoring; peer-reviewed; recall

Social anxiety and employment interviews: does nonverbal feedback differentially predict cortisol and performance? - Budnick, Christopher J.; Anderson, Eden M.; Santuzzi, Alecia M.; Grippo, Angela J.; Matuszewich, Leslie (Anxiety Stress and Coping, 2019)
Background & Objectives: Interviewers often provide positive nonverbal feedback to reduce interviewees' anxiety. Socially anxious individuals typically harbor negative self-views discrepant with positive feedback. We examined whether nonverbal feedback and social anxiety jointly influence cortisol responses to, and performance during, interviews. Design: An experimental between-subjects design randomly assigned participants to feedback condition. Methods: Undergraduate students (N = 130) provided saliva and completed social anxiety, interview anxiety, and affective measures before a simulated interview. Following a standardized script, a confederate interviewer provided positive, ambiguous, or negative nonverbal feedback. Participants then provided saliva and completed self-focused attention and self-awareness measures. Confederate interviewers and an external rater evaluated participants' anxiety displays, assertive behavior, and performance. Results: Positive feedback decreased cortisol and improved performance for low social anxiety participants. Socially anxious participants exhibited higher cortisol but did not exhibit significant differences in performance after positive compared to negative feedback. Conclusions: Consistent with previous findings, positive feedback did not benefit socially anxious interviewees. Positive feedback increased physiological arousal relative to negative feedback but did not hinder performance among people high in social anxiety. These results provide novel information about the interactive influence of social anxiety and nonverbal interviewer feedback on arousal, self-focus, and interview performance.
Keywords: Anxiety; Arousal; Attention; Feedback; Female; Humans; Hydrocortisone; Interviews as Topic; Job Application; Male; Saliva; Social anxiety; anxiety; arousal; attention; chemistry; controlled study; cortisol; dept.psy; feedback system; female; human; hydrocortisone; interview; interview anxiety; interviews; job finding; male; pathophysiology; peer-reviewed; psychology; randomized controlled trial; saliva; self-verification

Restraint stress exacerbates cell degeneration induced by acute binge ethanol in the adolescent, but not in the adult or middle-aged, brain - Fernandez, Macarena Soledad; de Olmos, Soledad; Nizhnikov, Michael E; Pautassi, Ricardo Marcos (Behavioural brain research, 2019)
Restraint stress (RS) induces neurotoxicity in the hippocampus, yet most of the studies have employed protracted RS (i.e., = 21 days). Binge ethanol can induce brain toxicity, an effect affected by age. It could be postulated that RS may facilitate ethanol-induced neurotoxicity, perhaps to a greater extent in adolescent vs. older subjects. We analyzed whether adolescent, adult or middle-aged male rats exposed to five episodes of RS followed, 72h later, by binge ethanol (i.e., two administrations of 2.5 g/kg ethanol) exhibited hippocampal neurotoxicity. Adolescents, but not adult or middle-aged rats, exhibited sensitivity to the neurotoxic effects of ethanol at dorsal CA2, ventral CA3 and ventral DG, and a neurotoxic effect of stress at dorsal CA1. Moreover, the combination of ethanol and stress exerted a synergistic effect upon cell degeneration at ventral CA1 and CA2, which was restricted to adolescents. Ethanol also increased cell degeneration, irrespective of age or stress, in dorsal CA3 and in dorsal DG; and ethanol and stress had, across all ages, a synergistic effect upon cell degeneration at the dorsal CA1. The greater neurotoxic response of adolescents to ethanol, stress, or ethanol+stress can put them at risk for the development of alcohol problems. Copyright © 2019 Elsevier B.V. All rights reserved.
Keywords: *Age Factors; *Binge Drinking/pp [Physiopathology]; *Ethanol/ae [Adverse Effects]; Adolescent; Adult rats; Age Factors; Animals; Article; Binge Drinking; Binge Drinking/me [Metabolism]; Brain; Brain/de [Drug Effects]; Dentate Gyrus; Dentate Gyrus/de [Drug Effects]; Ethanol; Ethanol/pd [Pharmacology]; Hippocampus; Hippocampus/de [Drug Effects]; Male; Middle-Aged rats; Neurotoxicity; Rats; Rats, Wistar; Restraint, Physical; Wistar rat; adolescent; adult; adult animal; age; alcohol; animal; animal behavior; animal cell; animal experiment; animal model; animal tissue; binge drinking; brain; controlled study; dentate gyrus; dept.psy; dorsal hippocampus; drinking behavior; drug effect; exercise; hippocampal CA1 region; hippocampal CA2 region; hippocampal CA3 region; hippocampus; immobilization stress; male; metabolism; middle aged; nerve cell degeneration; neurotoxicity; nonhuman; pathophysiology; peer-reviewed; priority journal; rat; sensitivity analysis; underage drinking; ventral dentate gyrus; ventral hippocampus

Offspring of male rats exposed to binge alcohol exhibit heightened ethanol intake at infancy and alterations in T-maze performance. - Hollander, Jessica; McNivens, Megan; Pautassi, Ricardo M; Nizhnikov, Michael E (Alcohol, 2019)
Alcohol use is associated with a variety of negative consequences, including heightened likelihood of cognitive impairment, proclivity to alcohol use disorders (AUD), and alterations in the drinker's offspring. Children and rodents exposed to alcohol during pregnancy, or those whose fathers consumed alcohol prior to mating, often exhibit neurodevelopmental, physiological, and behavioral deficits. The present study assessed cognitive function and alcohol intake in male and female rats that were offspring of alcohol-exposed fathers. Adult male rats were exposed to alcohol or vehicle (0.0 or 2.0 g/kg, respectively; twice daily for 2 days followed by a rest day, for a total of eight alcohol or vehicle exposure days), or were left untreated and then mated with non-manipulated females. The offspring were assessed for alcohol intake, via intraoral infusion, followed by cognitive assessment via an alternating T-maze task. The results indicated that paternal ethanol exposure, prior to breeding, resulted in offspring that consumed significantly more ethanol than vehicle or untreated controls. Furthermore, the offspring of alcohol-exposed fathers exhibited a significant failure to initiate and complete the T-maze performance tests. Although, when they did engage in the tests they performed at the level of controls (i.e., 80% correct). The present results add to a growing body of literature suggesting that paternal pre-conception alcohol exposure can have deleterious effects on the offspring. Copyright © 2018 Elsevier Inc. All rights reserved.
Keywords: *Alcohol Drinking/px [Psychology]; *Binge Drinking/px [Psychology]; *Fathers/px [Psychology]; *Maze Learning/de [Drug Effects]; *Prenatal Exposure Delayed Effects/px [Psychology]; Alcohol Drinking; Alcohol intake; Animals; Article; Binge Drinking; Fathers; Female; Male; Maze Learning; Paternal alcohol exposure; Pregnancy; Prenatal Exposure Delayed Effects; Rats; T-maze; T-maze test; adult; alcohol; alcohol consumption; animal; animal experiment; binge drinking; cognition; controlled study; dept.psy; drinking behavior; drug effect; father; female; male; maze test; nonhuman; paternal exposure; peer-reviewed; pregnancy; prenatal exposure; psychology; rat

The fear of missing out at work: Examining costs and benefits to employee health and motivation - Budnick, Christopher J.; Rogers, Arielle P.; Barber, Larissa K. (Computers in Human Behavior, 2020)
The popular business media argues that the “fear of missing out” (FoMO) on work-related opportunities harms employees’ health and performance. Yet, these claims rely on the study of FoMO in college students in non-work contexts. Therefore, we explored workplace FoMO among employees across three studies. We first developed a measure and provided validation evidence for workplace FoMO among diverse employees (N = 324; Study 1) and MBA students (N = 223; Study 2). Using a third large employee sample (N = 300; Study 3), we tested whether workplace FoMO predicted health (i.e., work burnout and work well-being) and motivational outcomes (i.e., message-checking behaviors and work engagement). We also examined whether family-supportive organizational perceptions (FSOP) moderated these relationships. Results indicated that workplace FoMO is a distinct construct from other measures, including general FoMO. Workplace FoMO also predicted work burnout and message checking behavior, but not work well-being. Lower levels of FSOP strengthened the positive relationship between workplace FoMO and message checking behavior, but also produced a positive relationship between workplace FoMO and work well-being. Overall, FoMO appears to be relevant to the work context and predicts both employee well-being and behavior outcomes. © 2019 Elsevier Ltd
Keywords: Behavioral research; College students; Costs and benefits; Employee health; Fear of missing out; Health; Job satisfaction; Motivation; Students; Technology use; Technology use at work; Well being; Work engagements; Work-related; article; burnout; controlled study; dept.psy; fear of missing out; human; major clinical study; motivation; peer-reviewed; perception; wellbeing; work engagement

Language choice matters: when profanity affects how people are judged - DeFrank, Melanie; Kahlbaugh, Patricia E (Journal of Language and Social Psychology, 2019)
Swearing is prevalent in our society, but the influence of such language choices on judgments of others is not well understood. This study examines how the composition of conversational dyads, speaker's gender, and use of profanity influence impressions. Participants (N = 138) were randomly assigned to read two conversations and rate target speakers (one male, one female). The conversations had neither, one, or both speakers using profanity and consisted of same- or mixed-gender dyads. The result is a 2 (target speaker, male/female) x 2 (dyad composition) x 3 (profanity) mixed design with speaker gender as the repeated measure. Speakers using profanity had poorer impression ratings on several variables, including overall impression, intelligence, and trustworthiness. Speakers swearing in mixed-gender dyads were rated as less sociable, and males swearing in mixed-gender dyads were rated as more offensive. Language choices matter, and more research is needed to understand the unconscious biases held against those who use profanity.
Keywords: adult; article; controlled study; conversation; dept.psy; ego development; female; gender; human; human experiment; impression formation; intelligence; language; major clinical study; male; peer-reviewed; profanity; randomized controlled trial

A comparison of different investigative interviewing techniques in generating differential recall enhancement and detecting deception - De Rosa, Jacob; Hiscockanisman, Cheryl; Blythe, Adam; Bogaard, Glynis; Hally, Ashley; Colwell, Kevin (Journal of Investigative Psychology and Offender Profiling, 2019)
This study compared the Stepwise Interview, Cognitive Interview, and Reality Interview in detecting deception with inmates. The dependent measures were the amount of unique details provided during the free narrative and mnemonics and the number of words provided during the free narrative and mnemonics of each interview. The Stepwise Interview generated 58.3% accuracy, the Cognitive Interview generated 70.0% accuracy, and the Reality Interview generated 93.3% accuracy. The different tasks of these interviews increased the differences between honest and deceptive statements and therefore, increased the accuracy in detection of deception. Differential recall enhancement is used to explain the findings.
Keywords: credibility assessment; dept.psy; detecting deception; investigative interviewing; peer-reviewed

Does eyewitness and interviewer gender influence children’s reports? An experimental analysis of eyewitness and interviewer gender on children’s testimony - Foster, Ida; Wyman, Joshua; Tong, Donia; Colwell, Kevin; Talwar, Victoria (Psychiatry, Psychology and Law, 2019)
This study examines how children's age, gender and interviewer gender affected children's testimony after witnessing a theft. Children (N=127, age = 6-11 years) witnessed an experimenter (E1) find money, which he/she may/may not have taken. E1 then asked the children to falsely deny that the theft occurred, falsely accuse E1 of taking the money, or tell the truth when interviewed by a second experimenter. Falsely denying or falsely accusing influenced children's forthcomingness and quality of their testimony. When accusing, boys were significantly more willing than girls to disclose about the theft earlier and without being asked directly. When truthfully accusing, children gave lengthier testimony to same-gendered adults. When denying, children were significantly more willing to disclose the theft earlier to male interviewers than to females. As children aged, they were significantly less likely to lie, more likely to disclose earlier when accusing, and give lengthier and more consistent testimony.
Keywords: adult; article; child; children; dept.psy; disclosures; false accusations; false denials; female; gender; girl; human; interviewer gender; lying; major clinical study; male; money; peer-reviewed; preschool child; theft; witness

Audiovisual speech perception in children with autism spectrum disorders - Irwin, Julia R.; Avery, T; Kleinman, D; Landi, N (ICA 2019 Aachen, 2019)
In face-to-face conversation, when a speaker talks, the outcome of their speech can both be heard (audio) and seen (visual). We employed a novel visual phonemic restoration paradigm to assess neural signatures (event related potentials [ERPs]) of audiovisual processing in typically developing children and in children with ASD. During EEG recording, two types of auditory stimuli were alternately presented with video of a speaker saying the consonant-vowel syllable /ba/: 1) a synthesized consonant-vowel syllable /ba/ or 2) a synthesized syllable derived from /ba/ in which auditory cues for the consonant are substantially weakened, such that it sounds more like /a/. The auditory stimuli are easily discriminable, however, in the context of a visual /ba/, the auditory /a/ is typically perceived as /ba/, producing a visual phonemic restoration. In an ERP context, we have shown that this restoration leads to an attenuated phoneme discrimination response in an active task in typical adults and children. To explore the hypothesis that children with autism spectrum disorder (ASD) have atypical AV speech integration under pre-attentive processing conditions, we tested whether children with ASD would show a reduction in this restoration effect under passive listening conditions. Indeed, in this task, children with ASD showed a large /ba/-/a/ discrimination response, even in the presence of a speaker producing /ba/, suggesting reduced influence of visual speech. © 2019 Proceedings of the International Congress on Acoustics. All rights reserved.
Keywords: Audiovisual; Autism; Phonemic Restoration; Speech; dept.psy

Personality and political preferences: the 2016 U.S. presidential election - Abe, Jo Ann A (Journal of Research in Personality, 2018)
This study examined whether personality variables would account for political preferences during the 2016 U.S. Presidential Election using a demographically diverse sample of participants (N = 897). Study A revealed participants' ratings of their own personality and emotions were weakly associated with political preferences, but their ratings of candidates' personality showed robust associations, and were far more predictive of voting intention than all of the demographic variables, political affiliation, and racial attitudes combined. In Study B, linguistic analysis of narratives revealed words reflective of liberal values were correlated with positive evaluations of Clinton's personality, whereas words reflective of conservative values and “populist” sentiment were correlated with positive evaluations of Trump's personality, suggesting appraisals of candidates may be associated with values. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Five Factor Model of Personality (FFM); Liberal and conservative values; Linguistic analysis; Political preferences; dept.psy; peer-reviewed; “Populist” sentiment

Personality, Well-Being, and Cognitive-Affective Styles: A Cross-Sectional Study of Adult Third Culture Kids - Abe, Jo Ann A. (Journal of Cross-Cultural Psychology, 2018)
Third Culture Kids (TCKs) and their adult counterparts (ATCKs) refer to individuals who spent part of their developmental years abroad and are an important demographic to study in this rapidly globalizing world. To date, the bulk of the research on (A)TCKs has been descriptive and little is known about their developmental trajectories in adulthood. The major objective of this study was to examine the personality traits, dimensions of well-being, and cognitive-affective styles of ATCKs across the adult life span using well-validated psychological measures. A subsidiary goal was to develop a new multidimensional international experiences scale to assess levels of multicultural engagement in ATCKs. The participants in this study (N = 700+; age = 18-80+) were recruited from the Alumni Office of an international school in Japan. Somewhat contrary to how they are often depicted in the news media and in qualitative studies, the ATCKs showed normative changes in personality and well-being in the direction of greater maturity and adjustment during adulthood, with those reporting higher levels of multicultural engagement generally exhibiting a more resilient personality profile, higher levels of well-being, and more adaptive cognitive and affective styles.
Keywords: adult third culture kids; dept.psy; five-factor model of personality; need for closure; peer-reviewed; well-being

Influence of prenatal pre-exposure to an odor on intake behavior of an aversive solution in newborn rats. - Kamenetzky, Giselle V; Suarez, Andrea B; Ifran, Maria Celeste; Nizhnikov, Michael E; Pautassi, Ricardo M (Neuroscience letters, 2018)
Early pre- or postnatal sensory experiences significantly influence flavor preference and food intake, and can induce liking for innately unpalatable flavors. Previous work found that newborn rats stimulated with an odor experienced shortly after birth exhibited heightened intake and seeking towards an artificial nipple containing quinine. This result suggests that odors made familiar trough early postnatal pre-exposure can shift the motivational value of unconditional stimuli. The objective of the current study was to assess the effect of an odor (lemon) experienced in-utero on the first intake responses towards an artificial nipple supplying quinine. The hypothesis, which was corroborated, was that stimulation with the olfactory stimulus experienced in-utero would increase the newborn's intake and grasp responses to the artificial nipple containing quinine. Exposure to the odor that had been pre-exposed in utero increased quinine intake and seeking (i.e., latency to grasp and total time in contact with the nipple, as well as number of and mean duration of nipple grasps) in 3-h-old pups. These results replicate those previously found with postnatal odor pre-exposure, and extend the phase for pre-exposure to the prenatal stage. Copyright © 2018 Elsevier B.V. All rights reserved.
Keywords: *Eating; *Feeding Behavior; *Odorants; *Prenatal Exposure Delayed Effects; *Quinine/ad [Administration & Dosage]; Animals; Animals, Newborn; Animals, Suckling; Article; Eating; Feeding Behavior; Female; Male; Neonate rat; Odor pre-exposure; Odorants; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal exposure; Quinine; Rats, Sprague-Dawley; Smell; Sprague Dawley rat; animal; animal experiment; aversive agent; controlled study; dept.psy; eating; feeding behavior; female; food intake; fragrance; learning; male; newborn; nipple; nonhuman; odor; peer-reviewed; pregnancy; prenatal exposure; priority journal; quinine; rat; smelling; stimulation; suckling animal

Intentional multiple mating by females in a species where sneak fertilization circumvents female choice for parental males - Stiver, Kelly A.; Kindsvater, Holly K.; Tamburello, Natascia; Heckman, Kellie L.; Klein, Joanne; Alonzo, Suzanne H. (Journal of Fish Biology, 2018)
This paper describes how individual female ocellated wrasse Symphodus ocellatus distribute their spawning among males and nests in space and time. It is based on previously collected genetic data of larvae from ten different nests (used to reconstruct half and full-sibling groupings both within and among nests on multiple days) and behavioural data of marked females across the reproductive season. Both the genetic analyses and behavioural observations confirm that female S. ocellatus intentionally engage in multiple mating, by repeatedly spawning at the same nest on different days and at several different nests (up to 12 spawning events over 3 weeks), leading to mixed paternity among her young. The main benefit of such high and intentional multiple mating is probably insurance against brood failure due to nest predation, desertion or poor paternal care by the male. These findings reveal that even in systems where females attempt to avoid male-controlled mixed paternity, they may still engage in intentional multiple mating due to these potential benefits. © 2018 The Fisheries Society of the British Isles
Keywords: Animals; Female; Fertilization; Male; Mating Preference, Animal; Paternity; Perciformes; Reproduction; Sexual Behavior, Animal; Symphodus ocellatus; animal; behaviour; dept.psy; female; fertilization; male; mate choice; mating systems; paternity; peer-reviewed; reproduction; sexual behavior; sexual conflict; sexual selection; trade-offs

Substance use, anxiety, and depressive symptoms among college students - Walters, Kenneth S.; Bulmer, Sandra Minor; Troiano, Peter F.; Obiaka, Uzoma; Bonhomme, Rebecca (Journal of Child & Adolescent Substance Abuse, 2018)
Research on college substance use and mental illness is limited and inconsistent. Measures of substance use, and anxiety and depressive symptoms, were completed by 1,316 undergraduates within a major drug transportation corridor. Hierarchical linear regressions were used to test associations between anxious and depressive symptoms and substance use (i.e., alcohol, cannabis, tobacco, cocaine, other amphetamines, sedatives, hallucinogens, and designer drugs). Depressive symptoms were associated with use of cannabis, tobacco, amphetamines, cocaine, sedatives, and hallucinogens. Anxiety symptoms were unrelated to substance use. These findings support the need for education and prevention at universities, emphasizing tobacco, cannabis, and certain “harder” drugs.
Keywords: anxiety; college students; depression; dept.hhs; dept.psy; mental health; peer-reviewed; substance use

Electrophysiological Indices of Audiovisual Speech Perception: Beyond the McGurk Effect and Speech in Noise. - Irwin, Julia; Avery, Trey; Brancazio, Lawrence; Turcios, Jacqueline; Ryherd, Kayleigh; Landi, Nicole (Multisensory research, 2018)
Visual information on a talker's face can influence what a listener hears. Commonly used approaches to study this include mismatched audiovisual stimuli (e.g., McGurk type stimuli) or visual speech in auditory noise. In this paper we discuss potential limitations of these approaches and introduce a novel visual phonemic restoration method. This method always presents the same visual stimulus (e.g., /ba/) dubbed with a matched auditory stimulus (/ba/) or one that has weakened consonantal information and sounds more /a/-like). When this reduced auditory stimulus (or /a/) is dubbed with the visual /ba/, a visual influence will result in effectively 'restoring' the weakened auditory cues so that the stimulus is perceived as a /ba/. An oddball design in which participants are asked to detect the /a/ among a stream of more frequently occurring /ba/s while either a speaking face or face with no visual speech was used. In addition, the same paradigm was presented for a second contrast in which participants detected /pa/ among /ba/s, a contrast which should be unaltered by the presence of visual speech. Behavioral and some ERP findings reflect the expected phonemic restoration for the /ba/ vs. /a/ contrast; specifically, we observed reduced accuracy and P300 response in the presence of visual speech. Further, we report an unexpected finding of reduced accuracy and P300 response for both speech contrasts in the presence of visual speech, suggesting overall modulation of the auditory signal in the presence of visual speech. Consistent with this, we observed a mismatch negativity (MMN) effect for the /ba/ vs. /pa/ contrast only that was larger in absence of visual speech. We discuss the potential utility for this paradigm for listeners who cannot respond actively, such as infants and individuals with developmental disabilities.
Keywords: Audio-visual speech; Audio-visual stimulus; Audiovisual; Audiovisual speech perception; Auditory stimuli; Developmental disability; ERP; Electrophysiology; Enterprise resource planning; Mismatch negativity; Phonemic restoration; Potential utility; Restoration; Speech; Speech recognition; Visual information; dept.psy; peer-reviewed; phonemic restoration

Personality, Emotional Qualities of Leisure, and Subjective Well-Being in the Elderly. - Kahlbaugh, Patricia; Huffman, Loreen (International journal of aging & human development, 2017)
In this study, we examined personality traits of older adults and their emotional experiences associated with engaging in specific leisure activities. Older individuals (17 males, 32 females), ages ranging from 65 to 97 years (mean age 74), completed measures of Big Five personality traits, positive and negative affect, subjective well-being (SWB), independent functioning, and an emotion-activity inventory. As expected, Extraversion, Agreeableness, Conscientiousness, and Openness to experience were related to positive affect, while Neuroticism was related to negative affect. Openness and Agreeableness were related to positive emotions experienced in social and cognitive domains, and Agreeableness was related to greater SWB, greater positive affect, and more positively experienced activities. Neuroticism was related to lower SWB and fewer positively experienced activities. These findings suggest that assessing the fit between personality and emotions experienced during activities should be considered when creating programs tailored to elderly individuals, with the goal of encouraging more active and rewarding lives.
Keywords: *Aging/px [Psychology]; *Emotions; *Leisure Activities; *Personal Satisfaction; *Personality; Affect; Aged; Aged, 80 and over; Aging; Emotions; Female; Humans; Leisure Activities; Male; Personal Satisfaction; Personality; affect; aged; aging; dept.psy; emotion; emotions; female; human; leisure; male; personality; psychology; satisfaction; subjective well-being; successful aging; very elderly

Restraint stress enhances alcohol intake in adolescent female rats but reduces alcohol intake in adolescent male and adult female rats. - Wille-Bille, Aranza; Ferreyra, Ana; Sciangula, Martina; Chiner, Florencia; Nizhnikov, Michael E; Pautassi, Ricardo Marcos (Behavioural brain research, 2017)
Adolescents may be more sensitive to stress-induced alcohol drinking than adults, which would explain the higher prevalence of alcohol abuse and dependence in late adolescence than in adulthood. The present study analyzed the impact of restraint stress on the initiation of alcohol intake across 2 weeks of intermittent, two-bottle choice intake in male and female adolescent rats and adult female rats. Restraint stress significantly increased alcohol intake and preference in female adolescent rats but decreased alcohol intake and preference in male adolescent and female adult rats. The effects of restraint stress on alcohol intake were mitigated in adolescent females following administration of the kappa opioid receptor antagonist norbinaltorphimine. Adolescent but not adult female rats that were subjected to restraint stress spent more time on the open arms of the elevated plus maze. Female adolescents exposed to stress also exhibited greater risk-taking behaviors in a concentric square field test compared with non-stressed controls. These results indicate age- and sex-related differences in the sensitivity to alcohol-stress interactions that may facilitate the initiation of alcohol use in female adolescents. The facilitatory effect of stress on alcohol intake was related to greater exploratory and risk-taking behaviors in young females after stress exposure. Copyright © 2017 Elsevier B.V. All rights reserved.
Keywords: *Aging/ph [Physiology]; *Aging/px [Psychology]; *Alcohol Drinking/pp [Physiopathology]; *Alcohol Drinking/px [Psychology]; *Sex Characteristics; *Stress, Psychological/pp [Physiopathology]; Adolescents; Adults; Age differences; Aging; Aging/de [Drug Effects]; Alcohol; Alcohol Drinking; Alcohol Drinking/dt [Drug Therapy]; Animals; Article; Central Nervous System Depressants; Central Nervous System Depressants/ad [Administration & Dosage]; Choice Behavior; Choice Behavior/de [Drug Effects]; Choice Behavior/ph [Physiology]; Disease Models, Animal; Ethanol; Ethanol/ad [Administration & Dosage]; Exploratory Behavior; Exploratory Behavior/de [Drug Effects]; Exploratory Behavior/ph [Physiology]; Female; Male; Motor Activity; Motor Activity/de [Drug Effects]; Motor Activity/ph [Physiology]; Naltrexone; Naltrexone/aa [Analogs & Derivatives]; Naltrexone/pd [Pharmacology]; Narcotic Antagonists; Narcotic Antagonists/pd [Pharmacology]; Rats, Wistar; Receptors, Opioid, kappa; Receptors, Opioid, kappa/ai [Antagonists & Inhibitors]; Receptors, Opioid, kappa/me [Metabolism]; Restraint, Physical; Risk-Taking; Sex Characteristics; Stress; Stress, Psychological; Stress, Psychological/dt [Drug Therapy]; Wistar rat; [kappa] opioid receptors; adolescent; adult; age; aging; alcohol; alcohol consumption; analogs and derivatives; animal; animal experiment; antagonists and inhibitors; behavior assessment; central depressant agent; comparative study; concentric square field test; controlled study; decision making; dept.psy; disease model; drinking behavior; drug effects; drug therapy; elevated plus maze test; exercise; experimental study; exploratory behavior; exploratory behavior test; female; high risk behavior; immobilization stress; kappa opiate receptor; kappa opiate receptor antagonist; male; mental stress; metabolism; motor activity; naltrexone; narcotic antagonist; nonhuman; norbinaltorphimine; pathophysiology; peer-reviewed; physiology; priority journal; psychology; rat; risk assessment; sensitivity analysis; sex difference; sexual characteristics; κ opioid receptors

Electrophysiological Indices of Audiovisual Speech Perception in the Broader Autism Phenotype. - Irwin, Julia; Avery, Trey; Turcios, Jacqueline; Brancazio, Lawrence; Cook, Barbara; Landi, Nicole (Brain sciences, 2017)
When a speaker talks, the consequences of this can both be heard (audio) and seen (visual). A novel visual phonemic restoration task was used to assess behavioral discrimination and neural signatures (event-related potentials, or ERP) of audiovisual processing in typically developing children with a range of social and communicative skills assessed using the social responsiveness scale, a measure of traits associated with autism. An auditory oddball design presented two types of stimuli to the listener, a clear exemplar of an auditory consonant-vowel syllable /ba/ (the more frequently occurring standard stimulus), and a syllable in which the auditory cues for the consonant were substantially weakened, creating a stimulus which is more like /a/ (the infrequently presented deviant stimulus). All speech tokens were paired with a face producing /ba/ or a face with a pixelated mouth containing motion but no visual speech. In this paradigm, the visual /ba/ should cause the auditory /a/ to be perceived as /ba/, creating an attenuated oddball response; in contrast, a pixelated video (without articulatory information) should not have this effect. Behaviorally, participants showed visual phonemic restoration (reduced accuracy in detecting deviant /a/) in the presence of a speaking face. In addition, ERPs were observed in both an early time window (N100) and a later time window (P300) that were sensitive to speech context (/ba/ or /a/) and modulated by face context (speaking face with visible articulation or with pixelated mouth). Specifically, the oddball responses for the N100 and P300 were attenuated in the presence of a face producing /ba/ relative to a pixelated face, representing a possible neural correlate of the phonemic restoration effect. Notably, those individuals with more traits associated with autism (yet still in the non-clinical range) had smaller P300 responses overall, regardless of face context, suggesting generally reduced phonemic discrimination.
Keywords: Article; Audiovisual speech perception; Broader autism phenotype; Development; ERP; audiovisual aid; audiovisual equipment; audiovisual speech perception; autism; behavior; broader autism phenotype; child; clinical article; dept.cmd; dept.hls; dept.psy; development; electrophysiology; female; human; male; participant observation; phenotype; social adaptation; social competence; speech perception; stimulus; vision test

Electrophysiology of perception and processing of phonological information as indices of toddlers' language performance - Harwood, Vanessa; Preston, Jonathan; Grela, Bernard; Roy, Dooti; Harold, Olivia; Turcios, Jacqueline; Andrada, Kiyomi; Landi, Nicole (Journal of Speech Language and Hearing Research, 2017)
Purpose: The toddler years are a critical period for language development and growth. We investigated how event-related potentials (ERPs) to repeated and novel nonwords are associated with clinical assessments of language in young children. In addition, nonword repetition (NWR) was used to measure phonological working memory to determine the unique and collective contribution of ERP measures of phonemic discrimination and NWR as predictors of language ability. Method: Forty children between the ages of 24-48 months participated in an ERP experiment to determine phonemic discrimination to repeated and novel nonwords in an old/new design. Participants also completed a NWR task to explore the contribution of phonological working memory in predicting language. Results: ERP analyses revealed that faster responses to novel stimuli correlated with higher language performance on clinical assessments of language. Regression analyses revealed that an earlier component was associated with lower level phonemic sensitivity, and a later component was indexing phonological working memory skills similar to NWR. Conclusion: Our findings suggest that passive ERP responses indexing phonological discrimination and phonological working memory are strongly related to behavioral measures of language.
Keywords: Brain; Child Language; Child, Preschool; Discrimination (Psychology); Electroencephalography; Evoked Potentials; Female; Humans; Language Tests; Male; Memory, Short-Term; Pattern Recognition, Physiological; Phonetics; Reaction Time; Regression Analysis; Signal Processing, Computer-Assisted; Speech Perception; adult; brain; child; clinical article; dept.psy; electroencephalography; event related potential; evoked response; female; human; language ability; language development; language test; male; pattern recognition; perception; perceptive discrimination; phonetics; physiology; preschool child; reaction time; regression analysis; short term memory; signal processing; speech perception; stimulus; working memory; young adult; ⚠️ Invalid DOI

EdPsych modules - Durwin, Cheryl Cisero; Reese-Weber, Marla J. (SAGE Publications, Inc, 2017)
Now with SAGE Publications, Cheryl Cisero Durwin and Marla Reese-Weber’s EdPsych Modules uses an innovative implementation of case studies and a modular format to address the challenge of effectively connecting theory and research to practice.  Each module is a succinct, stand-alone topic that represents every subject found in traditional chapter texts and can be used in any order for maximum flexibility in organizing your course.  Each of the book’s eight units of modules begins with a set of four case studies–early childhood, elementary, middle school, and secondary–and ends with "Assess" and "Reflect and Evaluate" questions and activities to encourage comprehension and application of the research and theories presented. The case approach and the extensive pedagogy that support it allows students to constantly see the applications of the theories and research that they are studying in the text.
Keywords: dept.psy

The development of gaze to a speaking face. - Irwin, Julia; Brancazio, Lawrence; Volpe, Nicole (The Journal of the Acoustical Society of America, 2017)
When a speaker talks, the visible consequences of what they are saying can be seen. Listeners are influenced by this visible speech both in a noisy listening environment and even when auditory speech can easily be heard. While visible influence on heard speech has been reported to increase from early to late childhood, little is known about the mechanism that underlies this developmental trend. One possible account of developmental differences is that looking behavior to the face of a speaker changes with age. To examine this possibility, the gaze to a speaking face was examined in children from 5 to 10 yrs of age and adults. Participants viewed a speaker's face in a range of conditions that elicit looking: in a visual only (speech reading) condition, in the presence of auditory noise (speech in noise) condition, and in an audiovisual mismatch (McGurk) condition. Results indicate an increase in gaze on the face, and specifically, to the mouth of a speaker between the ages of 5 and 10 for all conditions. This change in looking behavior may help account for previous findings in the literature showing that visual influence on heard speech increases with development.
Keywords: *Facial Expression; *Fixation, Ocular; *Speech Acoustics; *Speech Perception; *Visual Perception; *Voice Quality; Acoustic Stimulation; Acoustics; Age Factors; Audiometry, Speech; Child; Child, Preschool; Cues; Early-to-late; Facial Expression; Female; Fixation, Ocular; Humans; Male; Noise; Noise/ae [Adverse Effects]; Perceptual Masking; Photic Stimulation; Physics; Speech; Speech Acoustics; Speech Perception; Speech in noise; Speech reading; Video Recording; Visible speech; Visual Perception; Voice Quality; Young Adult; age; association; auditory stimulation; child; dept.hls; dept.psy; eye fixation; facial expression; female; human; male; masking; noise; photostimulation; preschool child; speech; speech audiometry; speech perception; videorecording; vision; voice; young adult

Strain-specific programming of prenatal ethanol exposure across generations. - Popoola, Daniel O; Nizhnikov, Michael E; Cameron, Nicole M (Alcohol (Fayetteville, N.Y.), 2017)
Behavioral consequences of prenatal alcohol exposure (PAE) can be transmitted from in utero-exposed F1 generation to their F2 offspring. This type of transmission is modulated by genetic and epigenetic mechanisms. This study investigated the intergenerational consequences of prenatal exposure to a low ethanol dose (1 g/kg) during gestational days 17-20, on ethanol-induced hypnosis in adolescent male F1 and F2 generations, in two strains of rats. Adolescent Long-Evans and Sprague-Dawley male rats were tested for sensitivity to ethanol-induced hypnosis at a 3.5-g/kg or 4.5-g/kg ethanol dose using the loss of righting reflex (LORR) paradigm. We hypothesized that PAE would attenuate sensitivity to ethanol-induced hypnosis in the ethanol-exposed animals in these two strains and in both generations. Interestingly, we only found this effect in Sprague-Dawley rats. Lastly, we investigated PAE related changes in expression of GABAA receptor alpha1, alpha4, and delta subunits in the cerebral cortex of the PAE sensitive Sprague-Dawley strain. We hypothesized a reduction in the cerebral cortex GABAA receptor subunits' expression in the F1 and F2 PAE groups compared to control animals. GABAA receptor alpha1, alpha4, and delta subunits protein expressions were quantified in the cerebral cortex of F1 and F2 male adolescents by western blotting. PAE did not alter cerebral cortical GABAA receptor subunit expressions in the F1 generation, but it decreased GABAA receptor alpha4 and delta subunits' expressions in the F2 generation, and had a tendency to decrease alpha1 subunit expression. We also found correlations between some of the subunits in both generations. These strain-dependent vulnerabilities to ethanol sensitivity, and intergenerational PAE-mediated changes in sensitivity to alcohol indicate that genetic and epigenetic factors interact to determine the outcomes of PAE animals and their offspring. Copyright © 2017 Elsevier Inc. All rights reserved.
Keywords: *Alcohol Drinking/ae [Adverse Effects]; *Behavior, Animal/de [Drug Effects]; *Cerebral Cortex/de [Drug Effects]; *Ethanol/to [Toxicity]; *Prenatal Exposure Delayed Effects; *Receptors, GABA-A/de [Drug Effects]; 4 aminobutyric acid A receptor; 4 aminobutyric acid A receptor alpha1; 4 aminobutyric acid A receptor alpha4; Age Factors; Alcohol Drinking; Alcohol Drinking/ge [Genetics]; Alcohol Drinking/me [Metabolism]; Alcohol Drinking/px [Psychology]; Animals; Article; Behavior, Animal; Blood Alcohol Content; Cerebral Cortex; Cerebral Cortex/me [Metabolism]; Cerebral Cortex/pa [Pathology]; Dose-Response Relationship, Drug; Epigenesis, Genetic; Epigenesis, Genetic/de [Drug Effects]; Ethanol; Ethanol/bl [Blood]; Female; Gestational Age; Long Evans rat; Male; Maternal Exposure; Pregnancy; Prenatal Exposure Delayed Effects; Rats, Long-Evans; Rats, Sprague-Dawley; Reaction Time; Receptors, GABA-A; Receptors, GABA-A/ge [Genetics]; Receptors, GABA-A/me [Metabolism]; Reflex, Righting; Reflex, Righting/de [Drug Effects]; Species Specificity; Sprague Dawley rat; Time Factors; Western blotting; adolescent; adult; age; alcohol; alcohol blood level; alcohol consumption; animal; animal behavior; animal experiment; animal model; animal tissue; blood; brain cortex; comparative study; controlled study; correlational study; dept.psy; dose response; drinking behavior; drug effects; epigenetics; female; genetic epigenesis; genetics; gestation period; gestational age; hemoglobin delta chain; heredity; hypnosis; male; maternal exposure; metabolism; nonhuman; outcome assessment; pathology; peer-reviewed; pregnancy; prenatal exposure; progeny; protein expression; psychology; rat; rat strain; reaction time; righting reflex; species difference; time factor

Audiovisual speech perception: A new approach and implications for clinical populations - Irwin, Julia; DiBlasi, Lori (Language and Linguistics Compass, 2017)
This selected overview of audiovisual (AV) speech perception examines the influence of visible articulatory information on what is heard. Thought to be a cross-cultural phenomenon that emerges early in typical language development, variables that influence AV speech perception include properties of the visual and the auditory signal, attentional demands, and individual differences. A brief review of the existing neurobiological evidence on how visual information influences heard speech indicates potential loci, timing, and facilitatory effects of AV over auditory only speech. The current literature on AV speech in certain clinical populations (individuals with an autism spectrum disorder, developmental language disorder, or hearing loss) reveals differences in processing that may inform interventions. Finally, a new method of assessing AV speech that does not require obvious cross-category mismatch or auditory noise was presented as a novel approach for investigators.
Keywords: dept.psy

Teaching and learning guide for audiovisual speech perception: A new approach and implications for clinical populations. - Irwin, Julia; Turcios, Jacqueline (Language and linguistics compass, 2017)
Keywords: dept.psy